Method for preparing a composite material containing an elastomer and a filler
Patent Information
- Application Number
- JP2023083259
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-06-05
- Filing Date
- 2023-05-19
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2040-06-04
AI Technical Summary
【0058】 集積された製造作業に関して、適用できるならば、本方法は、以下のパラメータの1以上のいずれかを本方法時に更に含むことができる:少なくとも1つの温度制御手段は、該混合時に、65℃以上の温度Tzに設定される;及び/又は、該混合時に、1個以上のローターは、混合時間の少なくとも50%について、少なくとも0.6m/sの先端速度で操作される;及び/又は、ミキサーに、少なくとも、天然ゴムを少なくとも50wt%を含有する固体エラストマー及び湿潤充填剤を装填し、ここで少なくとも固体エラストマー及び湿潤充填剤の乾燥重量ベースの充填率は、68%を超えない;及び/又は、少なくとも1つの温度制御手段により制御されたミキサー温度で該混合を実施し、並びに混合時間にわたり少なくとも2.5kW/kgの平均比出力を適用する;及び/又は、混合が、連続混合工程であり、並びに装填が、連続ミキサーへ、少なくとも固体エラストマー及び湿潤充填剤の連続フローを、装填することを含む;及び/又は、複合材料を得るための第二のミキサー、ここで第二のミキサーは、以下の条件の少なくとも1つの下で操作される:(i)5psi以下のラム圧;(ii)その最高レベルの少なくとも75%まで上昇されたラム;(iii)浮動モードで操作されたラム;(iv)混合物と実質的に接触しないように配置されたラム;(v)ミキサーは、ラム-レスである;並びに、(vi)混合物の充填率が、25%~70%の範囲である;及び/又は、少なくとも1500kJ/kg複合材料の得られる全比エネルギーを生じる、混合時間の少なくとも50%について、少なくとも0.5m/sの先端速度での1個以上のローター操作、ここで湿潤充填剤は、湿潤粒子状充填剤である;及び/又は、任意の、該装填(a)又は該混合(b)時における、分解防止剤及びカップリング剤から選択された少なくとも1種の添加物の添加、並びに任意の、ミキサーが120℃以上の温度へ到達した後の、1種以上のゴム薬品の添加。
Smart Images

Figure 0007642017000001 
Figure 0007642017000002 
Figure 0007642017000003
Abstract
Description
[Technical Field]
[0001] background It is always desirable in the rubber industry to develop methods for dispersing fillers in elastomers, and it is particularly desirable to develop methods that can be efficient in terms of filler dispersion quality, time, effort, and / or cost. [Background technology]
[0002] Numerous commercially significant products are formed from elastomeric compositions in which reinforcing filler materials are dispersed in either various synthetic elastomers, natural rubber, or elastomer compounds. Carbon black and silica, for example, are widely used to reinforce natural rubber and other elastomers. It is common to prepare masterbatches, or premixes, of reinforcing materials, elastomers, and various optional additives, such as extender oils. Such masterbatches are then compounded with processing and cure additives and, upon curing, produce numerous commercially significant products. Such products include, for example, pneumatic and non-pneumatic tires or solid tires for vehicles, including tread portions including caps and bases, undertreads, inner liners, sidewalls, wire skims, carcasses, and the like. Other products include, for example, engine mounts, bushings, conveyor belts, windshield wipers, rubber parts for aerospace and marine equipment, vehicle track elements, seals, liners, gaskets, wheels, bumpers, vibration isolation systems, and the like.
[0003] Good dispersion of reinforcing fillers in rubber compounds is recognized as a factor in achieving mechanical strength and consistent elastomer composite and rubber compound performance. Considerable effort has been expended in developing methods to improve dispersion quality, and various solutions have been offered to address this challenge. For example, more vigorous mixing can improve the dispersion of reinforcing fillers, but can also degrade the elastomer in which the filler is dispersed. This is particularly problematic for natural rubber, which is highly susceptible to mechanical and thermal degradation, especially under dry mixing conditions.
[0004] As an alternative to dry mixing techniques, it is known to feed elastomer latex or polymer solution and carbon black or silica slurry into a liquid mixing system, such as a stirred tank. Such "liquid masterbatch" techniques can be used with natural rubber latex and emulsifiable synthetic elastomers, such as styrene-butadiene rubber (SBR), or other elastomeric polymers in liquid form. However, while wet mixing techniques are promising, batch wet mixing can pose challenges in manufacturing operations. Continuous or semi-continuous techniques for producing liquid masterbatches, such as those disclosed in U.S. Pat. Nos. 6,048,923 and 8,586,651, the contents of which are incorporated herein by reference, are effective for producing elastomer-filler composites characterized by high quality. However, these processes are limited to liquid forms of rubber, such as elastomer latex or a solution form of rubber.
[0005] Therefore, there is a need to develop a method for incorporating fillers into solid elastomers to achieve acceptable or enhanced elastomer composite dispersion quality and functionality from the elastomer composite masterbatch, which can be translated into acceptable or enhanced properties in the corresponding vulcanized rubber compounds and rubber articles. Summary of the Invention [Means for solving the problem]
[0006] summary Disclosed herein are methods for preparing composite materials from solid elastomer(s) and wet filler(s), as well as products containing the composite materials, vulcanized rubbers, and products therefrom.
[0007] One aspect is a method of preparing a composite material, comprising: (a) charging at least a solid elastomer and a wet filler containing a liquid present in an amount ranging from 15% to 65% by weight, based on the total weight of the filler and wet filler, into a mixer having one or more rotors; (b) mixing at least the solid elastomer and the wet filler to form a mixture in one or more mixing steps, and at least one of the mixing steps is performed with at least one temperature control means set to a temperature Tz of 65°C or higher and removing at least a portion of the liquid from the mixture by evaporation; and (c) delivering from the mixer a composite material containing the filler dispersed in the elastomer at a loading of at least 20 phr with a filler yield loss of not more than 10% (e.g., not more than 5%), wherein the composite material has a liquid content of not more than 10% by weight, based on the total weight of the composite.
[0008] Another aspect is a method of preparing a composite material, comprising: (a) charging at least a solid elastomer containing at least 50 wt. % natural rubber and a wet filler containing a liquid present in an amount of at least 15 wt. % based on the total weight of the filler and wet filler into a mixer, wherein the loading on a dry weight basis of the at least solid elastomer and wet filler does not exceed 68%; (b) mixing the at least solid elastomer and wet filler in one or more mixing steps to form a mixture, and in at least one of the mixing steps, conducting the mixing at a mixer temperature controlled by at least one temperature control means and removing at least a portion of the liquid from the mixture by evaporation; and (c) delivering from the mixer a composite material containing the filler dispersed in the elastomer at a loading of at least 20 phr with a filler yield loss of not more than 10%, wherein the composite material has a liquid content of not more than 10 wt. % based on the total weight of the composite.
[0009] Another aspect is a method of preparing a composite material, the method comprising: (a) charging at least a solid elastomer and a wet filler containing a liquid present in an amount of at least 15 wt.%, based on the total weight of the filler and wet filler, into a mixer having one or more rotors; (b) mixing the at least the solid elastomer and the wet filler in the mixer in one or more mixing steps to form a mixture, and in at least one of the mixing steps, conducting the mixing with the one or more rotors operating at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, at a mixer temperature controlled by at least one temperature control means, and removing at least a portion of the liquid from the mixture by evaporation; and (c) discharging from the mixer a composite material containing the filler dispersed in the elastomer at a loading of at least 20 phr with no more than 10% filler yield loss, wherein the composite material has a liquid content of no more than 10 wt.%, based on the total weight of the composite.
[0010] Another aspect is a method of preparing a composite material comprising: (a) charging at least a solid elastomer and a wet filler containing a liquid present in an amount of at least 15 wt. %, based on the total weight of the filler and wet filler, into a first mixer having one or more rotors; (b) mixing the at least the solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of the mixing steps, conducting the mixing with the one or more rotors operating at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, at a mixer temperature controlled by at least one temperature control means, and removing at least a portion of the liquid from the mixture by evaporation; (c) removing from the first mixer a mixture containing the filler dispersed in the elastomer at a loading of at least 20 phr. (d) mixing the mixture from (c) in a second mixer to obtain a composite material, wherein the second mixer is operated under at least one of the following conditions: (i) a ram pressure of 5 psi or less; (ii) a ram raised to at least 75% of its maximum level; (iii) a ram operated in a floating mode; (iv) a ram positioned so as not to substantially contact the mixture; (v) the mixer is ramless; and (vi) a fill factor of the mixture is 25% to 70%; and (e) discharging from the second mixer a composite material having a liquid content of less than 3% by weight, based on the total weight of the composite material.
[0011] Another aspect is a method of preparing a composite material, comprising: (a) charging at least a solid elastomer and a wet filler containing a liquid present in an amount of at least 15 wt. % based on the total weight of the filler and wet filler into a first mixer having one or more rotors; (b) mixing the at least solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of the mixing steps, conducting the mixing at a mixer temperature controlled by at least one temperature control means and applying an average specific power of at least 2.5 kW / kg over the mixing time, and removing at least a portion of the liquid from the mixture by evaporation; and (c) discharging the mixture containing the filler dispersed in the elastomer at a loading of at least 20 phr from the first mixer. (d) mixing the mixture from (c) in a second mixer to obtain a composite material, wherein the second mixer is operated under at least one of the following conditions: (i) a ram pressure of 5 psi or less; (ii) a ram raised to at least 75% of its maximum level; (iii) a ram operated in a floating mode; (iv) a ram positioned so as not to substantially contact the mixture; (v) the mixer is ramless; and (vi) a fill factor of the mixture is 25% to 70%; and (e) delivering from the second mixer a composite material having a liquid content of less than 3% by weight, based on the total weight of the composite material.
[0012] Another aspect of the invention is a method for preparing a composite material, the method comprising: (a) charging a continuous flow of at least a solid elastomer and a pelletized wet filler into an input end of a continuous mixer, wherein the wet filler contains a liquid present in an amount of at least 15 wt. %, based on the total weight of the filler and the wet filler; (b) conveying the solid elastomer and the wet filler along the length of the continuous mixer, wherein during conveying, mixing occurs with removal of at least a portion of the liquid by evaporation; and (c) delivering from the output end of the continuous mixer a composite material containing the filler dispersed in the elastomer at a loading of at least 20 phr with no more than a 10% filler yield loss, wherein the composite material has a liquid content of no more than 10 wt. %, based on the total weight of the composite. One or more embodiments can be adapted to include: the continuous mixer has an elongated chamber; the mixing in (b) can occur by contacting the solid elastomer and the wet filler with one or more rotors axially oriented within the elongated chamber; the temperature of the one or more rotors can be controlled; the mixer can be a continuous mixer, such as a continuous compounder; the conveying in (b) can be carried out by at least one rotatable screw, through which mixing can also occur; the mixer can be a twin-screw extruder; the charging in (a) can include charging a substantially continuous flow of a pre-blend of at least the solid elastomer and the pelletized wet filler; the charging in (a) can separately charge a first substantially continuous flow of the solid elastomer and a second substantially continuous flow of the pelletized wet filler.
[0013] Another aspect is a method of preparing a composite material, comprising: (a) charging a mixer with a solid elastomer and a wetting filler containing a liquid present in an amount of at least 15% by weight based on the total weight of the filler and the wetting filler; (b) mixing at least the solid elastomer and the wetting filler in one or more mixing steps to form a mixture, and in at least one of the mixing steps, conducting the mixing at a mixer temperature controlled by at least one temperature control means and removing at least a portion of the liquid from the mixture by evaporation, wherein during the mixing, the mixer reaches a designated temperature of 120°C or greater; and (c) removing the solid elastomer and the wetting filler from the mixture in one or more mixing steps. (b) optionally adding at least one additive selected from antidegradants and coupling agents during said mixing, and optionally adding one or more rubber chemicals after the mixer reaches a designated temperature; and (d) delivering from the mixer a composite containing filler dispersed in the elastomer at a loading of at least 20 phr with a filler yield loss of not more than 10%, wherein the composite has a liquid content of not more than 10 wt. % based on the total weight of the composite, and wherein said charging (a) and said mixing (b) before the mixer reaches a designated temperature are carried out in the substantial absence of one or more rubber chemicals.
[0014] With respect to any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: at least one temperature control means heats at least the walls of the mixer; at least one temperature control means comprises a jacket with liquid flow means; during one or more mixing steps (step (b)) and optionally during charging (step (a)), the at least one temperature control means is set to a temperature Tz that is 50°C or higher, or 60°C or higher, or 65°C or higher, or 70°C or higher, or in the range of 30°C to 150°C, or in the range of 50°C to 100°C, or in the range of 60°C to 100°C, or in the range of 65°C to 100°C, or in the range of 70°C to 100°C; at least 50% of the filler is carbon black and / or silicon-treated carbon black, and in one or more mixing steps (step (b)) and optionally during loading (step (a)), at least one temperature control means is set to a temperature Tz that is 65°C or higher, or 70°C or higher, or in the range of 65°C to 100°C, or in the range of 70°C to 100°C; at least 50% of the filler is silica, and in one or more mixing steps (step (b)) and optionally during loading (step (a)), at least one temperature control means is set to a temperature Tz that is 50°C or higher, or 60°C or higher, or 65°C or higher, or 70°C or higher, or in the range of 30°C to 150°C, or in the range of 50°C to 100°C, or in the range of 60°C to 100°C, or in the range of 65°C to 100°C, or in the range of 70°C to 100°C.
[0015] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: in at least one of said mixing steps, said mixing is carried out with one or more rotors operating at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, with the mixer temperature controlled by at least one temperature control means; the tip speed is at least 0.7 m / s, or at least 1 m / s, or in the range of 0.6 m / s to 10 m / s.
[0016] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the total resulting specific energy for mixing is at least 1,100 kJ / kg composite; the total resulting specific energy for mixing is at least 1,100 kJ / kg composite and the filler contains silica; the total resulting specific energy for mixing is at least 1,400 kJ / kg composite; the total resulting specific energy for mixing is at least 1,500 kJ / kg composite; or the total resulting specific energy for mixing is at least 1,500 kJ / kg composite after substantially all of the wet filler has been charged to the mixer. 100%filler is at least 1,100 kJ / kg composite; the specific energy E obtained for mixing after at least 75 wt. % of the total wet filler is loaded into the mixer 75%filler is at least 1,300 kJ / kg composite material; the mixing in step (b) (in one or more mixing steps) is performed by applying energy E R This includes applying the energy efficiency in the range of 20% to 80% according to the following formula: Energy efficiency = Required heat / E R × 100% (where the heat requirement is the energy required to remove liquid from 1 kg of composite material at 100% efficiency); the energy efficiency is in the range of 40% to 55%; the time-average release rate of liquid per kg of composite material on a dry weight basis is in the range of 0.01 to 0.14 kg / (min kg), or 0.01 to 0.07 kg / (min kg); and the one or more mixing steps include applying an average specific power of at least 2.5 kW / kg over a mixing time, which can be a ram stop time.
[0017] With respect to any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the fill factor of the mixture is not more than 72%, not more than 70%, not more than 68%, or in the range of 50% to 70%, or in the range of 50% to 68%; the mixer is a batch mixer equipped with a ram capable of downward vertical movement to a lowest position, wherein during mixing, the mixer is operated with a maximum ram deflection from the lowest position a distance not exceeding 30% of the diameter of one or more rotors.
[0018] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the wetting filler has liquid present in an amount of at least 15 wt%, at least 20 wt%, at least 30 wt%; the wetting filler has liquid present in an amount of 30% to 65 wt%, or 40% to 65 wt%; the wetting filler has liquid present in an amount determined as a function of the OAN of the filler according to the formula: k*OAN / (100+OAN)*100, where, for carbon black, k ranges from 0.6 to 1.1, or from 0.8 to 1.05, or from 0.9 to 1; the mixture further includes a non-wetting filler; the wet filler is in the form of a powder, paste, pellet, or cake, e.g., in the form of a powder or pellet; at least 30 wt% of the total filler charged to the mixer is wet filler; at least 90 wt% of the total filler charged to the mixer is wet filler.
[0019] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the mixing comprises removing at least 50% by weight of the liquid by evaporation; the mixing can also comprise removing the liquid from the mixture by pressing, compressing, squeezing, or any combination thereof; the liquid comprises water; the liquid further comprises at least one ingredient selected from a base, an acid, a salt, a surfactant, and a processing aid.
[0020] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the loading comprises loading at least a portion of the solid elastomer into the mixer followed by loading at least a portion of the wet filler into the mixer; the loading comprises multiple additions of the filler; during loading at least a portion of the solid elastomer into the mixer, the elastomer is heated to a temperature of 90°C or greater before loading at least a portion of the wet filler into the mixer; during loading or mixing, the method further comprises adding at least one antidegradant; the at least one antidegradant is N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine.
[0021] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the delivered composite material has a liquid content not exceeding 5% by weight; the delivered composite material has a liquid content not exceeding 3% by weight; the delivered composite material has a liquid content not exceeding 2% by weight; the delivered composite material has a liquid content in the range of 0.1% to 10% by weight; and the composite material has a filler yield loss not exceeding 5%, or not exceeding 3% by weight.
[0022] With respect to any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: one or more rubber chemicals are not present in the delivered composite (in step (c)); the one or more rubber chemicals are selected from processing aids and activators; the one or more rubber chemicals are selected from zinc oxide, fatty acids, zinc salts of fatty acids, waxes, accelerators, resins, and process oils; the mixture consists essentially of a solid elastomer and a wetting filler; the mixture consists essentially of a solid elastomer, a wetting filler, and an stabilizing agent; the composite consists essentially of a filler and an stabilizing agent dispersed in the elastomer; the composite consists of a filler dispersed in the elastomer; the composite consists of a filler and an stabilizing agent dispersed in the elastomer.
[0023] For any aspect or method or embodiment disclosed herein, where applicable, mixing is performed in one mixing step.
[0024] With respect to any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the mixing is carried out in two or more mixing steps; the mixer is a first mixer, and the method further includes further mixing the mixture in the first mixer or a second mixer, or both, after the mixing and before the discharging to obtain a composite material; before the further mixing, after the mixing, the method further includes stopping the mixing and obtaining the mixture; the further mixing reduces the liquid content of the mixture compared to the liquid content of the mixture after the mixing; the mixture formed in step (b) obtains a material temperature of less than 180°C before the initiation of the further mixing by standing time or by cooling or both; a second mixer different from the first mixer of step (a) is utilized for the further mixing; after the further mixing and before the discharging, further mixing is performed in a third mixer to obtain a composite material; the first mixer is a tangential mixer or an intermeshing mixer, and the second mixer is the first mixer is a tangential mixer or an intermeshing mixer, and the second mixer is a kneader, a single-screw extruder, a twin-screw extruder, a multi-screw extruder, a continuous compounder, or a roll mill; the first mixer is a first tangential mixer, and the second mixer is a second tangential mixer; the second mixer is operated under at least one of the following conditions: (i) a ram pressure of 5 psi or less; (ii) a ram raised to at least 75% of its maximum level; (iii) a ram operated in a floating mode; (iv) a ram positioned so as not to substantially contact the mixture; (v) the mixer is ramless; and (vi) a fill factor of the mixture is in the range of 25% to 70%; the method further includes delivering the composite material from the first mixer to the second mixer; the mixing and the further mixing are carried out as a batch process, a continuous process, a semi-continuous process, or a combination thereof.
[0025] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the time between the start of mixing and delivery is less than 30 minutes, less than 15 minutes, in the range of 3 minutes to 30 minutes, in the range of 5 minutes to 15 minutes; the ram stop time is less than 30 minutes, less than 15 minutes, less than 10 minutes, in the range of 3 minutes to 30 minutes, or 5 minutes to 15 minutes, or 5 minutes to 10 minutes.
[0026] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: At the time of delivery, the temperature of the mixer is in the range of 120°C to 180°C or 130°C to 170°C.
[0027] With respect to any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the method can be a continuous process; the mixing can be carried out in a continuous mixer; the method can be a batch process; the mixer is an internal mixer; the mixer is a tangential mixer or an intermeshing mixer; the mixer has a chamber volume of at least 10 L; the mixing is carried out in at least one rotor selected from a two-blade rotor, a four-blade rotor, a six-blade rotor, an eight-blade rotor, and one or more screw rotors.
[0028] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the composite material has an oil content of less than 5 wt. % based on the total weight of the composite material or less than 1 wt. % based on the composite material, and optionally the filler comprises silica.
[0029] With respect to any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: further including at least one additional processing step or post-processing step selected from extruding, calendering, milling, granulating, baling, compounding, and sheeting; wherein the at least one additional processing step is carried out by one or more of a kneader, a roll mill, a screw extruder, a twin-screw extruder, a multi-screw extruder, a continuous compounder, and a twin-screw sheeter.
[0030] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any of one or more of the following embodiments: the filler comprises at least one material selected from carbonaceous materials, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, and coated and treated materials thereof; the filler comprises at least one material selected from carbon black and coated and treated materials thereof (e.g., carbon black and / or silicon-treated carbon black); at least 50 wt% of the filler is selected from carbon black and coated and treated materials thereof; or at least 90 wt% of the filler is carbon black.
[0031] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the filler comprises carbon black dispersed in the elastomer at a loading in the range of 30 phr to 150 phr, e.g., 20 phr to 100 phr, 30 phr to 70 phr, or 40 phr to 65 phr; ... 2 / g~200m 2 / g; the filler contains carbon black with an STSA in the range of 60m 2 / g~200m2 / g; the filler includes carbon black having a COAN in the range of 60 mL / 100 g to 120 mL / 100 g; the filler includes carbon black having a COAN in the range of 60 mL / 100 g to 120 mL / 100 g 2 / g~170m 2 / g and a COAN ranging from 70 mL / 100 g to 115 mL / 100 g.
[0032] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the wet filler comprises never-dried carbon black; the wet filler comprises dry carbon black that has been rewetted; the wet filler comprises dry carbon black that has been rewetted in a pelletizer, fluidized bed, spray, mixer, or rotating drum; prior to being rewetted, the dry carbon black pellets have been subjected to at least one process selected from milling, granulation, grinding, and classification; the wet filler comprises carbon black pellets; the wet filler comprises one or more of granulated, agglomerated, or fluffed carbon black;
[0033] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the at least one filler is selected from carbon black, silica, and silicon-treated carbon black, and the elastomer comprises natural rubber; the at least one filler is selected from carbon black, silica, and silicon-treated carbon black, and the elastomer comprises natural rubber and at least one additional elastomer; and the at least one additional elastomer is selected from polybutadiene and styrene-butadiene rubber.
[0034] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the filler comprises silica; at least 50% of the filler is silica; at least 90% of the filler is silica; the silica is selected from precipitated silica, fumed silica, silica gel, and colloidal silica; the filler further comprises carbon black; the filler further comprises carbon black in an amount ranging from 1% to 10% by weight, based on the total weight of the filler; the method further includes charging a coupling agent to the mixer; the coupling agent is charged with at least a portion of the wet filler.
[0035] With respect to any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the filler comprises silica; wherein during the one or more mixing steps (step (b)) and optionally during the charging step (step (a)), the at least one temperature control means is set to a temperature Tz in the range of 40°C to 110°C, 40°C to 100°C, 40°C to 90°C, 40°C to 75°C, or in the range of 50°C to 110°C, 50°C to 100°C, 50°C to 90°C, or 50°C to 75°C; and the wet filler has liquid present in an amount in the range of at least 20% by weight, at least 30% by weight, 20% to 75% by weight, 20% to 65% by weight, 20% to 60% by weight, 20% to 50% by weight, or 40% to 65% by weight.
[0036] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the filler comprises silica; the silica is dispersed in the elastomer at a loading in the range of 30 phr to 180 phr, or in the range of 30 phr to 150 phr, or in the range of 30 phr to 100 phr, or in the range of 40 phr to 75 phr; the silica is dispersed in the elastomer at a loading in the range of 80 m 2 / g~250m 2 / g; the silica has an STSA in the range of 80m 2 / g~200m 2 / g range; wet fillers include silica that never dries.
[0037] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the solid elastomer is selected from the group consisting of natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene-based elastomers, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers, and the like. the solid elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, nitrile rubber, hydrogenated nitrile rubber, and blends thereof; the elastomer comprises natural rubber, for example, at least 50 wt %, or at least 70 wt %, or at least 90 wt % of the solid elastomer is natural rubber; the elastomer is selected from one or more of natural rubber, styrene-butadiene rubber, and oil-extended styrene-butadiene rubber.
[0038] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: further comprising blending the delivered composite material with at least one additional elastomer; the at least one additional elastomer is the same as the solid elastomer; the at least one additional elastomer is different from the solid elastomer for forming the composite material containing the elastomer blend; the solid elastomer is natural rubber, and the at least one additional elastomer is selected from polybutadiene and styrene-butadiene rubber. the solid elastomer is a first solid elastomer, and charging further comprises charging the mixer with at least one additional solid elastomer; the at least one additional elastomer is the same as the first solid elastomer; the at least one additional elastomer is different from the first solid elastomer; the solid elastomer is a blend containing the first solid elastomer and at least one additional elastomer; the first solid elastomer is natural rubber, and the at least one additional elastomer is selected from polybutadiene and styrene-butadiene rubber.
[0039] With respect to any aspect or method or embodiment disclosed herein, including methods related to first and second mixers, the method can further include any one or more of the following embodiments, if applicable: the mixture (discharged from the first mixer) has, at the start of the one or more mixing steps (step (b)), a liquid content reduced to an amount less than 50 wt % of the liquid content of the mixture, for example, a liquid content in the range of 1% to 20 wt %, or in the range of 2% to 15 wt %, or in the range of 5% to 15 wt %, or in the range of 7% to 15 wt %, or in the range of 2% to 5 wt %; the mixture has a material temperature in the range of 100°C to 170°C; the fill factor of the mixture in the first mixer is in the range of 50% to 70%; the tip speed is at least 0.6 m / s, or at least 0.7 m / s, or at least 1 m / s.
[0040] With respect to any aspect or method or embodiment disclosed herein, including methods involving a first and second mixer, the method can further include any one or more of the following embodiments, if applicable: at least 50 wt% of the filler is carbon black; the wet filler has liquid present in an amount of at least 20 wt%, or at least 30 wt%, or in the range of 40% to 65 wt%; during one or more mixing steps of the first mixer (step (b)) and optionally during charging (step (a)), at least one temperature control means controls a temperature of 40°C to 110°C. or in the range of 50°C to 110°C, or in the range of 60°C to 110°C, or 60°C or higher, or 65°C or higher, or in the range of 65°C to 100°C, or in the range of 75°C to 90°C; the mixture (discharged from the first mixer) has a material temperature in the range of 120°C to 150°C, or in the range of 130°C to 140°C, for example, where the solid elastomer comprises natural rubber; the elastomer is selected from natural rubber, styrene-butadiene rubber, butadiene rubber, and blends thereof, and the mixture has a material temperature in the range of 120°C to 170°C.
[0041] With respect to any aspect or method or embodiment disclosed herein, including methods involving a first and second mixer, if applicable, the method can further include any one or more of the following embodiments: the resulting total specific energy of the mixing in the first mixer (in (b)) is in the range of 1000 to 2500 kJ / kg.
[0042] With respect to any aspect or method or embodiment disclosed herein, including methods involving first and second mixers, the method can further include any one or more of the following embodiments, if applicable: at least 50 wt% of the filler is silica; further comprising charging the first mixer with a coupling agent; the coupling agent being charged with at least a portion of the wet filler; during one or more mixing steps in the first mixer (step (b)) and optionally during charging (step (a)), at least one temperature control means controls the temperature to be in the range of 40°C to 100°C, or 40 the wet filler has a liquid present in an amount of at least 20% by weight, or in an amount of 20% to 65% by weight; the delivered mixture (in (c)) has a liquid content in the range of 1% to 10% by weight, or in the range of 2% to 15% by weight; the composite has an oil content of less than 5%, or less than 1% by weight, based on the total weight of the composite; and the mixture has a material temperature in the range of 100°C to 140°C, or 110°C to 140°C, or 130°C to 150°C, or 130°C to 140°C.
[0043] With respect to any aspect or method or embodiment disclosed herein relating to the first and second mixers, if applicable, the method can further include any one or more of the following embodiments: the second mixer is a tangential mixer; the fill factor of the mixture in the second mixer is in the range of 25% to 60%; the fill factor of the mixture in the second mixer is in the range of 25% to 50%.
[0044] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the composite has a Payne Difference Index of at least 105, or at least 110, and optionally at least 50% of the filler is silica.
[0045] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: the filler comprises silicon-treated carbon black; at least 90% of the filler is silicon-treated carbon black; the silicon-treated carbon black is dispersed in the elastomer at a loading ranging from 30 phr to 150 phr; the silicon-treated carbon black is dispersed in the elastomer at a loading ranging from 40 phr to 100 phr; the silicon-treated carbon black is dispersed in the elastomer at a loading ranging from 40 phr to 65 phr; the silicon-treated carbon black is dispersed in the elastomer at a loading ranging from 60 phr to 150 phr. 2 / g~200m 2 / g range; silicon-treated carbon black has an STSA of 60m 2 / g~150m 2 / g range; silicon-treated carbon black has a COAN range of 60 mL / 100 g to 120 mL / 100 g; silicon-treated carbon black has a COAN range of 70 mL / 100 g to 115 mL / 100 g.
[0046] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following embodiments: The filler comprises a blend of at least two fillers selected from carbon black, treated carbon black, silica, and silicon-treated carbon black.
[0047] With respect to any aspect or method or embodiment disclosed herein relating to continuous mixing, the method can further include any one or more of the following embodiments, if applicable: the mixing in (b) occurs by contacting the solid elastomer and the wet filler with one or more rotors axially oriented within an elongated chamber; the temperature of the one or more rotors is controlled; the mixer is a continuous compounder; the conveying in (b) is carried out by at least one rotatable screw, through which mixing also occurs; the mixer is a twin-screw extruder; the charging in (a) includes charging a substantially continuous flow of a pre-blend of at least the solid elastomer and the pelletized wet filler; the charging in (a) includes The method includes separately charging a first substantially continuous flow of a solid elastomer and a second substantially continuous flow of a pelleted wet filler; the charging in (a) further includes charging a substantially continuous flow of an antidegradant; the pelleted wet filler is a filler that never dries; the pelleted wet filler includes a dry filler that has been rewetted; the pelleted wet filler includes carbon black; the pelleted wet filler includes silica; the solid elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene-based elastomers, and blends thereof.
[0048] Another aspect is a composite material containing a filler dispersed in an elastomer, wherein the filler comprises carbon black in an amount of at least 50% by weight based on the total weight of the filler, and the elastomer comprises at least 50% by weight of natural rubber based on the total weight of the elastomer, and the composite material has the following properties: (a) The filler has a state of dispersion in the elastomer according to formula (1): A≦1.25*B+x (1) (In the formula: A is the area equivalent diameter (μm) of the filler particles in the composite material. 90 and B is [total area of particles with area-equivalent diameter ≥ 2 μm] / [total image area] × 100% where B≧1%; A and B are determined by light microscopy in transmission mode on microtome sections, and x is a number ranging from 15 to 20; and (b) The composite material has properties according to equation (2): G'(0.1%) / G'(200%)≦0.1*G'(50%)-y (2) where G'(0.1%) is the dynamic storage modulus measured at 0.1% strain amplitude, G'(200%) is the dynamic storage modulus measured at 200% strain amplitude, G'(50%) is the dynamic storage modulus measured at 50% strain amplitude, the dynamic storage moduli measured at a frequency of 1 Hz and 100°C, and y is a number in the range of 7 to 10.
[0049] Regarding the composite material, any one or more of the following embodiments may be applied: the filler comprises carbon black in an amount of at least 90% by weight relative to the total weight of the filler; the elastomer further comprises at least one rubber selected from polybutadiene rubber and styrene-butadiene rubber; x=15; y=10; the carbon black is at least 60 m 2 / g STSA; carbon black is 60m 2 / g~210m 2 / g range; the carbon black has a COAN of at least 75 mL / 100 g; the carbon black has a BET / STSA ratio in the range of 1 to 1.2; the composite has a carbon black loading of 60 phr or less, for example, a loading in the range of 30 phr to 60 phr or 40 phr to 60 phr; the filler further comprises silica; the composite consists of or consists essentially of a filler dispersed in an elastomer at a loading of at least 20 phr; the composite consists of or consists essentially of a filler and a stabilizing agent dispersed in an elastomer at a loading of at least 20 phr.
[0050] Another aspect is a method of making a vulcanized rubber comprising combining any of the composite materials disclosed herein with at least one curative and / or curing any of the composite materials disclosed herein in the presence of at least one curative.
[0051] Another aspect is a vulcanized rubber prepared from any of the composite materials disclosed herein.
[0052] Another aspect is a vulcanized rubber containing a filler dispersed in an elastomer, wherein the filler comprises carbon black in an amount of at least 50% by weight based on the total weight of the filler, and the elastomer comprises at least 50% by weight of natural rubber based on the total weight of the elastomer, and wherein: Carbon black must be at least 60m 2 / g of STSA and a BET / STSA ratio in the range of 1 to 1.2; and The vulcanized rubber has resistivity and dispersion properties that satisfy equation (3). [ln(R)-3.8] / [0.28*δ]≧0.0004*ν+0.9 (3) (In the formula: R is the resistivity (ohm·cm); δ=(6000·[0.806·φ -1 / 3 β -1 / 3 -1] / ρS)×β 1.43 where: φ = volume fraction of carbon black in the composite, S = BET surface area of carbon black (m 2 / g), ρ = carbon black density, 1.8 g / cm 3 It is estimated that β=φ eff / φ, φ eff is the effective volume fraction of carbon black, taking into account the occluded rubber, calculated from: φ eff= φ[1 + (0.0181 * COAN)] / 1.59, where COAN is the compression oil absorption of the carbon black determined by ASTM D3493; and ν≧65, where ν is the number of particles / mm with an area-equivalent diameter of at least 4 μm as determined by optical microscopy in transmission mode on microtome sections. 2 (The numerical value is .)
[0053] With respect to the vulcanized rubber, any one or more of the following embodiments may be applied: the filler comprises carbon black in an amount of at least 90% by weight relative to the total weight of the filler; the elastomer further comprises at least one rubber selected from polybutadiene rubber and styrene-butadiene rubber; the carbon black is at least 60% by weight. 2 / g~210m 2 / g range; 2 / g~190m 2 / g range; the carbon black has a COAN of at least 75 mL / 100 g; the vulcanized rubber has a loading of carbon black of 60 phr or less; the filler further comprises silica; the vulcanized rubber has a tensile stress ratio M300 / M100 of at least 5.9, at least 6.0, at least 6.1, or at least 6.2, where M100 and M300 refer to the tensile stresses at 100% and 300% elongation, respectively; the vulcanized rubber has a modulus of elasticity (M300 / M100) of not more than 0.22 (e.g., not more than 0.21, not more than 0.2). , not exceeding 0.19, or not exceeding 0.18); the vulcanized rubber has a resistivity index of at least 105; the vulcanized rubber has a tan δ value that is less than the tan δ value of a vulcanized rubber prepared from a dry-mixed composite material having the same composition (a "dry-mixed equivalent"); the vulcanized rubber has a tensile stress ratio M300 / M100 that is greater than the tensile stress ratio of a vulcanized rubber prepared from a dry-mixed composite material having the same composition, where M100 and M300 refer to the tensile stresses at 100% and 300% elongation, respectively.
[0054] With respect to the vulcanized rubber prepared from the composite material, wherein the method for preparing the composite material includes the first and second mixers, the vulcanized rubber may have a tan δ value that is less than the tan δ value of the vulcanized rubber prepared from the mixture delivered in step (c); the vulcanized rubber may have a tensile stress ratio M300 / M100 that is greater than the tensile stress ratio of the vulcanized rubber prepared from the mixture delivered in step (b), wherein M100 and M300 refer to the tensile stresses at 100% and 300% elongation, respectively.
[0055] Another aspect is an article of manufacture containing any of the vulcanized rubbers disclosed herein; ,Ta ear treads, under treads, inner liners, sidewalls, sidewall inserts, wire skims, and For retreaded tires cushion rubber; which may be selected from hoses, linings, liners, seals, gaskets, vibration isolation products, trucks, track pads for truck-propeller vehicle equipment, engine mounts, seismic stabilization devices, sieves for mining equipment, linings for mining equipment, conveyor belts, chute liners, slurry pump liners, mud pump impellers, valve seats, valve bodies, piston hubs, piston rods, plungers, slurry mixing impellers and slurry pump impellers, grinding mill liners, cyclones and hydrocyclones, expansion joints, linings for dredge pumps and outboard pumps for marine equipment, marine shaft seals, and propeller shafts.
[0056] Another aspect is a method of preparing a composite material in an integrated manufacturing operation, comprising: (a) producing a filler at a filler manufacturing facility by a process in which the final product, which is a wet filler, contains a liquid present in an amount of at least 20% by weight based on the total weight of the filler and the wet filler; (b) conveying the wet filler to at least one mixer; (c) charging the at least one mixer with at least a solid elastomer and the wet filler, wherein the at least one mixer has at least one temperature control means; and (d) mixing the at least one mixer with at least one solid elastomer and the wet filler in one or more mixing steps. (e) mixing at least a solid elastomer and a wet filler to form a mixture, and during at least one of the mixing steps, performing the mixing at a mixer temperature controlled by at least one temperature control means, and removing at least a portion of the liquid from the mixture by evaporation; and (e) delivering from the at least one mixer a composite material containing the filler dispersed in the elastomer at a loading of at least 20 phr with a filler yield loss of not more than 10%, wherein the composite material has a liquid content of not more than 10 wt.% based on the total weight of the composite.
[0057] With respect to integrated manufacturing operations, if applicable, the method can further include any one or more of the following embodiments: the wet filler is a never-drying filler; the filler manufacturing facility is a carbon black manufacturing facility and the wet filler is a never-drying carbon black; the filler manufacturing facility is a precipitated silica manufacturing facility and the wet filler is a never-drying precipitated silica; the filler manufacturing facility is a silicon-treated carbon black manufacturing facility; and further including preparing a vulcanized rubber containing the elastomer composite, and optionally forming an article comprising the vulcanized rubber or the elastomer composite.
[0058] For integrated manufacturing operations, if applicable, the method may further include any one or more of the following parameters during the method: at least one temperature control means is set to a temperature Tz of 65°C or greater during the mixing; and / or, during the mixing, one or more rotors are operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time; and / or, charging the mixer with at least a solid elastomer containing at least 50 wt% natural rubber and a wet filler, wherein the loading level on a dry weight basis of the at least solid elastomer and the wet filler does not exceed 68%; and / or, carrying out the mixing with a mixer temperature controlled by at least one temperature control means and applying an average specific power of at least 2.5 kW / kg over the mixing time; and / or, wherein the mixing is a continuous mixing process and the charging includes charging a continuous flow of at least the solid elastomer and the wet filler into the continuous mixer. and / or a second mixer to obtain the composite, wherein the second mixer is operated under at least one of the following conditions: (i) a ram pressure of 5 psi or less; (ii) a ram raised to at least 75% of its maximum level; (iii) a ram operated in a floating mode; (iv) a ram positioned so as not to substantially contact the mixture; (v) the mixer is ramless; and (vi) a fill factor of the mixture is in the range of 25% to 70%; and / or one or more rotors operating at a tip speed of at least 0.5 m / s for at least 50% of the mixing time to produce a resultant total specific energy of at least 1500 kJ / kg of composite, wherein the wet filler is a wet particulate filler; and / or, optionally, the addition of at least one additive selected from stabilizing agents and coupling agents during said charging (a) or said mixing (b), and optionally the addition of one or more rubber chemicals after the mixer has reached a temperature of 120°C or greater.
[0059] Those skilled in the art will readily appreciate that, where applicable, any of the aspects or embodiments disclosed herein can be combined, for example, any two, three, four, etc. DETAILED DESCRIPTION OF THE INVENTION
[0060] Detailed Description In part, disclosed herein is a method for preparing or forming a composite material by mixing a solid elastomer with a wet filler. In part, also disclosed herein are composite materials, vulcanized rubbers, and articles formed therefrom.
[0061] When mixing fillers and elastomers, it is difficult to ensure that the mixing time is long enough to ensure sufficient filler incorporation and dispersion before the elastomer in the mixture is exposed to high temperatures and undergoes degradation. In typical dry mixing processes, mixing times and temperatures are controlled to avoid such degradation, and the ability to optimize filler incorporation and dispersion is often not possible.
[0062] By utilizing a wet filler (e.g., containing filler and liquid) according to the presently claimed method, sufficient liquid is present in the mixture so that batch times and temperatures can be controlled better than those achievable with known dry mixing processes. Other benefits, such as enhanced filler dispersion and / or promotion of rubber-filler interaction and / or improved rubber compound properties, may be achieved.
[0063] Wet fillers are typically not used in commercial production due to the relatively long mixing times inherently required for evaporation of the liquid and dispersion of the filler in the elastomer (compared to "dry" mixing or dry mix or dry-mixed, i.e., dry filler mixed with solid elastomer).
[0064] Generally, and as described herein, the mixing process can be managed by controlling one or more mixer or process parameters, such as controlled mixer surface temperature, rotor speed, fill rate, ram pressure, incorporation of rubber chemicals (if any) late in the mixing cycle, composite discharge temperature, specific power, and / or the number of mixing steps or stages, e.g., applying two or more mixing stages.
[0065] The composite material formed by the methods disclosed herein can be considered an uncured mixture of filler(s) and elastomer(s), optionally with one or more additives, which are discussed in more detail herein. The composite material formed can be considered a mixture or masterbatch. The composite material formed can optionally be an intermediate product that can be used in subsequent rubber compounding and one or more vulcanization processes. Prior to compounding and vulcanization, the composite material can also be subjected to additional processes, such as one or more holding or further mixing step(s), one or more additional drying steps, one or more extrusion steps, one or more rolling steps, one or more milling steps, one or more granulation steps, one or more scraping steps, one or more twin-screw output extrusion steps, or one or more rubber working steps to obtain a rubber compound or rubber product.
[0066] A method for preparing a composite material includes charging or introducing into a mixer at least a solid elastomer and a wetting filler, e.g., a) one or more solid elastomers, and b) one or more fillers, wherein at least one filler or a portion of at least one filler is wetted with a liquid (wetting filler) prior to mixing with the solid elastomer. The combination of the solid elastomer with the wetting filler forms a mixture during the mixing step(s).
[0067] Wetting filler The method further includes performing mixing in which at least a portion of the liquid is removed by evaporation or by an evaporation process occurring during mixing in one or more mixing steps. The liquid of the wetting filler can be removed by evaporation (and at least a portion can be evaporated under the listed mixing conditions) and can be a volatile liquid, for example, volatile at the bulk mixture temperature. The volatile liquid can be or include water, for example, at least 50 wt% water, at least 75 wt% water, at least 90 wt% water, at least 95 wt% water, or at least 99 wt% water. For example, the liquid has a low boiling point of 180°C or less at 1 atm, e.g., 170°C or less, 160°C or less, 150°C or less, 140°C or less, 130°C or less, 120°C or less, 110°C or less, or 105°C or less, e.g., 60°C to 180°C, 60°C to 170°C, 60°C to 160°C, 60°C to 150°C, 60°C to 140°C, 60°C to 13 ... The volatile liquid may have a boiling point of 90°C to 120°C, 60°C to 110°C, 60°C to 100°C, 60°C to 90°C, 90°C to 180°C, 90°C to 170°C, 90°C to 160°C, 90°C to 150°C, 90°C to 140°C, 90°C to 130°C, 90°C to 120°C, 90°C to 110°C, 90°C to 100°C, 95°C to 120°C, or 95°C to 110°C, etc. For example, a volatile liquid can be distinguished from oils (e.g., extender oils, process oils) that may be present during at least some of the mixing, meaning that such oils are present in the delivered composite material and therefore are not evaporated during a substantial portion of the mixing time.
[0068] Regarding the wet filler, in one embodiment, the wet filler has a solid consistency. Optionally, the dry filler is wetted only to the extent that the resulting wet filler maintains the form, or similar consistency, of a powder, particle, pellet, cake, or paste, and / or has the appearance of a powder, particle, pellet, cake, or paste. The wet filler does not flow like a liquid (at zero applied stress). Optionally, the wet filler, whether it is individual particles, agglomerates, pellets, cake, or paste, can maintain its shape at 25°C when molded into such a shape. The wet filler is not a composite made by a liquid masterbatch process, and is not any other pre-compounded composite of filler dispersed (from an elastomer in a liquid state) in a solid elastomer in which the elastomer is the continuous phase. In another embodiment, the wet filler can be a slurry. In yet another embodiment, the wet filler is not a filler slurry and does not have the consistency of a liquid or slurry.
[0069] In their dry state, fillers may contain no or a small amount of liquid (e.g., water or moisture) adsorbed on their surface. For example, carbon black may have 0 wt. %, or 0.1 wt. % to 1 wt. %, or up to 3 wt. % or up to 4 wt. % liquid, and precipitated silica may have a liquid (e.g., water or moisture) content of 4 wt. % to 7 wt. % liquid, e.g., 4 wt. % to 6 wt. % liquid. Such fillers are referred to herein as dry fillers or non-wetting fillers. With respect to the present wet fillers, liquid or additional liquid may be added to the filler and may be present on a substantial portion or substantially all of the filler's surface, including interior surfaces or pores accessible to the liquid. Thus, sufficient liquid is provided to wet a substantial portion or substantially all of the filler's surface prior to mixing with the solid elastomer. During mixing, at least a portion of the liquid may also be removed by evaporation as the wet filler is dispersed in the solid elastomer, and the filler's surface may then become available for interaction with the solid elastomer. The wet filler has a liquid content of at least 15% by weight based on the total weight of the wet filler, for example at least 20%, at least 25%, at least 30%, at least 40%, at least 50% by weight based on the total weight of the wet filler, or 15% to 99%, 15% to 95%, 15% to 90%, 15% to 80%, 15% to 70%, 15% to 60%, 15% to 65%, 20% to 99%, 20% to 95%, 20% to 90%, 20% to 80%, 20% to 70%, 20% to 60%, %, 30% to 99%, 30% to 95%, 30% to 90%, 30% to 80%, 30% to 70%, 30% to 60%, 40% to 99%, 40% to 95%, 40% to 90%, 40% to 80%, 40% to 70%, 40% to 60%, 45% to 99%, 45% to 95%, 45% to 90%, 45% to 80%, 45% to 70%, 45% to 60%, 50% to 99%, 50% to 95%, 50% to 90%, 50% to 80%, 50% to 70%, or 50% to 60% by weight. The liquid content of the filler may be expressed as a weight percentage: 100 * [liquid mass] / [liquid mass + dry filler mass]. Alternatively, the amount of liquid may be determined based on the oil absorption number (OAN) of the filler, where OAN is determined based on ASTM D1765-10.The OAN is a measure of filler structure and can be used to determine the amount of liquid to wet the filler. For example, a wet filler such as wet carbon black, wet silica (e.g., precipitated silica), or wet silicon-treated carbon black can have a liquid content determined according to the following formula: k*OAN / (100+OAN)*100. In one embodiment, k is in the range of 0.3 to 1.1, or 0.5 to 1.05, or 0.6 to 1.1, or 0.7 to 1.1, or 0.8 to 1.1, or 0.9 to 1.1, or 0.6 to 1.0, or 0.7 to 1.0, or 0.8 to 1.05, or 0.9 to 1.0, or 0.95 to 1, or 0.95 to 1.1, or 1.0 to 1.1.
[0070] The liquid used to wet the filler can be or include an aqueous liquid, such as, but not limited to, water. The liquid can include at least one other component, such as, but not limited to, base(s), acid(s), salt(s), solvent(s), surfactant(s), coupling agent(s), and / or processing aid(s), and / or combinations thereof. More specific examples of this component are NaOH, KOH, acetic acid, formic acid, citric acid, phosphoric acid, sulfuric acid, or any combination thereof. For example, the base can be selected from NaOH, KOH, and mixtures thereof, or the acid can be selected from acetic acid, formic acid, citric acid, phosphoric acid, or sulfuric acid, and mixtures thereof. The liquid can be or include a solvent(s) that is immiscible with the elastomer used (e.g., an alcohol such as ethanol). Alternatively, the liquid can consist of about 80 wt% to 100 wt% water or 90 wt% to 99 wt% water, based on the total weight of the liquid.
[0071] Solid Elastomer With respect to solid elastomers used and mixed with wet fillers, the solid elastomers can be considered dry elastomers or substantially dry elastomers. The solid elastomers can have a liquid content (e.g., solvent or water content) of 5 wt% or less, e.g., 4 wt% or less, 3 wt% or less, 2 wt% or less, 1 wt% or less, or 0.1 wt% to 5 wt%, 0.5 wt% to 5 wt%, 1 wt% to 5 wt%, 0.5 wt% to 4 wt%, etc., based on the total weight of the solid elastomer. The solid elastomer (e.g., starting solid elastomer) can be entirely elastomer (e.g., a starting liquid such as water content of 5 wt% or less) or can be an elastomer that also includes one or more fillers and / or other ingredients. For example, the solid elastomer can be 50 wt% to 99.9 wt% elastomer with 0.1 wt% to 50 wt% filler pre-dispersed in the elastomer, such that the pre-dispersed filler is added to the wet filler. Such elastomers can be prepared by a dry blending process between a non-wetting filler and a solid elastomer. Alternatively, a composite made by blending a wet filler with a solid elastomer (e.g., according to the processes disclosed herein) can be used as the solid elastomer and further blended with a wet filler according to the processes disclosed herein. However, the solid elastomer is not a composite, mixture, or compound made by a liquid masterbatch process, nor is it any other pre-formulated composite of a filler dispersed in an elastomer, so long as the elastomer is in a liquid state, such as a latex, suspension, or solution.
[0072] The wet filler can be individually loaded into the mixer and finally mixed with the elastomer in the mixer. The solid elastomer can be one piece, multiple pieces, or bulk particulate material. Multiple pieces (e.g., strips, sheets, chunks) of elastomer or bulk particulate material can be achieved by cutting or grinding the solid elastomer using methods well known in the art. The size of these pieces can have dimensions of at least 1 μm, e.g., at least 10 μm, or at least 100 μm, up to 10 cm, up to 5 cm, or up to 1 cm.
[0073] Examples of solid elastomers include, but are not limited to, any solid form of a natural or synthetic elastomer.
[0074] After the composite material is formed and delivered, the method can include the further optional step of mixing the composite material with an additional elastomer to form a composite material containing a blend of elastomers. The "additional elastomer" can be the same or different from the solid elastomer used in the mixing step and can be any of the elastomers described herein, and their dry composites, such as natural rubber or synthetic elastomers (e.g., styrene butadiene rubber (SBR), polybutadiene rubber (BR) and polyisoprene rubber (IR), ethylene-propylene rubber (e.g., EPDM), isobutylene-based elastomers (e.g., butyl rubber), polychloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, and silicone elastomers). Blends of two or more elastomers (blends of a first and a second solid elastomer), including blends of a synthetic elastomer and natural rubber or blends with two or more synthetic or natural rubbers, may also be used. For example, a mixer can be charged with two or more charges of different elastomers to form a composite blend. Alternatively, the mixer can be charged with an elastomer blend. Alternatively, the process can include mixing the delivered composite material with an additional elastomer to form a blend. Alternatively, the process can include mixing the delivered composite material with an additional elastomer, where the additional elastomer is the same as the solid elastomer originally charged to the mixer, to form a composite with a diluted filler loading. Alternatively, the process can include blending a first delivered composite material with a second delivered composite material (the first and second delivered composite materials each being made from a wet filler and a solid elastomer), where the first and second delivered composite materials can have the same or different fillers (e.g., forming a filler blend) or the same or different elastomers (e.g., forming an elastomeric blend).
[0075] Loading the mixer In the methods disclosed herein, at least a solid elastomer and a wet filler are charged (e.g., fed, introduced) into a mixer. For example, charging of the solid elastomer and the wet filler can be the step in which the solid elastomer and the wet filler are introduced into the mixer. The charging of the solid elastomer and / or the filler can occur in one or more steps or additions. The charging can occur in any manner, including, but not limited to, conveying, metering, discharging, and / or feeding a batch, semi-continuous, or continuous flow of the solid elastomer and the wet filler into the mixer. The solid elastomer and the wet filler are not introduced into the mixer as a premix, where the premix was prepared by means other than combining the solid elastomer and the wet filler. The solid elastomer and the wet filler can be added together, but not as a mixture prepared by means other than combining the solid elastomer and the wet filler (e.g., the wet filler is not predispersed into the elastomer by means other than combining the solid elastomer and the wet filler in which the elastomer is the continuous phase). The mixture, premix, or precompound of solid elastomer and wet filler can be charged into a mixer and prepared, for example, in a mixer or container, by several known methods. The charging of the solid elastomer and the charging of the wet filler can occur all at once or sequentially, and can occur in any order. For example, (a) adding all of the solid elastomer first, (b) adding all of the wet filler first, (c) adding all of the solid elastomer together with a portion of the wet filler first, followed by one or more additions of the remaining portions of the wet filler, (d) adding some of the solid elastomer, then some of the wet filler, (e) adding at least some of the wet filler first, followed by at least some of the solid elastomer, or (f) adding some of the solid elastomer and some of the wet filler simultaneously or nearly simultaneously as separate charges to the mixer.
[0076] As an alternative to the charging process, prior to charging the wet filler into the mixer, the solid elastomer can be masticated until it reaches a predetermined temperature, such as about 90° C. to 100° C. or higher. This temperature can be 90° C. to 180° C., 100° C. to 180° C., 110° C. to 170° C., 120° C. to 160° C., or 130° C. to 160° C. The elastomer can be masticated using an internal mixer, such as a Banbury or Brabender mixer, extruder, roll mill, continuous compounder, or other rubber mixing equipment.
[0077] Alternatively, the charge can be made such that the dry filler is introduced into the mixer and moistened by the addition of liquid (e.g., water, either sequentially, simultaneously, or nearly simultaneously) to form a wet filler in the mixer, and then the solid elastomer is added to the mixer. The introduction of the moistened dry filler can be carried out with all or a portion of the filler intended to be used (e.g., additional portions of one or more moist fillers are further added to the mixer to obtain the intended total amount of starting wet filler).
[0078] Alternatively, the solid elastomer (all or a portion) or the wet filler (all or a portion) may be added to the mixer individually but within 20 minutes, or within 15 minutes, or within 10 minutes, or within 5 minutes of each other, or within 1 minute, 30 seconds, or within 15 seconds of each other.
[0079] mixture With respect to mixing, mixing can be carried out in one or more mixing steps. Mixing begins when at least the solid elastomer and wet filler are loaded into the mixer and energy is applied to the mixing system to drive one or more rotors of the mixer. One or more mixing steps can occur after the loading step is completed or can overlap with the loading step for any amount of time. For example, a portion of one or more solid elastomers and / or wet fillers can be loaded into the mixer before or after mixing begins. The mixer can then be loaded with one or more additional portions of solid elastomer and / or filler. With respect to batch mixing, the loading step is completed before the mixing step is completed.
[0080] By "one or more mixing steps," it is understood that the steps disclosed herein (e.g., with recited parameters such as tip speed, Tz, packing rate, specific energy, specific power, etc.) can be an initial mixing step, followed by additional mixing steps before delivery. Alternatively, the steps disclosed herein (e.g., with recited parameters such as tip speed, Tz, packing rate, specific energy, specific power, etc.) need not necessarily be performed as an initial mixing step. For example, the one or more mixing steps can include a first mixing step in which a solid elastomer and a wet filler are mixed under conditions in which a minimal amount of liquid is removed by evaporation. For example, the first mixing step can form a pre-blend. The mixture from this first mixing step can then be subjected to a second or additional mixing step (e.g., with recited parameters such as tip speed, Tz, packing rate, specific energy, specific power, etc.) performed by the disclosed process. As understood in the art, a mixing step is equivalent to a mixing stage.
[0081] As noted, during one or more mixing steps in any of the methods disclosed herein, at least a portion of the liquid present in the introduced mixture and / or wetting filler is at least partially removed by evaporation. Optionally, a majority (in wt%) of the liquid removed from the mixture occurs by evaporation. For example, at least 50 wt% of the liquid is removed by evaporation, based on the total weight of liquid removed during mixing. The total weight of liquid removed can be determined from the difference between the liquid content of the wetting filler and the sum of any liquid remaining in the composite material as it leaves the mixer and any liquid present in or drained from the mixer as it leaves the mixer. For example, when a composite material is delivered, additional liquid (e.g., a non-volatile liquid) may also be delivered, either with or within the composite material, or through an outlet provided within the mixer. The liquid removal by evaporation can represent at least 30 wt%, at least 40 wt%, at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, or 51 wt% to 100 wt%, 51 wt% to 95 wt%, 51 wt% to 90 wt%, 51 wt% to 80 wt%, 51 wt% to 70 wt%, 60 wt% to 100 wt%, 60 wt% to 95 wt%, 60 wt% to 90 wt%, or 60 wt% to 80 wt% of the total liquid contained in the wet filler charged to the mixer.
[0082] Optionally, one or more mixing steps or stages can further remove some of the liquid from the mixture by squeezing, compressing, and / or squeezing, or any combination thereof. Alternatively, some of the liquid can be drained from the mixer after or during the delivery of the composite material.
[0083] Regarding mixers that may be used in any of the methods disclosed herein, any suitable mixer capable of combining (e.g., mixing or compounding) the filler with the solid elastomer may be utilized. The mixer(s) may be a batch mixer or a continuous mixer. A combination of mixers and processes may be utilized in any of the methods disclosed herein, and these mixers may be used sequentially, in tandem, and / or integrated with other processing equipment. The mixer may be an internal or closed-type mixer or an open-type mixer, or an extruder or a continuous compounder or a kneading mixer, or a combination thereof. The mixer may be capable of kneading the filler into the solid elastomer and / or dispersing and / or distributing the filler in the elastomer. Any one or combination of commercially available mixers for producing rubber compounds may be used in the present method.
[0084] The mixer can be capable of batch, continuous, or semi-continuous processing. The mixer can have any chamber volume. Internal mixers generally include an enclosed mixing chamber. For batch mixers, the chamber volume can be at least 1 L, at least 2 L, at least 5 L, at least 10 L, at least 20 L, at least 50 L, at least 100 L, at least 250 L, at least 300 L, at least 600 L, or at least 1000 L, for example, 1 L to 1500 L, 10 L to 1200 L, 10 L to 1000 L, or 10 L to 750 L. , 10L to 500L, 10L to 300L, 10L to 100L, 20L to 1500L, 20L to 1200L, 20L to 1000L, 20L to 750L, 20L to 500L, 20L to 300L, 20L to 100L, 50L to 1500L, 50L to 1200L, 50L to 1000L, 50L to 750L, 50L to 500L, 50L to 300L, or 50L to 100L.
[0085] The top of a typical batch mixing chamber can be raised and lowered by a pneumatic or hydraulic piston, commonly referred to as a "floating weight" or "ram." The ram operates within a housing known as a "feed hopper," which has a loading door through which the materials to be mixed are introduced. The ram rises to feed the materials (e.g., at least the solid elastomer and wet filler) and descends to apply pressure to the mixture and confine it within the mixing chamber. Typically, the batch fill rate and ram pressure are selected to allow the ram to reach its lowest position to minimize the gap between the ram and the rotor, which can enable good filler dispersion. The vertical distance of the ram above its lowest position is known as the "ram deflection." The bottom of a typical batch mixer can be lowered on a pivot, known as a "drop door." This is used to deliver or "dump" the contents of the mixer.
[0086] A mixer may have one or more rotors (at least one rotor). For example, each rotor rotates inside its own cylindrical chamber, which can be connected to the chamber(s) of the other rotor(s). Typically, for a batch mixer, two rotors are utilized. The bodies of one or more rotors can be attached to a shaft and form one integrated component. The shaft is controlled by a mixing system to which energy (electrical energy) is applied. The rotor can be considered a device that imparts energy to the mixture and / or the components that form the mixture. The rotor can be designed with internal circuits or channels for steam, water, or other liquids for cooling and / or heating. When two rotors are present, they generally orbit in the same or opposite directions and at the same or different speeds (e.g., within 20 rpm of each other or 10 rpm of each other). The acute convergence of the rotors with the chamber wall and / or between the rotors imparts a shearing action to the mixture, and the resulting concentrated work generally creates a homogeneous mixture. At least one rotor or more rotors can be a screw-type rotor, an intermeshing rotor, a tangential rotor, a kneading rotor(s), a rotor used in an extruder, a roll mill that imparts significant total specific energy, or a creper mill. Generally, more than one rotor is utilized in a mixer; for example, a mixer can incorporate one rotor (e.g., a screw-type rotor), two, four, six, eight, or more rotors. Sets of rotors can be arranged in parallel and / or sequential orientation within a given mixer configuration.
[0087] Liquid that evaporates from the mixture can exit the mixer in one case through a gap between the ram and the body and / or through a port or outlet or vent designed to release the evaporated liquid (e.g., steam). For example, in a continuous mixer (such as a devolatilizing extruder), the evaporated liquid can be released through a vent stuffer or through a piston that periodically clears the material (e.g., evaporated liquid) through a vent or outlet or port.
[0088] One or more mixing steps can be a single mixing step, e.g., a single-stage or single-stage mixing step or process, where the mixing is carried out under one or more of the following conditions: at least one of the mixer temperatures is controlled by a temperature control means comprising one or more rotors operating at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, and / or by at least one temperature control means setting the temperature Tz to 65°C or higher, the fill rate is 68% or less, an average specific power of at least 2.5 kW / kg is applied throughout the mixing time and / or continuous mixing, and / or the mixing is carried out in the substantial absence of one or more rubber chemicals before the mixer reaches the specified temperature; each is further described herein. In certain cases, in a single-stage or single mixing step, the composite material can be delivered with a liquid content not exceeding 10% by weight. In other embodiments, two or more mixing steps or stages can be carried out, as long as the mixing step is carried out under one or more of the mentioned conditions.
[0089] Multi-stage mixing, optionally with a second or any number of subsequent mixing stages, can provide a composite that improves corresponding compound properties compared to a compound prepared from a composite mixed with only one stage of mixing. In other words, a composite formed from one-stage mixing can be compared to a composite formed from an additional-stage mixing process, e.g., subjected to a second stage. When such multi-stage mixing is utilized, one or more corresponding compound properties (e.g., tan δ and / or tensile stress ratio) can be improved. This improvement can be a 5%, 10%, or 15% or more improvement in one or more properties compared to a compound prepared from a composite subjected to one-stage mixing. This improvement can be obtained regardless of the type of filler used and regardless of the type of elastomer used. For example, the second stage can be carried out by a second mixer operated under at least one of the following conditions: (i) a ram pressure of 5 psi or less; (ii) a ram raised to at least 75% of its maximum level; (iii) a ram operated in a floating mode; (iv) a ram positioned so as not to substantially contact the mixture; (v) the mixer is ramless; and (vi) a fill factor of the mixture is between 25% and 70%.
[0090] This process can utilize one or more mixing steps and / or one or more mixers. For example, mixing at least a solid elastomer and a wet filler to form a mixture, removing at least a portion of the liquid from the mixture by evaporation, and discharging a composite material having a liquid content not exceeding 10% by weight from the mixer can occur as one mixing step in one mixer. In the context of two or more mixing steps, the discharged product is a composite material, but can also be referred to as a mixture, since it is subjected to further processing or mixing to form the final composite material. In another example, a first mixing step includes mixing at least a solid elastomer and a wet filler to form a mixture, and a second mixing step includes discharging a composite material (or mixture) having a liquid content not exceeding 10% by weight from the mixer. In this option, the first and second mixing steps can be performed in the same or different mixers. In yet another example, mixing at least a solid elastomer and a wet filler to form a mixture, removing at least a portion of the liquid from the mixture by evaporation, and discharging the composite (or mixture) having a liquid content not exceeding 10% by weight from a mixer can occur as one mixing step, and a second mixing step (in the same or a second mixer) can be performed to further dry the composite (or mixture). In other words, the process can include using two or more mixers, such that the mixture is mixed in a first mixer in a first mixing step, then removed, if desired, and charged to a second mixer in a second mixing step, and so on. When two or more mixers are utilized, each mixer can be the same or different from the other mixers used in the method. For example, the composite (or mixture) can be discharged from a first mixer and then conveyed to a second mixer. In another example, the composite (or mixture) can be discharged from a mixer and then charged back into the same mixer (e.g., after cooling). These processes, known as multi-stage mixing, can be repeated as many times as necessary. Each stage can be mixed with the same or one or more different operating parameters.
[0091] During a typical dry mixing process with filler (non-wetting) and solid elastomer, the temperature of the mixture will increase, at least in part, due to, for example, the viscous flow of the elastomer during mastication of the elastomer and / or the mixing as the filler is kneaded into the elastomer. This increase can be quite rapid, and the mixture is typically delivered before substantial thermal degradation of the rubber occurs, regardless of whether adequate filler dispersion is achieved.
[0092] It has been discovered that the presence and subsequent evaporation of liquid can improve the dispersion of the filler in the elastomer by incorporating the wet filler during the mixing process. To obtain a stable final composite, the amount of liquid is reduced (e.g., to an amount of 10% or less based on the total composite weight). Without wishing to be bound by any theory, the presence of liquid can cool and / or lubricate the mixture, which can reduce the overall rate of temperature increase, allowing for increased mixing or residence time and improved filler dispersion without substantial degradation of the elastomer. This, in turn, can result in improved composite and vulcanizate properties.
[0093] Temperature control In certain embodiments, in at least one mixing step, the method comprises performing mixing at a mixer temperature controlled by at least one temperature control means. Alternatively, as mentioned above, the method can comprise performing mixing at a controlled mixer temperature, such as by using a temperature controller. Controlling the mixer temperature refers to controlling the temperature of at least one surface of the mixer. Optionally, the mixer temperature can be controlled during both the loading and at least one mixing step. The temperature control means can be a temperature-controlling device on and / or within the mixer or otherwise associated with (e.g., connected to) the mixer that heats or cools at least one surface, and / or one or more components of the mixer. While not wishing to be bound by any theory, controlling the mixer temperature, e.g., the mixer surface temperature, through a temperature control means can affect mixing characteristics such as the slippage and grip of the mixture on the mixer surface, which can affect the shear and viscous flow of the mixture within the mixer, and in turn, can affect heat generation by the mixture.
[0094] Slippage can be a problem when liquids are present in the mix. Without wishing to be bound by any theory, the risk of excessive slippage (lubrication) is more likely when the surface temperature of the mixer surface is very low. Such excessive slippage can lead to low viscous flow and subsequent low heat release, which in turn reduces the rate of liquid removal by evaporation, causing insufficient or inadequate mixing, inefficient or inadequate drying, and / or long mixing times. In this case, slow filler incorporation and / or poor filler dispersion in the elastomer may be present. In typical mixes with dry fillers, slippage is not a significant issue; however, viscous flow of the mix can be more pronounced and result in faster heat release, which can degrade the elastomer. Such rapid heat release results in a rapid temperature rise in the mix, which requires short residence and mixing times to avoid rubber degradation. Inadequate mixing and inadequate filler dispersion may result.
[0095] Without wishing to be bound by any theory, without temperature control of at least one surface of the mixer, there is less opportunity to control slippage and the resulting temperature characteristics, e.g., temperature profile, when mixing the wetting filler and solid elastomer (e.g., mixing in the absence of at least one temperature control means). When operating a sequential mixing process or batch in the initial stage of mixing, the mixer surface temperature may have a wide range of surface temperatures, e.g., from room temperature to high temperatures, e.g., 180°C or higher. Loading the solid elastomer and wetting filler into the mixer at room temperature may cause inefficient mixing because excessive slippage is more likely to occur, and heat generation of the mixture may be delayed or even absent. As a result, the mixing may be inefficient, or the mixture may be delivered with a high liquid content and / or unincorporated filler at the mixture surface. Loading the solid elastomer and wetting filler into the mixer at an elevated temperature in the absence of a temperature control means may cause the liquid to evaporate very quickly, and the benefits of using a wetting filler may not be realized. Without temperature control measures, mixing characteristics and quality can be difficult to control and can vary during the mixing process. At temperatures above the boiling point of the liquid, flashing and loss of liquid can occur. If the loss of liquid is in the form of vapor, the vapor can carry the filler, leading to a loss of filler yield. In some situations, high surface temperatures of mixer parts can create a safety hazard.
[0096] Without wishing to be bound by any theory, if the mixer surface temperature is controlled (such as by a temperature control means), the slippage between the mixture and the mixer surface can be controlled, which in turn can affect the viscous flow of the mixture and the resulting heat generation. Additionally or alternatively, a controlled mixer surface temperature can allow the mixture to better grip the mixer surface. Controlling the mixer surface temperature allows for control of the viscous flow, heat generation, and mixing time to reach the target discharge temperature.
[0097] While not wishing to be bound by any theory, controlling the mixer surface temperature with at least one temperature control means may allow for control of the surface or bulk temperature of the mixture, instead of or in addition to any other mechanism. At the start of mixing, the solid elastomer in the mixture is typically at room temperature. In situations where the mixer surface temperature is higher than the temperature of the mixture, the mixer surface may transfer heat to at least a portion of the mixture, resulting in an increase in the mixture surface temperature. While not wishing to be bound by any theory, instead of or in addition to any other mechanism, the increase in the mixture surface temperature may cause the mixture to grip the mixer surface, reducing slippage and allowing the mixer to input more energy into the mixture and generate sufficient heat through viscous flow, ultimately removing the liquid. Once the mixture temperature exceeds the mixer surface temperature, the mixer surface may allow for heat transfer from the mixture. In other words, the mixer cools at least a portion of the mixture, for example, cooling the surface or bulk. This cooling slows the rapid temperature increase and allows for longer mixing and residence times at temperatures that do not decompose the rubber.
[0098] This control of overall mixer surface temperature by any mechanism(s) can provide the opportunity for longer mixing or residence times, which may result in improved filler dispersion and / or improved rubber-filler interaction and / or consistent mixing and / or efficient mixing compared to mixing processes without temperature control of at least one mixer surface.
[0099] The temperature control means can be, but is not limited to, the flow or circulation of a heat transfer fluid through channels in one or more components of the mixer. For example, the heat transfer fluid can be water or heat transfer oil. For example, the heat transfer fluid can flow through the rotor, mixing chamber walls, ram, and drop door. In other embodiments, the heat transfer fluid can flow in a jacket (e.g., a jacket having a liquid flow means) or coils around one or more components of the mixer. Alternatively, the temperature control means (e.g., providing heat) can be an electrical element fitted within the mixer. The system providing the temperature control means can further include means for measuring either the temperature of the heat transfer fluid or the temperature of one or more components of the mixer. This temperature measurement is sent to a system used to control the heating and cooling of the heat transfer fluid. For example, a desired temperature of at least one surface of the mixer can be controlled by setting the temperature of a heat transfer fluid disposed in a channel adjacent to one or more components of the mixer, such as a wall, door, rotor, etc.
[0100] The temperature of the at least one temperature control means can be set and maintained, for example, by one or more temperature control units ("TCUs"). This set temperature or TCU temperature is also referred to herein as "Tz." In the case of temperature control means incorporating a heat transfer fluid, Tz is a measure of the temperature of the fluid itself. Heating or cooling provided by the temperature control means is transferred to at least one surface of the mixer or one or more components of the mixer according to Tz; heat is transferred to or from the at least one surface and then to or from the material within the mixer, affecting the bulk temperature of the mixture or a portion thereof, e.g., the local temperature of the mixture. If the flow of the heat transfer fluid is sufficient, the transferred heating or cooling should result in a temperature of the mixer component reasonably close to Tz. Optionally, the velocity of the heat transfer fluid within the channel is at least 1 m / s.
[0101] The mixer can have thermocouples located in different parts of the mixer to provide a more accurate measurement of the temperature of the mixer part(s) or the mixture. Typical thermocouples installed in commercially available mixers are effective for measuring the temperature of the mixture. The temperature of at least one surface may deviate from Tz but still be a close approximation of Tz, e.g., the average surface temperature of at least one surface deviates from Tz by ±5%, ±10%, ±20%.
[0102] In alternative or additional embodiments, the temperature control means or device comprises a communication line between the temperature monitor / setting device and a heating / cooling device, such as a heater, chiller or heater-chiller combination, capable of heating a liquid or cooling a liquid and maintaining a set temperature.
[0103] The mixer can have two or more temperature control means or devices, e.g., two, three, or more, each providing a region of temperature control within the mixer or a section of the mixer. When two or more temperature control means or devices are utilized, each temperature-control device or means can utilize the same or different Tz temperatures. By way of further example, when two or more temperature control devices or means are utilized, the temperature difference between each set point temperature can be 0°C or about 0°C, or can be a temperature difference between 1°C and 100°C or 1°C and 50°C, e.g., 5°C to 50°C (e.g., Tz1, Tz2, Tz3 are ±0°C or ±5°C or ±10°C or ±20°C or ±30°C, ±40°C, etc.). One or more temperature control means or device(s) can be located at any position or component of the mixer(s). For example, the wall(s) or all walls of the mixer or mixer chamber, and / or the ram, and / or the drop door(s), and / or one or more rotors, and / or the extrusion head can be temperature controlled to form one or more temperature-controlled zones. Optionally, at least one temperature control means heats at least the walls of the mixer.
[0104] As mentioned, the mixer temperature or mixer temperatures may be controlled by at least one temperature control means. Optionally, the temperature control means may generally be set to a temperature Tz in the range of 5° C. to 150° C., or in the range of 5° C. to 155° C. For example, if the mixer is equipped with a liquid jacket, the heat transfer fluid passing through the liquid jacket before heat is transferred to the material in the mixer is at or about Tz, e.g., within 5° C., or within 2° C., or within 1° C. of Tz. Optionally, the temperature control means may be set to a temperature between 30°C and 150°C, 40°C and 150°C, 50°C and 150°C, or 60°C and 150°C, for example, 30°C and 155°C, 30°C and 125°C, 40°C and 125°C, 50°C and 125°C, 60°C and 125°C, 30°C and 110°C, 40°C and 110°C, 50°C and 110°C, 60°C and 110°C, 30°C and 100°C, 40°C and 100°C, 50°C and 100°C, 60°C and 125°C, The temperature Tz can be set to a range of 00°C, 30°C to 95°C, 40°C to 95°C, 50°C to 95°C, 50°C to 95°C, 30°C to 90°C, 40°C to 90°C, 50°C to 90°C, 65°C to 95°C, 60°C to 90°C, 70°C to 110°C, 70°C to 100°C, 70°C to 95°C, 70°C to 90°C, 75°C to 110°C, 75°C to 100°C, 75°C to 95°C, or 75°C to 90°C. Other ranges are possible with equipment available in the art. The temperature control means can be set to any of these temperatures Tz during the loading process.
[0105] In other embodiments, the temperature control means may be set to a temperature higher than that typically used for dry mixing, for example, a temperature of 65°C (Tz) or higher. This Tz is provided by the temperature control means. For example, if the mixer is equipped with a liquid jacket, the heat transfer fluid passing through the liquid jacket will be at or near this temperature, for example within 5°C, or within 2°C, or within 1°C, before heat is transferred to the materials in the mixer. (Tz) may be set to a temperature in the range of 65°C to 140°C, or 65°C to 130°C, or 65°C to 120°C, or 65°C to 110°C, or 65°C to 100°C, or 65°C to 95°C, or 70°C to 130°C, or 70°C to 120°C, or 70°C to 110°C, or 70°C to 100°C, or 80°C to 140°C, or 80°C to 130°C, or 80°C to 120°C, or 80°C to 110°C, or 80°C to 100°C, or other temperatures within or above or below these ranges.
[0106] The optimum T value can be selected based on the type of filler. For example, for a filler containing carbon black and silicon-treated carbon black (e.g., at least 50 wt%, at least 75 wt%, at least 90 wt%, or all or substantially all of the filler is carbon black or silicon-treated carbon black), the optimum T value can be selected based on the type of filler. z can have a value described herein, for example, 65° C. or greater, or 65° C. to 100° C. When the filler is silica, the Tz value can be in the range of 40° C. to 110° C., 40° C. to 100° C., e.g., 40° C. to 90° C., 40° C. to 80° C., 40° C. to 75° C., 50° C. to 110° C., 50° C. to 100° C., 50° C. to 90° C., 50° C. to 80° C., 50° C. to 75° C., 60° C. to 110° C., or 60° C. to 100° C.
[0107] Alternatively, for example, if the mixer conditions result in sufficient mechanical energy input, the upper limit of Tz should not substantially exceed the boiling point of the liquid in the wet filler. If very rapid evaporation occurs, this can result in liquid removal before sufficient mixing occurs, and in addition, some of the filler can escape through the mixer vent along with the vapor (e.g., steam), resulting in insufficient filler loading in the delivered composite and high filler yield loss. Furthermore, some of the lost filler can coat the surface of the composite. Alternatively, the upper limit of Tz is selected to be approximately the boiling point of the liquid, for example, +10°C, or +5°C, or +1°C, or -1°C, or -5°C, or -10°C above the boiling point of the liquid.
[0108] An option to prevent the temperature of the mixture from exceeding the boiling point of the liquid during charging or early mixing is the stage of addition of the wet filler to the mixer. For example, a fraction or portion of the filler is added at the beginning, and the remainder is added later in the mixing cycle (in one or more addition steps). Another option is to select mixer conditions that allow all of the wet filler to be added at or near the beginning of the cycle. Another option is to add additional liquid (e.g., water) to the mixer (e.g., mixer chamber) to cool the mixture.
[0109] Total specific energy Compared to dry mixing, under similar filler, elastomer, and mixer types, this process can allow for higher energy input. Controlled removal of liquid from the wet filler allows for longer mixing times, resulting in improved filler dispersion. This energy input can be represented by the resulting total specific energy imparted to the composite during the mixing process. For example, mixing occurs when at least the wet filler and solid elastomer are loaded into the mixer and energy is applied to at least one rotor. For example, in a batch mixer, the total specific energy takes into account the energy applied to the rotor(s) during loading and delivery of the solid elastomer and / or wet filler per kg of composite on a dry weight basis. For continuous mixers, the total specific energy is the power input per kg of product on a dry weight basis under steady-state conditions. For processes with multi-stage mixing, the total specific energy is the sum of the specific energies from each mixing step. The determination of total specific energy preferably does not include the amount of energy used to shape or form the delivered composite material (e.g., excluding the energy of milling the composite material). The resulting "total specific energy" is the energy E applied to the mixing system driving one or more rotors per mass of composite material on a dry weight basis, as defined herein. R (e.g., electrical energy). This total specific energy is E 全 As described herein, the process provides an overall specific energy under selected operating conditions that is balanced by relatively long mixing times with evaporation or removal of water in a reasonable time.
[0110] Alternatively, the process includes performing mixing in at least one mixing step such that the resulting total specific energy is at least 1,100 kJ / kg composite material, at least 1,200 kJ / kg, at least 1,300 kJ / kg, or at least 1,400 kJ / kg or at least 1,500 kJ / kg, e.g., at least 1,600 kJ / kg, at least 1,700 kJ / kg, at least 1,800 kJ / kg, at least 1,900 kJ / kg, at least 2,000 kJ / kg, at least 2,500 kJ / kg, or at least 3,000 kJ / kg. As a system-specific alternative, the total specific energy can range from 1,000 kJ / kg to 3,000 kJ / kg, e.g., from 1,000 kJ to 2,500 kJ / kg, from 1,100 kJ to 2,500 kJ / kg, etc. Alternatively, the total specific energy may be from about 1,400 kJ / kg composite or from about 1,500 kJ / kg composite (or per kg of mixture present in the mixer) to about 10,000 kJ / kg composite (or per kg of mixture present in the mixer), for example, from 2,000 kJ / kg to about 5,000 kJ, or from 1,500 kJ / kg to 8,000 kJ / kg, from 1,500 kJ / kg to 7,000 kJ / kg, or from 1,500 kJ / kg to 6,000 kJ / kg. , 1,500kJ / kg to 5,000kJ / kg, 1,500kJ / kg to 3,000kJ / kg, 1,600kJ / kg to 8,000kJ / kg, 1,600kJ / kg to 7,000kJ / kg, 1,600kJ / kg to 6,000kJ / kg, 1,600kJ / kg to 5,000kJ / kg, 1,600kJ / kg to 4,000kJ / kg, 1,600kJ / kg to 3,000kJ / kg, or any other value in these ranges.
[0111] Specific energy after adding filler In addition to the total specific energy, E 100%filler and E 75%filler An understanding of the E and how they compare to the total specific energy may be useful in one or more aspects disclosed herein. 100%filleris the amount of specific energy (kJ per kg of dry composite) utilized when 100% (by weight) of all fillers are added or present at the time of mixing (in the mixer) and the composite is delivered and has a liquid content of no more than 10% by weight, e.g., no more than 5% by weight, no more than 4% by weight, no more than 3% by weight, or no more than 2% by weight. Further, E 75%filler is the amount of specific energy (kJ / kg of dry composite) utilized once 75% (wt) of all fillers are added or present during mixing and the composite has a liquid content of no more than 10 wt%, e.g., no more than 5 wt%, no more than 4 wt%, no more than 3 wt%, or no more than 2 wt%. 100%filler and E 75%filler The manner in which is measured is no different from the total specific energy, except at the point where the amount of energy input for mixing is calculated.
[0112] E 100%filler and E 75%filler can be measured from the point at which the ram is lowered after the filler is charged into the mixer to start or restart mixing (the latter being the case if more than one filler addition step is performed). Thus, if the filler is not added all at once, E 100%filler is E 75%filler and unless all fillers are added before any mixing, the total specific energy is E 100%filler and E 75%filler From various experiments, the minimum E 100%filler and minimum E 75%filler A preference for the minimum total specific energy may be understood, which may not necessarily be the same as the minimum total specific energy. Sometimes, a better understanding of filler-elastomer interactions may be combined with one or more of the methods disclosed herein. 100%filler and / or E 75%filler This can be achieved through the study and understanding of
[0113] The properties of a rubber compound are driven, in part, by the recipe (elastomer selection, filler type, etc.) and how these components are brought together (e.g., through mixing). For a given material selection and filler loading, properties can be influenced by (a) the degree and distribution of filler dispersion within the elastomer matrix, (b) adhesion (interaction) between the filler and polymer, (c) polymer properties, and other factors. The problem is that dispersion can be increased with mixing without negatively affecting interactions and / or polymer degradation. Degradation from high energy input can be observed as polymer chain breakage and oxidation for elastomers such as natural rubber, or gel formation for synthetic rubbers. While not wishing to be bound by any theory, with wet fillers, a greater specific energy is applied to the mixture and available for dispersion compared to mixing with dry fillers. This energy can then be released, in part, through evaporation of the liquid. This is in contrast to dry mixing, where the majority of the energy input results in an increase in temperature and subsequent possible degradation of the elastomer.
[0114] With respect to the filler, for example, when the filler comprises or is a carbon black or carbon-based filler (such as a two-phase carbon black-silica or carbon black-silicon agglomerate, e.g., silicon-treated carbon black), or when the filler is predominantly (by weight of the total filler) a carbon black or carbon-based filler, there can be a preferred minimum amount of specific energy (E) to disperse the wet filler after a substantial amount of filler (at least 75 wt. % of the total wet filler in the composite) has been charged to the mixer in order to obtain the desired improvement in the properties of the resulting rubber compound.
[0115] For example, at least one option is 1100kJ / kg(E 100%filler ) or 1300kJ / kg(E 75%filler) have been found to be useful in achieving one or more desirable reinforcing or other elastomeric properties (e.g., M300 / M100 and / or hysteresis (tan δ)) in the resulting vulcanizate. Thus, for systems with primarily wet carbon-based fillers, such as carbon black or silicon-treated carbon black, that fall below these energy values, the composite may yield a vulcanizate with properties that are less than optimal.
[0116] Optionally, the process may further comprise, in at least one mixing step, 100%filler is at least 1,100 kJ / kg of composite material, e.g., at least 1,150 kJ / kg, at least 1,200 kJ / kg, at least 1,300 kJ / kg, at least 1,400 kJ / kg, at least 1,500 kJ / kg, at least 2,000 kJ / kg, or at least 3,000 kJ / kg. 100%filler is from about 1,100 kJ / kg composite material (or per kg of mixture present in the mixer) to about 10,000 kJ / kg composite material (or per kg of mixture present in the mixer), for example, from 1,100 kJ / kg to about 5,000 kJ, or from 1,200 kJ / kg to 8,000 kJ / kg, from 1,300 kJ / kg to 7,000 kJ / kg, from 1,400 kJ / kg to 6,000 kJ / kg, or from 1,500 kJ / kg to 1,600 kJ / kg. kJ / kg to 5,000 kJ / kg, 1,500 kJ / kg to 3,000 kJ / kg, 1,600 kJ / kg to 8,000 kJ / kg, 1,600 kJ / kg to 7,000 kJ / kg, 1,600 kJ / kg to 6,000 kJ / kg, 1,600 kJ / kg to 5,000 kJ / kg, 1,600 kJ / kg to 3,000 kJ / kg, or any other value within these ranges.
[0117] Optionally, the process may further comprise, in at least one mixing step, 75%filleris at least 1,300 kJ / kg of composite material, e.g., at least 1,350 kJ / kg, at least 1,400 kJ / kg, at least 1,500 kJ / kg, at least 1,600 kJ / kg, at least 1,700 kJ / kg, at least 1,800 kJ / kg, or at least 2,000 kJ / kg or at least 3,000 kJ / kg. 75%filler is from about 1,300 kJ / kg composite material (or per kg of mixture present in the mixer) to about 10,000 kJ / kg composite material (or per kg of mixture present in the mixer), for example, 1,350 kJ / kg to about 5,000 kJ, or 1,400 kJ / kg to 8,000 kJ / kg, 1,500 kJ / kg to 7,000 kJ / kg, 1,600 kJ / kg to 6,000 kJ / kg, 1,700 kJ / kg to 8,000 kJ / kg, 1,800 kJ / kg to 10,000 kJ / kg, or 1,900 kJ / kg to 12,000 kJ / kg. kJ / kg to 5,000 kJ / kg, 1,800 kJ / kg to 3,000 kJ / kg, 1,900 kJ / kg to 8,000 kJ / kg, 1,600 kJ / kg to 7,000 kJ / kg, 1,600 kJ / kg to 6,000 kJ / kg, 1,600 kJ / kg to 5,000 kJ / kg, 1,600 kJ / kg to 3,000 kJ / kg, or any other value within these ranges.
[0118] Specific Power Optionally, the method includes applying an average specific power (specific energy / mixing time, kW / kg) during one or more mixing steps. Average specific power can be reported for a single mixing step, such as first stage mixing, where average specific power for the mixing stage = specific energy / mixing time. The mixing time can be the ram stop time. For continuous mixing, average specific power can be calculated by the average specific energy divided by the mixer residence time. Alternatively, for continuous mixing, average specific power (kW) is calculated over a defined period divided by the mass (kg) of material inside the mixer at a particular time.
[0119] Optionally, the average specific power applied is at least 2.5 kW / kg over the mixing time, e.g., at least 3 kW / kg, at least 3.5 kW / kg, at least 4 kW / kg, at least 4.5 kW / kg, 2.5 kW / kg to 10 kW / kg, 2.5 kW / kg to 9 kW / kg, 2.5 kW / kg to 8 kW / kg, or 2.5 kW / kg to 10 kW / kg over the ram stop time. Optionally, one or more parameters can be selected to achieve the desired specific power, including, but not limited to, the liquid content in the filler, Tz, fill rate, and / or tip speed.
[0120] If a sufficiently high average specific power is utilized when mixing with the wet filler, the mixing time, e.g., ram stop time, can be reduced to an amount that is suitable for both efficiency and product properties. Thus, optionally, the method includes applying an average specific power of at least 2.5 kW / kg (or other ranges disclosed herein) for a ram stop time of 10 minutes or less, e.g., 8 minutes or less, or 6 minutes or less, in at least one mixing step.
[0121] The added energy, for example provided by one or more rotors in a mixer, can be constant or relatively constant. Alternatively, the instantaneous specific energy / unit time (kJ / (min·kg) (specific power) can be within 10% of the average specific energy / unit time (average specific power) during the mixing process.
[0122] tip speed Optionally, the process includes performing mixing such that, in at least one mixing step, one or more rotors are operated at a tip speed of at least 0.5 m / s for at least 50% of the mixing time, or at a tip speed of at least 0.6 m / s for at least 50% of the mixing time. The energy input into the mixing system is at least in part a function of the speed and rotor type of at least one rotor. The tip speed takes into account the rotor diameter and rotor speed and can be calculated according to the following formula: Tip speed, m / s = π × (rotor diameter, m) × (rotational speed, rpm) / 60 The tip speed can vary over the course of mixing, so that alternatively, a tip speed of at least 0.5 m / s or at least 0.6 m / s is achieved for at least 50% of the mixing time, such as at least 60%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90%, at least 95%, or substantially all of the mixing time. The tip speed can be at least 0.6 m / s, at least 0.7 m / s, at least 0.8 m / s, at least 0.9 m / s, at least 1.0 m / s, at least 1.1 m / s, at least 1.2 m / s, at least 1.5 m / s, or at least 2 m / s for at least 50% of the mixing time, or for other portions of the mixing as listed above. The tip speed can be selected to minimize the mixing time, or can be from 0.6 m / s to 10 m / s, 0.6 m / s to 8 m / s, 0.6 to 6 m / s, 0.6 m / s to 4 m / s, 0.6 m / s to 3 m / s, 0.6 m / s to 2 m / s, 0.7 m / s to 4 m / s, 0.7 m / s to 3 m / s, 0.7 m / s to 2 m / s, 0.7 m / s to 10 m / s, 0.7 m / s to 8 m / s, 0.7 to 6 m / s, 1 m / s to 10 m / s, 1 m / s to 8 m / s, 1 m / s to 6 m / s, 1 m / s to 4 m / s, 1 m / s to 3 m / s, or 1 m / s to 2 m / s (e.g., for at least 50% of the mixing time or other mixing times described herein). Alternatively or additionally, the tip speed can be selected to maximize throughput. Time / throughput considerations may take into account that as mixing time decreases, the liquid level in the delivered composite may increase. In certain circumstances, it may be beneficial to perform mixing at a high tip speed for a higher throughput commensurate with the desired liquid content of the delivered composite (e.g., an excessively high tip speed results in a shorter residence time or mixing time, which does not result in sufficient filler dispersion or sufficient removal of liquid from the composite).
[0123] Delivery, mixing time, and discharge or mixer temperature In any of the methods disclosed herein, a discharge step from the mixer occurs and produces a composite containing the filler dispersed in the elastomer at a loading of at least 1 phr with no more than a 10% filler yield loss, wherein the composite has a liquid content of no more than 10% by weight. During the mixing cycle, the mixture experiences an increase in temperature after much of the liquid is released from the composite and the incorporated filler. It is desirable to avoid an excessive temperature increase that would degrade the elastomer. Discharge (e.g., "draining" during batch mixing) can occur based on time or temperature or specific energy or power parameters selected to minimize such degradation.
[0124] In one embodiment, the mixing time can be determined from the period when loading is complete to delivery. For batch internal mixers, the mixing time can be determined from the ram stop time, e.g., the time when the ram is operated to its lowest position, e.g., the time when the ram is fully closed or seated. In other embodiments, the lowest position of the ram can result in a specific amount of ram deflection (as disclosed herein), e.g., the maximum ram deflection from the lowest position is a distance not exceeding 30% of the rotor diameter. The mixing time does not include the time when additional components are loaded, such as loading one or more additional portions of elastomer and / or filler. Alternatively, for continuous mixers, the nominal mixing time (or residence time) can be calculated from the mixer chamber volume and the volumetric production rate.
[0125] Alternatively, delivery occurs based on a specified mixing time. The mixing time between the start of mixing and delivery can be about 1 minute or more, e.g., about 1 to 40 minutes, about 1 to 30 minutes, about 1 to 20 minutes, or 1 to 15 minutes, or 5 to 30 minutes, or 5 to 20 minutes, or 5 to 15 minutes, or 1 to 12 minutes, or 1 to 10 minutes, or 3 to 30 minutes, or other time periods. Alternatively, for batch internal mixers, the ram stop time can be used as a parameter to monitor the batch mixing time, e.g., the time the mixer is operated with the ram at its lowest position, e.g., the fully retracted position or ram deflection as described herein. For example, the ram stop time can range from 3 to 30 minutes, 3 to 20 minutes, 3 to 10 minutes, 5 to 30 minutes, 5 to 20 minutes, or 5 to 10 minutes.
[0126] Alternatively, delivery can occur based on the discharge or delivery temperature (mixer temperature). For example, the mixer can have a discharge temperature in the range of 120°C to 180°C, 120°C to 190°C, 130°C to 180°C, e.g., 140°C to 180°C, 150°C to 180°C, 130°C to 170°C, 140°C to 170°C, 150°C to 170°C, or other temperatures within or outside these ranges.
[0127] Composite liquid content The method further includes discharging the formed composite material from the mixer. The discharged composite material may have a liquid content not exceeding 10 wt. % based on the total weight of the composite material, as outlined in the formula: % Liquid Content of Composite = 100*[Liquid Mass] / [Liquid Mass + Dry Composite Mass].
[0128] In any of the methods disclosed herein, the delivered composite material may have a liquid content of no more than 10 wt% based on the total weight of the composite material, for example, no more than 9 wt%, no more than 8 wt%, no more than 7 wt%, no more than 6 wt%, no more than 5 wt%, no more than 2 wt%, or no more than 1 wt% based on the total weight of the composite material. This amount can range from about 0.1 wt% to 10 wt%, or from about 0.5 wt% to 9 wt%, or from about 0.5 wt% to about 7 wt%, based on the total weight of the composite material delivered from the mixer at the end of the process. In any of the methods disclosed herein, the liquid content (e.g., "moisture content") can be the measured weight percent of liquid present in the composite material based on the total weight of the composite material.
[0129] While in any of the methods disclosed herein the delivered composite material can optionally have a liquid content of 10% by weight or less, there may be liquid (e.g., water) present in the mixer that is not retained in the delivered composite material. This excess liquid is not part of the composite material, and is not part of any calculated liquid content of the composite material.
[0130] In any of the methods disclosed herein, the total liquid content (or total water content or moisture percentage) of the material charged to the mixer is higher than the liquid content of the composite material delivered at the end of the process. For example, the liquid content of the delivered composite material can be 10% to 99.9% (wt% to wt%), 10% to 95%, or 10% to 50% lower than the liquid content of the material charged to the mixer.
[0131] Filler Loading In any of the methods disclosed herein, in the discharge step as part of the method, the elastomer as it leaves the mixer has a filler loading (parts per thousand rubber, or phr) of at least 1 phr, at least 10 phr, at least 15 phr, at least 20 phr, at least 30 phr, at least 40 phr, and a filler yield loss of no more than 10% on a dry weight basis. For example, the filler loading can be in the range of 20 phr to 250 phr, 20 phr to 200 phr, 20 phr to 180 phr, 20 phr to 150 phr, 20 phr to 100 phr, 20 phr to 90 phr, 20 phr to 80 phr, 30 phr to 200 phr, 30 phr to 180 phr, 30 phr to 150 phr, 30 phr to 100 phr, 30 phr to 80 phr, 30 phr to 70 phr, 40 phr to 200 phr, 40 phr to 180 phr, 40 phr to 150 phr, 40 phr to 100 phr, 40 phr to 80 phr, 35 phr to 65 phr, or 30 phr to 55 phr. With these loadings, the filler yield loss does not exceed 10% on a dry weight basis. Alternatively, other filler loadings and filler yield loss values may apply and are disclosed herein. Fillers include carbon black, silica, silicon-treated carbon black, and other fillers disclosed herein, and blends thereof.
[0132] In certain embodiments, at least 50% of the filler (e.g., at least 75% or at least 90% of the filler) is selected from carbon black and its coated and treated materials. In certain embodiments, at least 50% of the filler (e.g., at least 75% or at least 90% of the filler) is silica. In certain embodiments, at least 50% of the filler (e.g., at least 75% or at least 90% of the filler) is silicon-treated carbon black.
[0133] For example, carbon black may be dispersed in an elastomer at a loading ranging from 30 phr to 200 phr, or from 30 phr to 70 phr, or from 40 phr to 65 phr, or from 40 phr to 60 phr. As a more specific example, carbon black may be dispersed in natural rubber with an elastomer, either natural rubber alone or with one or more other elastomers, and with a filler, either carbon black alone or with one or more other fillers (e.g., silica or silicon-treated carbon black), at a loading ranging from 30 phr to 70 phr, or from 40 phr to 65 phr, or from 40 phr to 60 phr.
[0134] The amount of silica present in the formed elastomer composite can be 20 phr to 250 phr, 20 phr to 200 phr, 20 phr to 150 phr, 20 phr to 100 phr, 30 phr to 150 phr, 30 phr to 100 phr, 25 phr to 100 phr, 25 phr to 80 phr, 35 phr to 115 phr, 35 phr to 100 phr, 40 phr to 110 phr, 40 phr to 100 phr, 40 phr to 90 phr, 40 phr to 80 phr, etc. Filler formulations containing silica can include 10 wt% carbon black and / or silicon-treated carbon black.
[0135] The amount of silicon-treated carbon black present in the formed elastomer composite can be from 20 phr to 250 phr, from 20 phr to 200 phr, from 30 phr to 150 phr, from 40 phr to 100 phr, or from 50 phr to 65 phr.
[0136] Other loadings, filler types, and formulations are disclosed herein.
[0137] Filler yield loss Filler yield loss is determined by subtracting the measured phr of filler in the delivered composite from the theoretical maximum phr of filler in the elastomer (assuming all filler charged to the mixer is kneaded into the composite). This measured amount can be obtained from thermogravimetric analysis (TGA). Filler yield loss (%) is then calculated as follows: [(theoretical filler phr)-(measured filler phr)] / (theoretical filler phr) x 100 This filler yield loss includes lost filler present on the surface of the composite due to poor filler incorporation into the elastomer. Alternatively, any process of the methods disclosed herein does not result in significant loss of the filler initially charged into the mixer. In any of the methods disclosed herein, the filler yield loss can be no more than 10%, e.g., no more than 9%, or no more than 8%, or no more than 7%, or no more than 6%, or no more than 5%, or no more than 4%, or no more than 3%, or no more than 2%, or no more than 1%, e.g., a filler yield loss in the range of 0.1% to 10%, 0.1% to 5%, 0.1% to 2%, 0.5% to 10%, 0.5% to 5%, 0.5% to 2%, 1% to 10%, 1% to 5%, or 1% to 2%.
[0138] filling rate When mixing dry filler with solid elastomer, this is typically done to maximize the fill factor in order to maximize the amount of composite produced. Fill factor (%) = (volume of material loaded into mixer) / (actual mixer chamber volume). The actual mixer chamber volume includes consideration of the mixer design, e.g., rotor volume. The fill factor is often selected to ensure that the ram remains contained until the end of mixing, and a typical fill factor value is about 72% for a dry mix.
[0139] In any of the methods disclosed herein, the loading of at least the solid elastomer and the wet filler can be such that the mixing chamber of the mixer has a fill factor of about 25% to about 90% (dry weight basis) of its volumetric capacity. In any of the methods disclosed herein, the loading of at least the solid elastomer and the wet filler can be such that the mixing chamber of the mixer has a fill factor of about 50% to about 80% of its volumetric capacity, such as about 50% to about 72%, about 50% to about 70%, about 50% to about 68%, about 60% to about 75%, about 60% to about 72%, about 60% to about 70%, or about 60% to about 68% of its volumetric capacity.
[0140] In any of the methods disclosed herein, the method is such that the loading of at least the solid elastomer and the wet filler into a mixer (e.g., an internal mixer such as a batch mixer or other mixer) is such that the loading of the at least the solid elastomer and the wet filler on a dry weight basis is not more than 72%, not more than 70%, not more than 68%, or not more than 66%, such as about 30% to 72%, 40% to 70%, 45% to 70%, 30% to 60%, 50 to 72%, 50 to 70%, 50 to 68%, 60 to 72%, 60 to 70%, 60 to 68%, 65 to 72%, 65 to 70%, 65 to 68%, or 40 to 60%, or 50 to 60%, etc. A more specific example is charging a mixer with at least a solid elastomer and wet filler such that the fill rate does not exceed 68% and the solid elastomer comprises at least 50 wt% natural rubber.
[0141] It has been observed that certain elastomers, such as natural rubber, swell when mixed with wet fillers. As mixing progresses, the temperature of the mixture rises, superheating the water incorporated into the mixture. This causes the mixture to swell, thereby increasing its overall volume. If the initial fill rate is very high, the swelling may be enough to exert excessive force on the ram (also known as a floating weight), causing the ram to lift from its fully retracted position. In this situation, the portion of the mixture immediately below the ram begins to temporarily isolate itself from the bulk of the mixture, reducing its mixing effectiveness. Additionally, this isolated mixture may form a "plug" below the deflected ram, inhibiting steam release from the mixer. Consequently, such ram deflection extends the batch cycle time and impairs filler dispersion. If a plug occurs (e.g., adding 6 PPD), and the ram is raised by the batch sequence, excessive amounts of steam may be suddenly released, posing a safety concern.
[0142] Thus, when the elastomer, such as natural rubber, is capable of swelling in the presence of an evaporable liquid, the fill factor (on a dry weight basis) of the solid elastomer containing the wet filler and natural rubber can be in the range of not more than 70%, not more than 68%, not more than 66%, e.g., 60%-70%, 60%-68%, 60%-66%, or 65%-68%. The solid elastomer can contain at least 50%, at least 75%, at least 90%, or at least 95% natural rubber. For example, the solid elastomer can be a blend of natural rubber and at least one additional elastomer, such as polybutadiene and / or styrene-butadiene rubber, or other elastomers disclosed herein. The filler can be any of the fillers disclosed herein, such as carbon black, silicon-treated carbon black, and silica.
[0143] Optionally, in any of such methods involving a controlled fill rate of 72% or less, or 70% or less, or 68% or less, or methods disclosed herein utilizing a batch mixer or similar type mixer, the mixer can be equipped with a ram capable of downward vertical movement to a lowest position where the ram is housed adjacent to one or more rotors within the mixer. During mixing, the mixer can be operated with maximum ram deflection from the lowest position a distance not exceeding 30% of the diameter of one or more rotors. Alternatively, this distance can be not exceeding 25%, or not exceeding 20%, or not exceeding 15%, or not exceeding 10%, or not exceeding 5% of the diameter of one or more rotors. Optionally, for any of the methods disclosed herein, during the mixing step, the fill rate is optimized to minimize ram deflection.
[0144] In certain embodiments, the packing ratio can be a function of one or more variables. For example, the packing ratio can be determined based on the rotor type. For example, when a batch mixer (e.g., a tangential mixer) is used, for a two-blade rotor, the packing ratio can be 72% or less; for a two- or four-blade rotor, the packing ratio can be 70% or less; for a two-, four-, or six-blade rotor, the packing ratio can be 68% or less. In other embodiments, for example, when an intermeshing mixer is used, the packing ratio can be 60% or less.
[0145] In certain embodiments, the use of a wet filler allows for the use of higher tip speeds compared to typical dry mixing processes. Because such higher tip speeds increase the average pressure applied to the ram, they increase the tendency to overforce the ram. Alternatively, the lower packing ratios disclosed herein in combination with increased tip speeds may be desirable for commercial production. With the relatively high packing ratios typically used in the dry mixing industry, the associated problems that arise following mixing with a wet filler can make commercial production impractical. Thus, in certain embodiments, packing ratios disclosed herein, e.g., packing ratios of 70% or less, 68% or less, or 66% or less, may be utilized in conjunction with higher tip speeds, e.g., a tip speed of 0.6 m / s for at least 50% of the mixing time, and other tip speeds disclosed herein.
[0146] Time averaged release rate As described herein, the process provides operating conditions that balance longer mixing times (relative to dry mixing processes) with evaporation or removal of liquid within a reasonable time. If insufficient specific power input is present or Tz is too low, the liquid may remain in the mixture longer than desired, resulting in inefficient mixing. In other cases, the liquid may evaporate or be removed too quickly, causing the mixture to resemble a dry mix, thereby preventing the benefits associated with long effective mixing times and sufficient energy input. In any of the methods disclosed herein, the rate of liquid release, including but not limited to the rate of liquid evaporation from the composite during mixing, may be measured as the time-averaged release rate of liquid per kg of composite, and this rate may be 0.01 to 0.14 kg / (min·kg), or 0.01 to 0.07 kg / (min·kg), or other rates below or above this range. This release rate may be the overall release rate of liquid removed by any means during mixing, or it may be the release rate due to evaporation alone. In the case of aqueous liquids, the evaporation rate can be thought of as the rate of steam evolution or steam generation.
[0147] Alternatively, the time-averaged release rate (kg / kg min) can be calculated from the following formula: Time-averaged release rate = total liquid removed / (release time x composite weight) where: Composite weight is determined on a dry weight basis; Total liquid removed (kg) = liquid in wet filler - liquid content in delivered composite; Discharge time = Ram stop time (minutes) - Mastication time of rubber only (minutes).
[0148] As discussed herein, the ram down time is the time (period or amount of time) that the ram is operated to its lowest position.
[0149] It is believed that an optimized time-average discharge rate of liquid (e.g., the time-average discharge rate of evaporated liquid) can provide improved dispersion of filler in the elastomer, balanced with a suitable mixing time. Discharge rates of less than 0.01 kg / (min·kg) generally reflect longer time periods for removing liquid, e.g., at Tz below 65°C and / or specific energy levels below 1,500 kJ / kg, and / or tip speeds below 0.5 m / s or 0.6 m / s. Discharge rates greater than 0.15 kg / (min·kg) can reflect shorter mixing times. Non-optimized time-average delivery rates result in mixing conditions similar to a dry mix, which can result in poor rubber properties or damage the elastomer.
[0150] Energy efficiency At least when mixing the solid elastomer and wet filler, the mixing (in one or more mixing steps) is performed with an energy efficiency in the range of 20% to 80%. R ) to at least one rotor of a mixer, or to one or more rotors (e.g., at least two rotors, four rotors, etc.), where the energy efficiency is based on the formula: Energy efficiency = required heat / E R ×100% where: - heat requirement (kJ / kg) is the energy (kJ) required to remove the liquid from 1 kg of composite material with 100% efficiency; -The required heat is (heat of evaporation) + (sensible heat), -Heat of evaporation = liquid removed (kg) * latent heat of evaporation of liquid (2260kJ / kg for water), -Sensible heat = liquid removed (kg) * specific heat volume of liquid (4.1855 kJ / kg / K for water) * (100 - ambient temperature °C), - Amount of liquid removed (kg) = total liquid added to mixer (kg) - liquid content of delivered composite (kg). Typically, the amount of liquid content at the time of loading can be determined from the amount of liquid in the wet filler.
[0151] Energy efficiencies in the range of 20% to 80% would, by definition, be greater than the energy efficiencies for dry mixing processes (e.g., <5%). In certain embodiments, energy efficiencies can range from 30% to 80%, 40% to 80%, 50% to 80%, 30% to 70%, 40% to 70%, 50% to 70%, 30% to 60%, 40% to 60%, 50% to 60%, or 40% to 55%. Energy efficiencies greater than 80% are believed to be associated with insufficient mixing.
[0152] Other operating parameters to be considered include the maximum pressure that can be used. The pressure affects the temperature of the filler and rubber mixture. If the mixer is a batch mixer equipped with a ram, the pressure inside the mixer chamber can be affected by controlling the pressure applied to the ram cylinder.
[0153] Multi-stage or multi-step mixing Any of the methods disclosed herein relate, in part, to methods of preparing composite materials that involve at least two mixing steps or stages. These two (or more) mixing steps can be considered multi-step or multi-stage mixing, involving a first mixing step or stage and at least a second mixing step or stage. The one or more multi-stage mixing processes can be batch, continuous, semi-continuous, and combinations thereof.
[0154] For multi-step processes, a method for preparing a composite material includes charging or introducing into a first mixer at least a) one or more solid elastomers and b) one or more fillers, wherein at least one filler, or a portion of at least one filler, is a wetting filler as described herein (e.g., a wetting filler containing a liquid present in an amount of at least 15 wt. % based on the total weight of the filler and the wetting filler). The combination of the solid elastomer with the wetting filler during this mixing step(s) forms a mixture or composite material, which may be considered the first mixing step or stage. The method further includes mixing the mixture during this first mixing step to an extent that at least a portion of the liquid is removed by evaporation or a vaporization process occurring during mixing. This first mixing step (in one or more mixing steps) or stage may be carried out using one or more of the processes previously described for forming a composite material, with the understanding that it is not necessary to have a liquid content of no more than 10 wt. % for the mixture (e.g., the mixture) discharged from the mixer after the first mixing step after completion of the first mixing. Stated another way, due to the multi-stage process(es), the resulting mixture after completion of the first mix (or first mixing step) from the first mixer can have a liquid content greater than 10 wt %, but has a reduced liquid content (wt %) compared to the liquid content of the combined solid elastomer and wet filler at the start of the first mixing step.
[0155] The method then includes mixing or further mixing the mixture in at least a second mixing step or stage using the same mixer (i.e., the first mixer) and / or a second mixer(s) different from the first mixer. The mixing by the second mixer can be such that the second mixer or second mixer has a ram pressure of 5 psi or less, a ram elevated to at least 75% of the ram's maximum level (e.g., at least 85%, at least 90%, at least 95%, or at least 99% or 100% of the ram's maximum level), a ram operated in a floating mode, and / or a ram positioned so as not to substantially contact the mixture; and / or a ramless mixer; and / or operated at a mixture fill factor ranging from 25% to 70%. The method then includes discharging the formed composite from the last mixer used such that the composite has a liquid content of no more than 10% by weight, based on the total weight of the composite.
[0156] After the first mixing, the further mixing step(s) performed for multi-stage mixing can utilize any one or more of the mixing procedures or parameters or steps utilized in the first mixing step described herein. Thus, in performing the further mixing steps or stages, the same or different mixer design and / or the same or different operating parameters as the first mixer can be used in the further mixing stages. The mixers and options thereof described above with respect to the first mixing step and / or the operating parameters described above with respect to the mixing steps can optionally be used in the further or second mixing step (e.g., a mixing step including a tip speed of at least 0.5 m / s for at least 50% of the time, or at least 0.6 m / s for at least 50% of the time, and / or a resulting specific energy of at least 1100, at least 1400, or at least 1500 kJ / kg composite material, and / or mixing to a specified temperature of at least 120°C, and / or a loading factor not exceeding 7%, and / or a Tz of 40°C or higher, 50°C or higher, 60°C or higher, or 65°C or higher, and / or an evaporation rate and / or number of rotors, and / or rotor type, and / or temperature control means, and / or an average specific power of at least 2.5 kW / kg applied over the mixing time and / or over continuous mixing, etc., as described herein). Any or all of one or more of these options can be utilized with respect to the further mixing step(s) described above. A second or subsequent mixing step can utilize different process parameters than those used in the first mixing step. Any combination of these mixing parameters can be used in multi-stage mixing. Accordingly, any of the methods disclosed herein further include methods of preparing a composite material in multi-stage mixing, where one or more of the following parameters can be utilized in at least one mixing step, at least two mixing steps, or all mixing steps: i. at least one temperature control means is set to a temperature Tz of 65°C or greater during said mixing; and / or ii. during said mixing, the one or more rotors operate at a tip speed of at least 0.6 m / s for at least 50% of the mixing time; and / or iii. Applying an average specific power of at least 2.5 kW / kg over the mixing time; and / or iv. (a) charging includes charging into the mixer at least a solid elastomer containing at least 50 wt. % natural rubber and a wet filler, wherein the loading level of the at least solid elastomer and the wet filler on a dry weight basis does not exceed 68%; and / or v. The mixture is continuous; and / or vi. optionally adding at least one additive selected from antidegradants and coupling agents during said charging (a) or said mixing (b), and optionally adding one or more rubber chemicals after the mixer has reached a temperature of 120°C or greater; and / or vii. (a) said charging and (b) said mixing before the mixer reaches the specified temperature are carried out in the substantial absence of one or more rubber chemicals; and / or viii. The mixer has a fill factor, and the fill factor on a dry weight basis of at least the solid elastomer and the wet filler is not more than 72%, not more than 70%, or not more than 68%.
[0157] In such a multi-stage mixing process, at least one of the aforementioned parameters may be utilized in the first mixing step, at least two of the aforementioned parameters may be utilized in the first mixing step, or at least three of the aforementioned parameters may be utilized in the first mixing step, or at least four of the aforementioned parameters may be utilized in the first mixing step, or all of the aforementioned parameters may be utilized in the first mixing step. And, in such a multi-stage mixing process, at least one of the aforementioned parameters may be utilized in the second or further mixing step(s), at least two of the aforementioned parameters may be utilized in the second or further mixing step(s), or at least three of the aforementioned parameters may be utilized in the second or further mixing step(s), or at least four of the aforementioned parameters may be utilized in the second or further mixing step(s), or all of the aforementioned parameters may be utilized in the second or further mixing step(s). The parameters used in the first mixing step or stage can be the same or different from the parameters used in the second or further mixing step(s). The mixer used in the first mixing step can be the same or different from the mixer used in the second or further mixing step(s).
[0158] Thus, for multi-stage mixing processes, in at least one option, the first mixer used in the first mixing step is utilized in a further or second mixing step. Before the first mixer or another mixer is used in the second mixing step, there may be a further option of a resting period during which the composite material formed from the first mix is allowed to rest, cool, or both in the first mixer or another container or location (e.g., mixing, stopping, then further mixing). For example, this resting period may be for the mixture to achieve a material temperature of less than 180°C before the further mixing step begins (e.g., the discharged mixture may have a material temperature in the range of about 100°C to about 180°C, about 70°C to 179°C, about 100°C to about 170°C, or about 120°C to about 160°C). Alternatively, the resting period before the further mixing step begins may be about 1 minute to 60 minutes, or longer. The material temperature can be obtained in a number of ways known in the art, such as by inserting a thermocouple or other temperature measuring device into the mixture or composite.
[0159] In a multi-stage process, a second mixing step (second mixing stage) can include charging the mixer with other ingredients in addition to the mixture discharged from the first mixing step. For example, the method can include charging an additional filler, such as a dry filler, a wet filler (e.g., having a liquid present in an amount of at least 15% by weight), or a combination thereof, before or during the second mixing step. The additional filler can be the same or different from the filler already present in the mixture. For example, the mixture discharged from the first mixer can be considered a masterbatch, either in whole or in part, combined with the additional filler.
[0160] For multi-stage mixing processes, in at least one option, at least a second mixer is used in the further mixing step(s). If this option is used, the second mixer can have the same or a different design as the first mixer and / or the same or one or more different operating parameters as the first mixer. Specific examples are provided below for the first mixer and second mixer options, but are not meant to be limiting.
[0161] For example, the first mixer can be a tangential mixer or an intermeshing mixer, and the second mixer can be a tangential mixer, an intermeshing mixer, an extruder, a kneader, or a roll mill.
[0162] For example, the first mixer can be an internal mixer, and the second mixer can be a kneader, a single screw extruder, a twin screw extruder, a multi-screw extruder, a continuous compounder, or a roll mill.
[0163] For example, the first mixer can be a first tangential mixer and the second mixer can be a second (different) tangential mixer.
[0164] For example, the first mixer can be operated with a ram pressure above 0 psi, and the second mixer with a ram pressure of 5 psi or less, such as 3 psi or less, or even 0 psi. This option can also be used when the second mixing step utilizes the same mixer as the first mixing step. For example, the first mixer is operated with a ram and the second mixer is operated without a ram.
[0165] For example, the second mixer may be utilized and operated at a fill rate of the mixture on a dry weight basis ranging from 25% to 70%, 25% to 60%, 25% to 50%, 30% to 50%, or other fill rate amounts described herein.
[0166] If a second mixer is utilized, any of the methods disclosed herein can include the additional step of delivering the mixture from the first mixer to the second mixer to perform the second mixing step. Alternatively, delivery can occur directly to the second mixer, or delivery can occur such that the mixture is delivered to a holding vessel (e.g., bin, table) and then transferred or conveyed (e.g., using a conveyor belt or other feeding device) to the second mixer.
[0167] As a further option, a third or subsequent mixer may be utilized in any of the methods disclosed herein. If this option is used, the third or subsequent mixer may have the same or a different design as the first and / or second mixer, and / or may have the same or one or more different operating parameters as the first and / or second mixer.
[0168] In any of the multi-step processes disclosed herein, the final discharged composite material (e.g., the composite material discharged after the second, third, or subsequent mixing step) can have a liquid content of no more than 5%, no more than 4%, no more than 3%, no more than 2%, or no more than 1% by weight, based on the total weight of the composite material. This amount can range from 0.1% to 5%, 0.1% to 4%, 0.1% to 3%, 0.1% to 2%, 0.1% to 1%, 0.5% to 5%, 0.5% to 4%, 0.5% to 3%, 0.5% to 2%, or 0.5% to 1% by weight, based on the total weight of the composite material discharged from the mixer at the end of the process.
[0169] In any of the multi-step processes disclosed herein, the total liquid content (or total water content or moisture percentage) of the materials charged to the mixer at the beginning of the process is higher than the liquid content of the composite material when the first mixing step is stopped. For example, the liquid content of the mixture when the first mixing step is stopped can be 10% to 50% lower (wt% to wt%), or 25% or more lower, or 10% or more lower than at the start of the first mixing step.
[0170] Further, in any of the multi-step processes disclosed herein, the total liquid content (or total water content or moisture percentage) of the mixture at the end of the first mixing step is higher than the liquid content of the final composite material delivered at the end of the process (after the final mixing step). For example, the liquid content of the delivered composite material can be 10% to 50% lower (wt% to wt%), or 25% or more lower, or 10% or more lower than after completion of the first mixing step.
[0171] In any of the multi-stage processes disclosed herein, the temperature of the composite material upon discharge from the final mixer (e.g., discharge temperature) can range from 130° C. to 180° C., for example, 140° C. to 170° C. Alternatively, the multi-stage process can be monitored by material temperature, or probe temperature, which is the temperature of the mixture or composite material obtained or measured immediately (within 5 minutes, 3 minutes, or 60 seconds) after discharge, and the average temperature of the composite material can be considered.
[0172] In a multi-stage process, examples of preferred ingredients or parameters include, but are not limited to, the filler containing carbon black and the elastomer containing natural rubber, and / or the filler containing silica and the elastomer containing natural rubber, and / or the mixture from the first mixer output having a material temperature of 100° C. to 140° C., 110° C. to 140° C., 130° C. to 150° C., 120° C. to 150° C., or 130° C. to 140° C., and / or the resulting total specific energy of the mixer (first mix) from the first mixer is in the range of 1,000 kJ / kg to 2,500 kJ / kg. Any one or more of these preferred ingredients or parameters may be used in combination for any of the multi-stage processes disclosed herein.
[0173] Another multi-step process is: (a) charging at least a solid elastomer and a wet filler containing a liquid present in an amount of at least 15% by weight based on the total weight of the filler and the wet filler into a first mixer having one or more rotors; and (b) mixing at least a solid elastomer and a wet filler in one or more mixing steps to form a mixture, and at least one of the mixing steps performing the mixing with one or more rotors operating at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, with a mixer temperature controlled by at least one temperature control means, and removing at least a portion of the liquid from the mixture by evaporation.
[0174] This tip speed can have other values as disclosed herein.
[0175] Alternatively, instead of controlling the tip speed, this process may have the advantage of applying a suitable average specific power that allows a reasonable ram down time for mixing in the first mixer. (a) charging at least a solid elastomer and a wet filler containing a liquid present in an amount of at least 15% by weight based on the total weight of the filler and the wet filler into a first mixer having one or more rotors; and (b) mixing at least a solid elastomer and a wet filler in one or more mixing steps to form a mixture, and at least one of said mixing steps applying an average specific power of at least 2.5 kW / kg at a mixer temperature controlled by at least one temperature control means and over a ram down time, said mixing being carried out, and removing at least a portion of the liquid from the mixture by evaporation.
[0176] For example, the method can include applying an average specific power of at least 3 kW / kg over the ram down time, at least 3.5 kW / kg over the ram down time, at least 4 kW / kg over the ram down time, at least 4.5 kW / kg over the ram down time, or at least 5 kW / kg over the ram down time, e.g., in the range of 2.5-10 kW / kg, 3-10 kW / kg, 3.5-10 kW / kg, 3-10 kW / kg, 4.5-10 kW / kg, 5-10 kW / kg, 2.5-8 kW / kg, 3-8 kW / kg, 3.5-8 kW / kg, 3-8 kW / kg, 4.5-8 kW / kg, or 5-8 kW / kg over the ram down time. The ram down time can be 15 minutes or less, 12 minutes or less, 10 minutes or less, 8 minutes or less, or 6 minutes or less.
[0177] Depending on either option, i.e., tip speed or specific power, the method: (c) delivering from the first mixer a mixture containing a filler dispersed in an elastomer at a loading of at least 20 phr, wherein the mixture has a liquid content reduced to an amount less than the liquid content at the start of step (b), and wherein the mixture has a material temperature in the range of 100°C to 180°C; (d) mixing the mixture from (c) in a second mixer to obtain a composite material, wherein the second mixer is operated under at least one of the following conditions: (i) Ram pressure of 5 psi or less; (ii) rum elevated to at least 75% of its highest level; (iii) rams operated in floating mode; (iv) a ram positioned so as not to come into substantial contact with the mixture; (v) the mixer is ramless; and (vi) the filling rate of the mixture is 25% to 70%; and (e) delivering from the second mixer a composite material having a liquid content of less than 3 wt. % based on the total weight of the composite material.
[0178] This multi-step process provides additional parameters for dispersing the filler into the elastomer. Control of the batch mixing time, expressed as the ram stop time in the first mixer, allows for dispersion of the filler into the elastomer to a certain extent, followed by mixing in the second mixer under conditions that minimize substantial or any degradation of the solid elastomer, such as natural rubber. Thus, one or more steps of mixing in the first mixer are accompanied by evaporation of at least a portion of the liquid, so that the mixture discharged from the first mixer has a reduced liquid content, e.g., liquid present in the wet filler, below the liquid content at the start of step (b). This liquid content can be reduced by 50 wt%, 60 wt%, 70 wt%, or more. The amount of liquid content remaining in the discharged mixer can depend on the filler type, elastomer type, filler loading, etc. In certain embodiments, it is desirable to have a certain amount of moisture remaining in the mixture to take advantage of the wet mixing process and its benefits in the mixing that occurs in the second mixer. Alternatively, it may be desirable to remove most of the liquid during one or more mixing steps in the first mixer due to other fillers and / or elastomer types. Thus, the delivered mixture may contain between 0.5% and 20% by weight of the mixture, e.g., between 0.5% and 17%, between 0.5% and 15%, between 0.5% and 12%, between 0.5% and 10%, between 0.5% and 7%, between 0.5% and 5%, between 0.5% and 3%, between 0.5% and 2%, between 1% and 20%, between 1% and 17%, between 1% and 15%, between 1% and 12%, between 1% and 10%, between 1% and 7%, between 1% and 5%, between 1% and 3%, between 1% and 2%, between 2% and 20%, between 2% and 2%. It can have a liquid content (depending in part on the liquid content of the wetting filler) that ranges from 17%, 2% to 15%, 2% to 12%, 2% to 10%, 2% to 7%, 2% to 5%, 2% to 3%, 3% to 20%, 3% to 17%, 3% to 15%, 3% to 12%, 3% to 10%, 3% to 7%, 3% to 5%, 5% to 20%, 5% to 17%, 5% to 15%, 5% to 12%, 5% to 10%, or 5% to 7%.
[0179] The material temperature (also known as probe temperature) of the mixture at the time of discharge in (c) can be measured, for example, by inserting a thermocouple or other temperature measuring device into the mixture or composite. Generally, a drier mixture discharged from the first mixer has a higher material temperature, so this material temperature can be a gauge for moisture content. Discharging the mixture when the material temperature is within a specific range, e.g., 100°C to 180°C, will ensure that a specific amount of moisture remains in the mixture. Because it is not always possible to obtain the material temperature of the mixture during the mixing process, the mixer temperature can be monitored. For example, a relevant mixer temperature can be obtained by inserting a thermocouple into the chamber. Such mixer temperature can be calibrated to reasonably approximate or correlate with the material temperature. For example, the mixer temperature can differ from the material temperature by as much as 40°C or less, 30°C or less, 20°C or less, 10°C or less, or 5°C or less. The difference between the mixer temperature and the material temperature is not necessary, as long as this difference is reasonably consistent with each mix.
[0180] For example, the material temperature of the mixture can range from 100° C. to 150° C., e.g., 100° C. to 145° C., 100° C. to 140° C., 110° C. to 150° C., 110° C. to 145° C., 110° C. to 140° C., 120° C. to 150° C., 120° C. to 145° C., 120° C. to 120° C., 125° C. to 150° C., 125° C. to 145° C., 125° C. to 140° C., 130° C. to 150° C., 130° C. to 145° C., 130° C. to 140° C., 135° C. to 150° C., 135° C. to 145° C., or 135° C. to 140° C. In certain embodiments, the material temperatures mentioned may be appropriate when the elastomer is natural rubber.
[0181] For synthetic elastomers such as butadiene rubber or styrene-butadiene rubber, the material temperature of solid elastomers containing such synthetic elastomers can range from 100°C to 170°C, 110°C to 170°C, 120°C to 170°C, 130°C to 170°C, 140°C to 170°C, or 150°C to 170°C.
[0182] Optionally, the filler comprises at least one material selected from carbon black and coated and treated versions thereof (e.g., at least 50 wt%, at least 75 wt%, or at least 90 wt% of the filler is selected from carbon black and silicon-treated carbon black). The wet filler can have liquid present in an amount of at least 20 wt%, at least 30 wt%, or in an amount ranging from 40% to 65 wt%. In step (b) and optionally step (a), the at least one temperature control means is set to a temperature Tz in the range of 60°C to 110°C, for example, 65°C or higher, in the range of 65°C to 100°C, or in the range of 75°C to 90°C.
[0183] Optionally, at least 50% (at least 75% or at least 90%) of the filler is silica. The charging can further include charging a coupling agent into the mixer, for example, with at least a portion (or a first portion) of the wet filler. In step (b) and optionally step (a), the at least one temperature control means is set to a temperature Tz in the range of 40°C to 100°C, or in the range of 40°C to 75°C, or in the range of 50°C to 90°C, or in the range of 50°C to 75°C. The wet filler can have liquid present in an amount of at least 20% by weight, or in an amount in the range of 20% to 65% by weight.
[0184] As an option for the first mixer, the mixing time is the ram stop time, e.g., not more than 15 minutes, not more than 10 minutes, not more than 8 minutes, e.g., a ram stop time ranging from 3 to 15 minutes, or from 3 to 10 minutes, or from 5 to 10 minutes. Other ranges are disclosed herein. As another option for the second mixer, the mixing time is the period of time between the start of mixing and delivery.
[0185] The total specific energy of the mixing process in the first mixer can be similar to that described earlier in this specification or can be different, for example to ensure a shorter batch time. In addition, the filler type can affect the total specific energy. Alternatively, the resulting total specific energy of the mixing in the first mixer, i.e., the mixing in (b), is in the range of 1000 kJ / kg to 2500 kJ / kg.
[0186] With respect to mixing in the second mixer, it is desirable to operate the mix under conditions that do not degrade the elastomer. Under typical mixing conditions, after the material is loaded into the mixer chamber, the ram is lowered to its fully retracted position, which applies pressure to the material during the mixing process. During mixing in the second mixer, this pressure is desirably relieved, which can occur under one or more of the following conditions: (i) For example, the ram can be retracted, but essentially no pressure is applied to the ram, e.g., a pressure of 5 psi or less; or (ii) the ram is raised to at least 75% of its maximum level. Some mixers allow the ram to be positioned at a specific height. A ram in a fully retracted position is at 0% of its maximum level, as opposed to a ram raised to its maximum level or in a fully open position, which is the typical ram position when material is loaded into a mixer. A ram positioned at a height of at least 75% of its maximum level, e.g., at least 80%, at least 85%, at least 90%, at least 95%, or fully raised to its maximum level (100%), ensures minimal contact between the ram and the elastomer loaded into the mixer. (iii) When no pressure is applied to the mixing chamber, certain rams can operate as floating weights, e.g., in floating mode. While the ram is in contact with the elastomer, the applied pressure is minimal. (iv) The ram is positioned so that it does not substantially contact the mixture. If the contents have a low fill factor, e.g., as low as 25%, it may not be necessary to position the ram at a height of at least 75% of its maximum level. The ram can be positioned at a height that does not substantially contact the mixture, e.g., no more than 10% of the ram's surface (by area), e.g., no more than 5% of the ram's surface, contacts the mixture, or 0% of the ram's surface does not contact the mixture. (v) Certain mixers are ramless, i.e., do not include a ram. Examples of ramless mixers are model numbers IM550ET, IM1000ET from Harburg Freudenberger Maschinenbau GmbH (HF).(vi) The fill rate of the mixture on a dry weight basis is in the range of 25% to 70%, e.g., 25% to 60%, 25% to 55%, 25% to 50%, 25% to 45%, 25% to 40%, 30% to 70%, 30% to 60%, 30% to 55%, 30% to 50%, 30% to 45%, 30% to 40%, 35% to 70%, 35% to 60%, 35% to 55%, 35% to 50%, 35% to 45%, or 35% to 40%. By controlling the fill rate, no manipulation or positioning of the ram may be necessary.
[0187] The material temperature of the final composite material exiting the second mixer (e.g., the composite material exiting step (e)) can also be monitored, again to minimize elastomer degradation. Such material temperatures can be similar to those described above for the mixture exiting the first mixer.
[0188] The mixtures output from (c) are intermediates in a multi-stage or multi-step process, but they may also be considered composites. In certain cases, the vulcanizates formed from the mixture of step (c) may have specific rubber properties that are improved over vulcanizates prepared from composites resulting from dry mixing processes for a given composition (e.g., elastomer type, filler type, filler loading, and, optionally, compounding ingredients and curatives). Such vulcanizates are discussed in more detail below.
[0189] As discussed herein, it is understood that additional mixers or mixing steps can be used. For example, after the composite material leaves the second mixer, the composite material can be subjected to additional mastication, such as by mixing in either the first or second mixer, or a third mixer.
[0190] Continuous Mixing Alternatively, the process is a continuous mixing process in which at least the solid elastomer and wet filler (e.g., wet carbon black pellets) are mixed in a continuous mixer. The continuous mixer allows for control of the feed rates of the solid elastomer, wet filler, and other ingredients, and / or control of water evaporation. Such control, in turn, can lead to a process that is amenable to automation.
[0191] For example, a method for preparing a composite material includes: (a) charging a continuous flow of at least a solid elastomer and a pelletized wet filler into an input end of a continuous mixer, wherein the wet filler contains a liquid present in an amount of at least 15% by weight based on the total weight of the filler and the wet filler; (b) conveying the solid elastomer and wet filler along the length of a continuous mixer, wherein during conveying, mixing occurs with removal of at least a portion of the liquid by evaporation; and (c) delivering from the discharge end of the continuous mixer a composite material containing a filler dispersed in an elastomer at a loading of at least 20 phr with a filler yield loss not exceeding 10%, wherein the composite material has a liquid content not exceeding 10 wt. % based on the total weight of the composite material.
[0192] The at least one solid elastomer and wet filler can be fed into a continuous mixer by mechanisms well known in the art, such as conveyors, hoppers, screw feeders, and combinations thereof. For example, the filler can be fed into a hopper, which can then be fed into a screw feeder and ultimately into an intake port at one end of the elongated chamber of the mixer. The solid elastomer can be provided as chunks, strips, pellets, or other solid form and fed into the mixer by a conveyor. Thus, a "continuous flow" loading of elastomer does not necessarily require a single continuous length of polymer, as long as the loading can be measured as a rate of elastomer or filler per unit time.
[0193] A continuous mixer can have, for example, an elongated chamber. Optionally, the solid elastomer, the wet filler, and / or a mixture containing the solid elastomer and the wet filler are continuously transported or conveyed along the length of the continuous mixer. For example, the material is continuously conveyed from the input end of the elongated chamber along the length of the chamber until the material contacts one or more axially oriented rotors within the elongated chamber. The mixture may diverge from its path along the length of the mixer, but the net path of the mixture is along the length of the mixer. The material may be conveyed through one or more rotors, whereby mixing occurs, and subsequently discharged from the discharge end. An example of such a mixer is a continuous compounder, such as the FCM™ Farrel Continuous Mixer manufactured by Farrel-Pomini. Other continuous mixers include the Unimix continuous mixer and MVX (Mixing, Venting, eXtruding) equipment from Farrel Pomini (Ansonia, CT, USA), the long continuous mixer from Pomini, the Pomini continuous mixer, the twin rotor co-rotating intermeshing extruder, the twin rotor counter-rotating non-intermeshing extruder, the continuous compounding extruder, the twin screw kneading extruder manufactured by Kobe Steel, and the Kobe continuous mixer.
[0194] The continuous mixer can be, for example, an extruder, such as a twin-screw extruder, equipped with a rotatable screw that can simultaneously transport and mix the solid elastomer, the wet filler, and / or a mixture containing the solid elastomer and the wet filler along a chamber to a discharge end.
[0195] As an additional option, continuous mixers, such as twin-screw extruders or other mixers, can have multiple zones. These zones can be defined based on temperature. For example, upon initial entry into the continuous mixer, at least the solid elastomer and filler can be mixed in a first zone at a temperature where little or no evaporation occurs. Alternatively, this first zone can be operated at a temperature ranging from 100°C to 140°C. The first zone can have a constant temperature range throughout the first zone, or the temperature can increase as the elastomer and filler mixture passes through the zone. A second zone downstream of the first zone is a water evaporation zone, where the mixture can be subjected to higher temperatures and / or reduced pressure to reduce the water content. Such liquid (e.g., water) evaporation zone(s), also known as steam stripping zone(s), are commercially available for twin-screw extruders and can include one or more pumping systems and / or one or more heating systems, either or both of which can facilitate evaporation of the liquid. The steam stripping zone may be equipped with one or more vents to facilitate removal of liquid vapor. A rotatable screw may be present in the continuous mixer to transport the mixture through each zone.
[0196] The temperatures of the various zones may be controlled as described herein, for example as described for Tz.
[0197] One or more zones may be provided downstream of the water evaporation zone to allow for the addition of desired amounts of antioxidants, rubber chemicals, and / or curatives (e.g., an addition zone) and / or cooling (e.g., one or more cooling zones).
[0198] Examples of suitable twin-screw extruders are described in Patent Publication Nos. WO 2018 / 219630, WO 2018 / 219631, and WO 2020 / 001823, the disclosures of which are incorporated herein by reference. For example, WO 2018 / 219630 describes an extruder as part of a continuous process for drying agglomerated wet masterbatch that can be employed as a continuous mixer. The extruder includes 11 zones, the first five of which are mixing zones, and the sixth is a water evaporation (water stripping) zone, which can remove essentially all of the water content from the mixture.
[0199] The continuous mixing process may further include presses, rollers, extruders, and the like, for receiving the dried composite material and shaping the resulting composite material into sheets, strips, and the like.
[0200] As disclosed herein, "continuous" with respect to a process or method or any step involves the operation of a process or method (or a segment or portion thereof) where the step or action occurs without any interruption or halt that occurs in batch processing methods. A "continuous process" or "continuous method" can involve a process or method in which composite materials and / or vulcanized rubber and / or precursors to composite materials are made in a continuous operation without forming intermediate products that are used at a later point in time. A "continuous process" or "continuous method" can involve a continuous flow or input of raw materials such that the processing of the raw materials occurs continuously, and the production of the resulting material occurs on a continuous basis without any interruptions except for maintenance and normal stops in production (e.g., end of shift, end of production lot, etc.).
[0201] Alternatively, to simplify loading of the materials into the continuous mixer, the wet filler and solid elastomer can be combined (e.g., as a pre-blended mixture) prior to continuous mixing. For example, the wet filler and solid elastomer can be combined in a batch process (e.g., in an internal mixer) before being loaded into the continuous mixer. This entire process, including the pre-blended or pre-blended steps, can be considered a semi-continuous process; however, the step of mixing the wet filler and solid elastomer, including removal of at least a portion of the liquid by evaporation, is carried out in the continuous mixer and is a continuous process. The composite material exiting the continuous mixer can be further processed by post-processing steps disclosed herein or further masticated or mixed in a subsequent mixer, whether batch or continuous.
[0202] Alternatively, the wet filler may be loaded in pellet form, which can facilitate continuous loading. For example, pelletized wet filler can minimize filler yield loss. The pelletized wet filler can be any pelletized filler described herein, such as carbon black, silicon-treated black, silica, and blends thereof.
[0203] Integrated Manufacturing Alternatively, any one of the methods disclosed herein may lend itself to execution as a unit operation within a multi-unit manufacturing plant, such as a plant for producing fillers, elastomers and / or elastomer compounds, vulcanized rubber and rubber products, or combinations thereof. For fillers, there is a need to optimize a filler manufacturing process with an intermediate step requiring the formation of a wet filler, followed by a subsequent drying step to produce dry granules with low dust and easy handling. These steps often require complex and expensive drying equipment to produce granules that are easy to transport but difficult to disperse in rubber. The integrated plant option may be feasible when fillers, such as carbon black or silica, or any of the fillers and combinations thereof described herein, are made, and / or when the wet filler contains process water or other liquids from the process used to produce the filler, such as carbon black pellets that never dry or silica that never dries.
[0204] In one integrated manufacturing option, where carbon black filler and / or silicon-treated carbon black filler are produced by an oven process (e.g., a carbon black manufacturing facility), water is used to densify the fluffy carbon black by wet-granulating the fluff, resulting in as-produced water-containing carbon black. Typically, the as-produced, wet carbon black is conveyed to a dryer where it is dried, and then packaged and shipped to reduce dust and minimize the costs and handling issues associated with transporting and storing the wet, low-density, fluffy carbon black particulate material. With an integrated manufacturing process, the as-produced, never-dried carbon black may be conveyed directly to a mixer as a wet filler for mixing with a solid elastomer in the mixing process described herein. In a multi-stage or step mixing process, composites made from such never-dried carbon blacks are subjected to one or more additional integrated unit operations, including, but not limited to, compounding with the same or different elastomers and fillers, and / or with or without additional materials such as oils, resins, polymers, and other typical rubber chemicals and additives; further mixing or working; curing to form vulcanizates; and further processing into rubber articles.
[0205] In another integrated manufacturing option, where silica fillers are produced by a precipitation process (e.g., a precipitated silica manufacturing facility), precipitated silica is generally produced by acidifying a silicate solution, which leads to polymerization, nucleation, and growth of silica particles in an aqueous medium. The growing particles can be colloidal, leading to agglomeration, which can be reinforced by further deposition of silica on the particle surface. The final size, surface area, and structure of the particles are controlled by controlling the silicate concentration, temperature, pH, and metal ion content. At the end of the particle formation process, an aqueous slurry of particles is obtained. This slurry undergoes solid-liquid separation, typically involving filtration through a filter press, belt filter, or vacuum filter. The filtered particles are then washed to remove salts and other soluble materials, and further filtered to produce a filter cake. The filter cake typically contains 60-90% by weight water and 10-40% silica, based on the total filter cake weight. A typical manufacturing process is described in US Pat. No. 7,250,463, which is incorporated herein by reference in its entirety.
[0206] Traditionally, wet filter cakes are dried fairly slowly in ovens or rotary dryers. Silicas produced in this manner are generally considered difficult to disperse in rubber. Alternative drying processes involve rapid heating to high temperatures for a short period of time, such as in a spray dryer. Precipitated silicas produced by this alternative drying process generally result in much better dispersibility in rubber. During conventional drying, the combination of high capillary forces exerted by a thin layer of water and chemical reactions between silanol groups on adjacent particles is thought to lead to dense agglomeration with strong bonds between particles. The most important chemical reaction is condensation, which leads to siloxane bonds. This reaction is promoted by heat and by the removal of water. The strong bonds formed between particles are not easily broken during rubber mixing, therefore, tending to result in poor dispersion. During the rapid drying process, the residence time of the particles at high temperatures is very short, providing less time for particle rearrangement or compaction and fewer condensation reactions. This leads to fewer bonds or strong contacts between silica particles, and therefore better rubber dispersion. However, silica particle-particle bonding is not believed to be completely eliminated in the rapid drying process, but is only reduced compared to conventional processes.
[0207] In an integrated manufacturing option, it would be beneficial to use never-dried silica (e.g., slurry or cake), thereby avoiding or reducing the traditional silica drying process and kneading the silica wet filler into a solid elastomer. The advantages of such a multi-unit manufacturing operation include those enumerated herein, along with obtaining high quality silica-elastomer composites, a streamlined and simplified manufacturing process for producing composites from never-dried silica, and significant cost savings.
[0208] Such multi-unit integrated manufacturing operations can produce never-drying fillers that can be used immediately or within hours or days after production in the elastomer mixing operation. The never-drying fillers can be transported to the elastomer mixing operation by conveyor line, bin, rail, truck, or other means. The never-drying fillers can be in cake or paste, liquefied, or pelletized form. By such a process, fillers can be produced in a filler plant and then transported or conveyed to an adjacent elastomer plant, where the elastomeric material can be synthesized, purified, compounded, or otherwise fabricated into a desired solid elastomer for use in one or more of the processes of the integrated manufacturing options described herein, and optionally, the elastomer plant can further convey the formed composite and proceed to perform further processing, including, but not limited to, preparing a vulcanized rubber and forming a tire or one or more tire components or other products containing the vulcanized rubber or composite.
[0209] Because the integrated manufacturing process utilizes wet fillers, the ability to use never-drying fillers, such as never-drying carbon black or never-drying silica, or other never-drying fiber, particulate, or elastomeric reinforcing materials, and combinations thereof, can potentially create a more efficient operation and allow for turnkey operations. The use of any never-drying filler is possible in such integrated processes described herein.
[0210] One example of a method utilizing integrated manufacturing operations may involve producing a filler at a filler production facility by a process in which the final product, a wet filler, contains liquid present in an amount of at least 15 wt. % based on the total weight of the filler and wet filler; conveying the wet filler to at least one mixer; charging at least a solid elastomer and the wet filler into the at least one mixer, wherein the at least one mixer is equipped with at least one temperature control means; mixing at least the solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of the mixing steps, the mixing is carried out at a mixer temperature controlled by at least one temperature control means and removing at least a portion of the liquid from the mixture by evaporation; and discharging from the at least one mixer a composite containing the filler dispersed in the elastomer at a loading of at least 20 phr with a filler yield loss of not more than 10%, wherein the composite has a liquid content of not more than 20 wt. % based on the total weight of the composite.
[0211] With respect to integrated manufacturing operations, the method can further include any one or more of the following embodiments: the wet filler is a never-drying filler; the filler manufacturing facility is a carbon black manufacturing facility and the wet filler is a never-drying carbon black; the filler manufacturing facility is a precipitated silica manufacturing facility and the wet filler is a never-drying precipitated silica; the filler manufacturing facility is a silicon-treated carbon black manufacturing facility; and further including preparing a vulcanized rubber containing the elastomer composite, and optionally forming an article containing the vulcanized rubber or the elastomer composite.
[0212] With respect to integrated manufacturing operations, the method may further include any one or more of the following parameters during the method: at least one temperature control means is set to a temperature Tz of 65°C or greater during the mixing; and / or during the mixing, the one or more rotors operate at a tip speed of at least 0.6 m / s for at least 50% of the mixing time; and / or charging the mixer with at least a solid elastomer containing at least 50 wt% natural rubber and a wet filler, wherein the loading level on a dry weight basis of the at least solid elastomer and the wet filler does not exceed 68%; and / or carrying out the mixing with a mixer temperature controlled by at least one temperature control means and applying an average specific power of at least 2.5 kW / kg over the mixing time; and / or the mixing is a continuous mixing process and the charging includes charging a continuous flow of at least the solid elastomer and the wet filler into the continuous mixer; and / or (iii) the ram is operated in a floating mode; (iv) the ram is positioned so as not to substantially contact the mixture; (v) the mixer is ramless; and (vi) the fill factor of the mixture is between 25% and 70%; and / or one or more rotors operate at a tip speed of at least 0.5 m / s for at least 50% of the mixing time, resulting in a total specific energy of at least 1500 kJ / kg of composite material, and wherein the wet filler is a wet particle filler; and / or at least one additive selected from an antidegradant and a coupling agent is optionally added during said charging (a) or said mixing (b), and optionally one or more rubber chemicals are added after the mixer reaches a temperature of 120°C or greater.
[0213] The preceding discussion of filler amounts, types, and other parameters equally applies here (e.g., various examples and ranges for exemplary loading amounts are provided previously and equally apply here).
[0214] Filler Type The wet filler used in any of the methods disclosed herein can be a solid material, such as a solid bulk material in the form of a powder, paste, pellet, or cake. In the present method, the wet filler can be dispersed in the elastomer at a loading ranging from 1 phr to 100 phr on a dry weight basis, or at a loading ranging from 20 phr to 250 phr, 20 phr to 200 phr, e.g., 20 phr to 180 phr, 20 phr to 150 phr, 20 phr to 120 phr, or 20 phr to 100 phr, as well as other ranges disclosed herein.
[0215] In any of the methods disclosed herein, a wet filler such as wet carbon black, wet silica, or wet silicon-treated carbon black (described in further detail herein) can be described in terms of its liquid content determined as a function of its oil absorption number (OAN). Wet fillers such as wet carbon black that can be used herein can satisfy the formula: k*OAN / (100+OAN)*100, where k ranges from 0.3 to 1.1, or from 0.5 to 1.05, or from 0.6 to 1.1, or from 0.95 to 1, or from 0.95 to 1.1, or from 1.0 to 1.1.
[0216] More specifically, such a wet filler having this type of "wet" form as a solid can contain, for example, up to 80 wt% of liquid (e.g., water and / or other aqueous liquid) based on the total weight of the wet filler. The wet filler can contain 80 wt% or less, for example, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, etc., relative to the total weight of the filler, such as about 15% to about 80 wt%, about 20% to about 80%, about 25% to about 80%, about 30% to about 80%, about 35% to about 80%, about 40% to about 80%, about 15 wt% to about 70%, about 20 wt% to about 70%, about 25% to 70%, about 30% to 70%, about 35% to about 80%, about 40% to about 80%, etc. The wet filler can have a liquid content (e.g., water content) of at least 30% by weight (based on the weight of the filler), or at least 40% by weight, or in an amount of 20% to 80% by weight, or about 15% to 65%, or about 20% to 65%, or about 25% to 65%, or about 30% to 65%, or about 35% to 65%, or about 40% to 65%, or about 15% to 60%, or about 20% to 60%, or about 25% to 60%, or about 30% to 60%, or about 35% to 60%, or about 40% to 60% by weight.
[0217] More specifically, the wet carbon black can have a liquid content in the range of about 20% to about 70% by weight, for example, about 25% to about 70%, about 30% to about 70%, about 35% to about 70%, about 40% to about 70%, about 45% to about 70%, about 50% to about 70%, or about 20% to about 65% by weight, based on the total weight of the wet carbon black.
[0218] The wetted filler can be any conventional filler used with elastomers, such as reinforcing fillers, including, but not limited to, carbon black, silica, carbon black-containing fillers, silica-containing fillers, and / or any combination thereof. The filler can be particulate, fibrous, or plate-like, such as wetted particulate fillers. For example, particulate fillers are made of discrete bodies. Such fillers often have an aspect ratio (e.g., length to diameter) of 3:1 or less, or 2:1 or less, or 1.5:1 or less. Fibrous fillers can have aspect ratios of, for example, 2:1 or more, 3:1 or more, 4:1 or more, or even higher. Typically, fillers used to reinforce elastomers have microscopic (e.g., hundreds of micrometers or smaller) or nanoscale (e.g., less than 1 micrometer) dimensions. In the case of carbon black, the discrete bodies of particulate carbon black refer to agglomerates or agglomerates formed from primary particles, but not the primary particles themselves. In other embodiments, the fillers can have plate-like structures, such as graphene and reduced graphene oxide.
[0219] The filler can be chemically treated (e.g., chemically treated carbon black, chemically treated silica, silicon-treated carbon black) and / or chemically modified. The filler can be or include carbon black having attached organic group(s). The filler can have one or more coatings present on the filler (e.g., silicon-coated material, silica-coated material, carbon-coated material). The filler can be oxidized and / or have other surface treatments. The filler can include at least one material selected from carbonaceous materials, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, recycled carbon, recovered carbon black (e.g., as defined in ASTM D8178-19), rCB, graphene, graphene oxide, reduced graphene oxide (e.g., reduced graphene oxide worms as disclosed in PCT Publication No. WO 2019 / 070514 A1 or high-density reduced graphene oxide granules as disclosed in U.S. Provisional Patent Application No. 62 / 857,296, filed June 5, 2019, the disclosures of which are incorporated herein by reference), carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, as well as corresponding coated or chemically treated versions thereof (e.g., chemically treated carbon black). There are no limitations regarding the type of silica, carbon black, or other fillers that can be used. Further details regarding fillers are provided in other sections of this specification.
[0220] The filler can be or include a blend of carbon black and silica in any weight ratio, such as a weight ratio ranging from 1:99 to 99:1, 25:75 to 75:25, or 45:55 to 55:45. Alternatively, the blend of carbon black and at least one other filler (e.g., silica and / or silicon-treated carbon black) can include at least 1 wt% carbon black (i.e., not more than 99 wt% silica), at least 5 wt% carbon black, at least 10 wt% carbon black, at least 20 wt% carbon black, at least 30 wt% carbon black, at least 50 wt% carbon black, at least 66 wt% carbon black, at least 75 wt% carbon black, at least 90 wt% carbon black, at least 95 wt% carbon black, or at least 99 wt% carbon black (i.e., not more than 1 wt% silica), where the wt% values are based on the total weight of the blend on a dry basis. The filler can be a blend of at least two fillers, such as those selected from carbon black, silica, and silicon-treated carbon black.
[0221] Alternatively, the blend of silica and at least one other filler (e.g., carbon black and / or silicon-treated carbon black) can contain at least 1 wt% silica (i.e., not more than 99 wt% carbon black), at least 5 wt% silica, at least 10 wt% silica, at least 20 wt% silica, at least 30 wt% silica, at least 50 wt% silica, at least 66 wt% silica, at least 75 wt% silica, at least 90 wt% silica, at least 95 wt% silica, or at least 98 wt% silica or at least 99 wt% silica (i.e., not more than 1 wt% carbon black or any other filler), or at least 99.8 wt% silica, where the wt% values are based on the total weight of the blend on a dry basis.
[0222] Optionally, the mixture can further include one or more non-wetting fillers (e.g., any of the non-wetting fillers described herein, e.g., dry fillers, e.g., fillers having no more than 10 wt% liquid). When non-wetting fillers are present, the total amount of filler is such that at least 10 wt%, at least 20 wt%, at least 30 wt%, at least 40 wt%, at least 50 wt%, or at least 60 wt%, or at least 70 wt%, or at least 80 wt%, or at least 90 wt%, or at least 95 wt% of the filler is wet filler, e.g., from about 10 wt% to 99 wt% of the total amount of filler. 0.5 wt%, about 20 wt% to 99.5 wt%, about 30 wt% to 99.5 wt%, about 40 wt% to 99.5 wt%, about 50 wt% to 99.5 wt%, or about 50 wt% to 99 wt%, 60 wt% to 99 wt%, or 70 wt% to 99 wt%, or 80 wt% to 99 wt% can be wetting filler, with the balance of this filler being non-wetting or not considered a wetting filler.
[0223] The amount of filler (e.g., wet filler alone or wet filler with other fillers) loaded into the mixture may range (on a dry weight basis) from 1 phr to 200 phr, 1 phr to 150 phr, 1 phr to 100 phr, or 30 phr to 150 phr, e.g., about 5 phr to 100 phr, 10 phr to 100 phr, 20 phr to 100 phr, 30 phr to 100 phr, 40 phr to 100 phr, 50 phr to 100 phr, or 5 phr to 70 phr, 10 phr to 70 phr, 20 phr to 70 phr , 30 phr to 70 phr, 35 phr to 70 phr, 40 phr to 70 phr, 5 phr to 65 phr, 10 phr to 65 phr, 20 phr to 65 phr, 30 phr to 65 phr, 35 phr to 65 phr, 40 phr to 65 phr, 5 phr to 60 phr, 10 phr to 60 phr, 20 phr to 60 phr, 30 phr to 60 phr, 35 phr to 60 phr, 40 phr to 60 phr, 5 phr to 50 phr, or other amounts within or outside one or more of these ranges. Other ranges include about 15 phr to about 180 phr, about 20 phr to about 200 phr, about 20 phr to about 180 phr, about 20 phr to about 150 phr, about 20 phr to about 100 phr, about 25 phr to about 80 phr, about 30 phr to about 150 phr, about 35 phr to about 115 phr, about 35 phr to about 100 phr, about 40 phr to about 100 phr, about 40 phr to about 90 phr, about 40 phr to about 80 phr, about 29 phr to about 175 phr, about 40 phr to about 110 phr, about 50 phr to about 175 phr, about 60 phr to about 175 phr, etc. The filler can be any filler disclosed herein, such as carbon black, silica, or silicon-treated carbon black, whether alone or with one or more other fillers. The aforementioned phr amounts also apply to fillers dispersed in the elastomer (filler loading).
[0224] With respect to graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, and multi-walled carbon nanotubes, these fillers can be dispersed in elastomers at loadings ranging from 1 phr to 100 phr, e.g., from 1 phr to 50 phr, from 1 phr to 25 phr, from 1 phr to 20 phr, or from 1 phr to 10 phr. When combined with other fillers such as carbon black, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, and multi-walled carbon nanotubes can be dispersed in elastomers at loadings ranging from 0.5 phr to 99 phr, e.g., from 0.5 phr to 50 phr, from 0.5 phr to 25 phr, from 0.5 phr to 20 phr, or from 0.5 phr to 10 phr. In such combinations, the graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, and multi-walled carbon nanotubes can be present in an amount of at least 1%, at least 2%, at least 5%, at least 10%, at least 15%, at least 20%, at least 30%, at least 40%, or at least 50% by weight of the total amount of filler dispersed in the elastomer. In certain cases, for example, with respect to graphene, graphene oxide, reduced graphene oxide (e.g., reduced graphene oxide worms and dense reduced graphene oxide granules), carbon nanotubes, single-walled carbon nanotubes, and multi-walled carbon nanotubes, the loading of these fillers in the total filler can be much lower, and their loading in the composite can be 0.01 phr to 10 phr, 0.1 to 5 phr, or 0.1 to 2 phr.
[0225] For example, for oil-extended elastomers or oiled recipes, filler loadings are typically higher and can range from 20 phr to 250 phr, 50 phr to 250 phr, 70 phr to 250 phr, 60 phr to 150 phr.
[0226] The carbon black can be untreated or treated carbon black or a mixture thereof. The filler can be or include wet carbon black in the form of pellets, fluffy powder, granules, and / or agglomerates. The wet carbon black can be formed into pellets, granules, or agglomerates, for example, in a pelletizer, fluidized bed, or other device to create a wet filler.
[0227] The wet carbon black can be one or more of the following: - carbon black that never dries; and / or - Carbon black pellets that never dry out; and / or dried carbon black pellets that have been rewetted, e.g., with water, in a pelletizer; and / or dried carbon black pellets that have been crushed and then rewetted with water in a pelletizer; and / or dried carbon black pellets combined with water; and / or -Fluffy powder, granules or agglomerates combined with water.
[0228] In typical carbon black manufacturing, carbon black is first prepared as a dry, fine-particle (fluffy) material. This fluffy carbon black can be densified by a conventional pelletizing process, for example, by combining the carbon black with a liquid, such as by adding water, and feeding the mixture into a pin pelletizer. Pin pelletizers are well known in the art and include the pin pelletizer described in U.S. Pat. No. 3,528,785. The resulting wet pellets are then heated under controlled temperature and time parameters to remove the liquid from the pellets before further handling and shipping. In an alternative process, carbon black pellets can be produced by a process that omits the drying step. In such a process, the pelletized carbon black contains at least 20% by weight, e.g., at least 30% by weight, or at least 40% by weight, of process water, based on the total weight of the wet carbon black. These "never-dried carbon black" pellets can be used directly in the claimed process after pelletizing. As used herein, "never dried" refers to pellets prepared from fluffy carbon black, not subjected to a drying step, and retaining a moisture content greater than 15 wt. % of the total weight of the filler (pellets), e.g., greater than 20 wt. %, greater than 30 wt. %, greater than 40 wt. %, or in the range of 20-65 wt. %, 20-60 wt. %, 30-65 wt. %, 30-60 wt. %, 40-65 wt. %, or 40-60 wt. %. For example, never dried pellets can refer to pellets formed from fluffy carbon black, densified by a conventional pelletizing process, and used without a drying step. During storage and / or transportation, never dried pellets may lose some water. However, it is understood that "never dried" pellets maintain or have a moisture content as disclosed herein.
[0229] Alternatively, dried carbon black pellets (such as commercially available carbon black pellets) can be rewetted in a pelletizer. These pellets can be granulated, crushed, classified, and / or milled, for example, in a jet mill. The resulting carbon black is in fluffy form and can be repelletized in a pelletizer or otherwise compressed or agglomerated into wet carbon black in the presence of water. Alternatively, the fluffy carbon black can be compressed into other shapes, such as brick shapes, by equipment known in the art. Alternatively, carbon black, such as carbon black pellets or fluffy carbon black, can be wetted using, for example, a fluidized bed, a spray, a mixer, or a rotating drum. When the liquid is water, the never-dried or rewetted carbon black can achieve a water content in the range of 20% to 80%, 30% to 70% by weight, or other ranges, such as 55% to 60% by weight, based on the total weight of the wet carbon black.
[0230] The carbon black used in any of the methods disclosed herein can be any grade of reinforcing and semi-reinforcing carbon black. Examples of ASTM grade reinforcing grades are N110, N121, N134, N220, N231, N234, N299, N326, N330, N339, N347, N351, N358, and N375 carbon black. Examples of ASTM grade semi-reinforcing grades are N539, N550, N650, N660, N683, N762, N765, N774, N787, N990 carbon black and / or N990 grade thermal black.
[0231] This carbon black is 20m 2 / g~250m 2 / g range or higher, e.g., at least 60 m 2 / g, e.g. 60m 2 / g~150m 2 / g, 70m2 / g~250m 2 / g, 80m 2 / g~200m 2 / g, 90m 2 / g~200m 2 / g, 100m 2 / g~180m 2 / g, 110m 2 / g~150m 2 / g, 120m 2 / g~150m 2 / g, or 30m 2 / g~200m 2 / g, etc. The STSA (Statistical Thickness Specific Surface Area) is determined in accordance with ASTM Test Procedure D-5816 (measured by nitrogen adsorption).
[0232] This carbon black has a viscosity of about 30 mL / 100 g to about 150 mL / 100 g, for example, about 30 mL / 100 g to about 125 mL / 100 g, about 30 mL / 100 g to about 115 mL / 100 g, about 50 mL / 100 g to about 150 mL / 100 g, about 50 mL / 100 g to about 125 mL / 100 g, about 50 mL / 100 g to about 115 mL / 100 g, about 60 mL / 100 g to about 120 mL / 100 g, or about 70 mL / 100 g. The carbon black may have a Compressed Oil Absorption (COAN) ranging from about 70 mL / 100 g to about 125 mL / 100 g, from about 70 mL / 100 g to about 115 mL / 100 g, from about 80 mL / 100 g to about 150 mL / 100 g, from about 80 mL / 100 g to about 125 mL / 100 g, from about 80 mL / 100 g to about 115 mL / 100 g, or from about 80 mL / 100 g to about 100 mL / 100 g. The Compressed Oil Absorption (COAN) is determined according to ASTM D3493. Optionally, the carbon black may have a COAN of 70 mL / 100 g to 115 mL / 100 g and a COAN of 60 mL / 100 g. 2 / g~150m 2 / g range.
[0233] As mentioned, the carbon black can be rubber black, particularly a reinforcing grade of carbon black or a semi-reinforcing grade of carbon black. Carbon blacks sold under the Regal®, Black Pearls®, Spheron®, Sterling®, Propel®, Endure®, and Vulcan® trademarks from Cabot Corporation, Raven®, Statex®, Furnex®, and Neotex® trademarks and the CD and HV lines available from Birla Carbon (formerly Columbian Chemicals), and Corax®, Durax®, Ecorax®, and Purex® trademarks and the CK line available from Orion Engineered Carbons (formerly Evonik and Degussa Industries), as well as other fillers suitable for use in rubber or tire applications, may also be utilized for use with various implementations. Suitable chemically functionalized carbon blacks include those disclosed in WO 96 / 18688 and US 2013 / 0165560, the disclosures of which are incorporated herein by reference. Any mixture of these carbon blacks may be used. Carbon blacks having surface areas and structures superior to ASTM grades and representative values selected for blending with rubber, such as those described in U.S. Patent Application Publication No. 2018 / 0282523, the disclosure of which is incorporated herein by reference, may be used in wet fillers and composites made by any of the methods disclosed herein.
[0234] The carbon black can be oxidized, such as carbon black surface-treated with an oxidizing agent. Oxidizing agents include, but are not limited to, air, oxygen gas, ozone, NO (including mixtures of NO and air), peroxides, such as hydrogen peroxide, persulfates including sodium persulfate, potassium persulfate, or ammonium persulfate, hypohalides such as sodium hypochlorite, halites, halates, or perhalates (such as sodium chlorite, sodium chlorate, or sodium perchlorate), oxidizing acids such as nitric acid, and transition metal-containing oxidants, such as permanganates, osmium tetroxide, chromium oxide, or cerium ammonium nitrate. Mixtures of oxidants, particularly mixtures of gaseous oxidants such as oxygen and ozone, may also be used. Additionally, carbon blacks prepared using other surface modification methods, such as chlorination and sulfonation, to introduce ionic or ionizable groups onto the pigment surface may also be used. The processes utilized to make oxidized carbon black are known in the art, and several types of oxidized carbon black are commercially available.
[0235] The carbon black can be furnace black, gas black, thermal black, acetylene black, lamp black, plasma black, recovered carbon black (e.g., as defined in ASTM D8178-19), or a carbon product containing silicon-containing and / or metal-containing species. The carbon black can be a multiphase agglomerate containing at least one carbon phase and at least one metal-containing or silicon-containing species phase, i.e., silicon-treated carbon black. In silicon-treated carbon black, the silicon-containing species, e.g., silicon oxide or carbide, is an intrinsic part of the carbon black and is distributed throughout at least a portion of the carbon black agglomerate. Silicon-treated carbon black is not a coated or otherwise modified carbon black agglomerate, but actually represents a two-phase agglomerate particle. One phase is carbon, which still exists as graphite crystals and / or amorphous carbon, while the second phase is silica and possibly other silicon-containing species. Thus, the silicon-containing species phase of silicon-treated carbon black is an inherent part of the agglomerates, distributed throughout at least a portion of the agglomerates. Ecoblack™ silicon-treated carbon black is available from Cabot Corporation. The preparation and characteristics of these silicon-treated carbon blacks are described in U.S. Patent No. 6,028,137, the disclosure of which is incorporated herein by reference.
[0236] Silicon-treated carbon black can contain silicon-containing regions that are primarily on the surface of the carbon black agglomerates but are still part of the carbon black, and / or can contain silicon-containing regions distributed throughout the carbon black agglomerates. The silicon-treated carbon black can be oxidized. The silicon-treated carbon black can contain from about 0.1% to about 50% by weight of silicon, based on the weight of the silicon-treated carbon black, for example, from about 0.1% to about 46.6%, from about 0.1% to about 46%, from about 0.1% to about 45%, from about 0.1% to about 40%, from about 0.1% to about 35%, from about 0.1% to about 30%, from about 0.1% to about 25%, from about 0.1% to about 20%, from about 0.1% to about 15%, from about 0.1% to about 10%, from about 0.1% to about 5%, or from about 0.1% to about 2% by weight. These amounts can be about 0.5 wt% to about 25 wt%, about 1 wt% to about 15 wt% silicon, about 2 wt% to about 10 wt%, about 3 wt% to about 8 wt%, about 4 wt% to about 5 wt%, or about 6 wt%, all based on the weight of the silicon-treated carbon black.
[0237] Those skilled in the art will recognize that, apart from the silicon content of silicon-treated carbon black, the surface of the particle may also have varying amounts of silica and carbon black. For example, the surface area of silicon-treated carbon black may comprise from about 5% to about 95% silica, e.g., from about 10% to about 90%, from about 15% to about 80%, from about 20% to about 70%, from about 25% to about 60%, from about 30% to about 50%, or from about 35% to about 40%, e.g., up to about 20% or up to about 30% silica. The amount of surface silica may be determined by the difference between the particle's surface area as measured by iodine value (ASTM D-1510) and nitrogen adsorption (i.e., BET, ASTM D6556).
[0238] Alternatively, filler, such as carbon black, can be chemically treated.For example, carbon black can be bonded with at least one organic group.The bond can occur through diazonium reaction, in which at least one organic group has a diazonium salt substituent, as described in detail in, for example, U.S. Patent Nos. 5,554,739; 5,630,868; 5,672,198; 5,707,432; 5,851,280; 5,885,335; 5,895,522; 5,900,029; and 5,922,118, the disclosures of which are incorporated herein by reference.
[0239] Optionally, with respect to the filler, at least silica, one or more silica types, or any combination of silica(s), can be used in any embodiment disclosed herein. The silica can include precipitated silica, fumed silica, silica gel, and / or colloidal silica. The silica can be or include untreated silica and / or chemically treated silica. Silica is suitable for reinforcing elastomer composites and has a Brunaur Emmett Teller surface area (BET, determined by multipoint BET nitrogen adsorption, ASTM D1993) of about 20 m 2 / g ~ approx. 450m 2 / g; approx. 30m 2 / g ~ approx. 450m 2 / g; approx. 30m 2 / g~about 400m 2 / g; or about 60m 2 / g ~ approx. 250m 2 / g, approx. 60m 2 / g ~ approx. 250m 2 / g, approx. 80m 2 / g~about 200m 2 / g. Silica can be characterized by a 2 / g~250m 2 / g, for example, about 80m 2 / g~200m 2 / g or 90m 2 / g~200m 2 / g, 80m 2 / g~175m2 / g, or 80m 2 / g~150m 2 The filler may have an STSA in the range of 1 / g. Highly dispersible precipitated silicas can be used as fillers in the present process. Highly dispersible precipitated silica ("HDS") is understood to mean any silica that has a substantial ability to disaggregate and disperse within an elastomeric matrix. Such dispersion may be determined in known manner by electron or optical microscopy of thin sections of the elastomer composite. Examples of commercially available HDS grades include Perkasil® GT 3000GRAN silica from WR Grace, Ultrasil® 7000 silica from Evonik Industries, Zeosil® 1165 MP, 1115 MP, Premium, and 1200MP silica from Solvay SA, Hi-Sil® EZ 160G silica from PPG Industries, and Zeopol® 8741 or 8745 silica from Evonik Industries. Conventional non-HDS precipitated silicas may also be used. Examples of commercial grades of conventional precipitated silica include Perkasil® KS 408 silica from WR Grace, Zeosil® 175GR silica from Solvay SA, Ultrasil® VN3 silica from Evonik Industries, and Hi-Sil® 243 silica from PPG Industries, Inc. Precipitated silicas having surfaces bonded with silane coupling agents may also be used. Examples of commercial grades of chemically treated precipitated silica include Agilon® 400, 454, or 458 silica from PPG Industries, and Coupsil silicas, such as Coupsil® 6109 silica, from Evonik Industries.
[0240] As explained above, the amount of liquid in the filler is equally applicable to silica, but as a more specific example, when silica is used as part of or as the entire wet filler, the silica can have the liquid present in an amount of about 25 wt % to about 75 wt %, for example, about 30% to about 75%, about 40% to about 75%, about 45% to about 75%, about 50% to about 75%, about 30% to about 70%, about 40% to about 70%, about 45% to about 70%, about 50% to about 70%, about 30% to about 65%, about 40% to about 65%, about 45% to about 65%, about 50% to about 65%, about 30% to about 60 wt %, about 40% to about 60%, about 45% to about 60%, or about 50% to about 60 wt %, based on the weight of the total wet filler or the weight of only the wet silica present.
[0241] Typically, the silica (e.g., silica particles) has a silica content of at least 20 wt%, at least 25 wt%, at least 30 wt%, at least 35 wt%, at least 40 wt%, at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, or nearly 100 wt% or 100 wt%, or about 20 wt% to about 100 wt%, all based on the total weight of the particle. Any silica(s) can be chemically functionalized to have attached or adsorbed chemical groups, such as attached or adsorbed organic groups. Any combination of silica(s) can be used. The silica can be a silica having a partially or entirely hydrophobic surface, which can be a silica that is hydrophobic or a silica that begins to become hydrophobic by treatment (e.g., chemical treatment) to render the silica surface hydrophobic. The hydrophobic surface may be obtained by chemical modification of the silica particles by hydrophobizing silanes without ionic groups, such as bis-triethoxysilylpropyl tetrasulfide. Hydrophobic surface-treated silica particles suitable for use herein may be obtained from commercial suppliers, such as Agilon® 454 silica and Agilon® 400 silica from PPG Industries. Silicas with low surface silanol density, such as those obtained through dehydroxylation at temperatures above 150°C, for example via a calcination process, may also be used herein. Intermediate forms of silica obtained from precipitation processes in the form of cakes or pastes without drying (silicas that never dry) may be added directly to a mixer as a wet filler, thus eliminating the complex drying and other downstream processing steps used in the conventional production of precipitated silica.
[0242] In any embodiment and at any step, the coupling agent can be introduced at any step (or steps or locations) so long as the coupling agent has an opportunity to become dispersed in the composite material. The coupling agent can be or include one or more silane coupling agents, one or more zirconate coupling agents, one or more titanate coupling agents, one or more nitro coupling agents, or any combination thereof. Coupling agents include bis(3-triethoxysilylpropyl)tetrasulfane (e.g., Si 69 from Evonik Industries, Struktol SCA98 from Struktol), bis(3-triethoxysilylpropyl)disulfane (e.g., Si 75 and Si 266 from Evonik Industries, Struktol SCA985 from Struktol), 3-thiocyanatopropyl-triethoxysilane (e.g., Si 264 from Evonik Industries), γ-mercaptopropyl-trimethoxysilane (e.g., VP Si 163 from Evonik Industries, Struktol SCA989 from Struktol), γ-mercaptopropyl-triethoxy ... 263), zirconium dineoalkanolatodi(3-mercapto)propionato-O,N,N'-bis(2-methyl-2-nitropropyl)-1,6-diaminohexane, S-(3-(triethoxysilyl)propyl)octanethioate (e.g., NXT coupling agent from Momentive, Friendly, WV), and / or coupling agents having one or more chemically similar or identical chemical groups. Additional specific examples of coupling agents include, but are not limited to, the trade names VP Si 363 from Evonik Industries and NXT Z and NXT Z-50 silanes from Momentive. The coupling agents described herein are used to provide a hydrophobic surface modification of silica (precoupled or pretreated silica) prior to use in any of the processes disclosed herein.It should be understood that any combination of elastomers, additives, and additional composite materials may be added to the elastomer composite, for example, in a compounder.
[0243] Other fillers are described in U.S. Patent Application Publication No. 2018 / 0282523 and European Patent No. 2423253B1, the disclosures of which are incorporated herein by reference.
[0244] Solid Elastomer The solid elastomer may be or include natural and / or synthetic elastomers and / or rubbers. Elastomer types include natural rubber (NR), styrene butadiene rubber (SBR), polybutadiene rubber (BR) and polyisoprene rubber (IR), ethylene-propylene rubber (e.g., EPDM), isobutylene-based elastomers (e.g., butyl rubber), polychloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, and silicone elastomers.
[0245] Illustrative elastomers include natural rubber, SBR, BR, IR, functional SBR, functional BR, functional NR, EPDM, butyl rubber, halogenated butyl rubber, CR, NBR, HNBR, fluoroelastomers, perfluoroelastomers, and silicone rubber, including, for example, natural rubber, functional natural rubber, styrene-butadiene rubber, functional styrene-butadiene rubber, polybutadiene rubber, functional polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, nitrile rubber, hydrogenated nitrile rubber, and blends thereof, or, for example, natural rubber, styrene-butadiene rubber, polybutadiene rubber, and blends thereof, such as blends of first and second solid elastomers. When two or more elastomers are used, these two or more elastomers can be charged simultaneously (as one charge or two or more charges) into the mixer as a blend, or the elastomers can be added individually, in any order and amount. For example, the solid elastomer can include natural rubber compounded with one or more elastomers disclosed herein, such as butadiene rubber and / or styrene-butadiene rubber. For example, the additional solid elastomer can be added separately to the mixer, and the natural rubber can be added separately to the mixer.
[0246] The solid elastomer can be or include natural rubber. Natural rubber can also be chemically modified in some manner. For example, it can be treated to chemically or enzymatically modify or reduce various non-rubber components, or the rubber molecules themselves can be modified with various monomers or other chemical groups such as chlorine. Other examples include epoxidized natural rubber and natural rubber having a nitrogen content of at most 0.3 wt %, as described in PCT Publication No. WO 2017 / 207912.
[0247] Other exemplary elastomers include, but are not limited to, rubber; polymers (e.g., homopolymers, copolymers, and / or terpolymers) of 1,3-butadiene, styrene, isoprene, isobutylene, 2,3-dialkyl-1,3-butadiene (where alkyl is methyl, ethyl, propyl, etc.), acrylonitrile, ethylene, propylene, and the like. The elastomers may have a glass transition temperature (Tg), as measured by differential scanning calorimetry (DSC), ranging from about −120° C. to about 0° C. Examples include, but are not limited to, styrene-butadiene rubber (SBR), natural rubber and its derivatives, such as chlorinated rubber, polybutadiene, polyisoprene, poly(styrene-co-butadiene), and oil-extended derivatives of any of the foregoing. Blends of any of the foregoing may also be used. Particularly suitable synthetic rubbers include: copolymers of styrene and butadiene containing from about 10% to about 70% by weight of styrene and from about 90 to about 30% by weight of butadiene, such as a copolymer of 19 parts styrene and 81 parts butadiene, a copolymer of 30 parts styrene and 70 parts butadiene, a copolymer of 43 parts styrene and 57 parts butadiene, a copolymer of 50 parts styrene and 50 parts butadiene; polymers and copolymers of conjugated dienes such as polybutadiene, polyisoprene, polychloroprene, and the like, as well as polymers and copolymers of such conjugates. Copolymers of substituted dienes with ethylene-containing monomers copolymerizable therewith, such as styrene, methylstyrene, chlorostyrene, acrylonitrile, 2-vinylpyridine, 5-methyl-2-vinylpyridine, 5-ethyl-2-vinylpyridine, 2-methyl-5-vinylpyridine, allyl-substituted acrylates, vinyl ketones, methyl isopropenyl ketone, methyl vinyl ether, α-methylene carboxylic acids and their esters and amides, such as acrylic acid amide and dialkylacrylic acid amide. Also suitable for use herein are copolymers of ethylene with other higher α-olefins, such as propylene, 1-butene, and 1-pentene. Other polymers are described in U.S. Patent Application Publication No. 2018 / 0282523 and European Patent Application No. 2423253B1, the disclosures of which are incorporated herein by reference.Other polymers include silicone-based elastomers or hybrid systems having silicone and hydrocarbon domains.
[0248] Rubber chemicals The composite material prepared by any of the methods disclosed herein can consist of an elastomer and a filler, i.e., no rubber chemicals are present. Alternatively, in addition to the filler and elastomer, the composite material can contain at least one additive selected from stabilizing agents and coupling agents. Alternatively, the composite material can include one or more rubber chemicals. In another alternative, the composite material can be a curative-containing composition.
[0249] In a typical dry mixing process (solid elastomer and dry filler), it is often necessary to add certain additives; typical additives include antidegradants, coupling agents, and one or more rubber chemicals that allow the filler to disperse in the elastomer. Rubber chemicals, as defined herein, include one or more of the following: processing aids (e.g., various oils and plasticizers, waxes, which provide ease of mixing and processing of the rubber), activators (e.g., zinc oxide and fatty acids, which activate the vulcanization process), accelerators (e.g., sulfenamides and thiazoles, which accelerate the vulcanization process), vulcanizing agents (or curatives that crosslink the rubber, e.g., sulfur, peroxides), and other rubber additives, such as, but not limited to, retarders, co-agents, peptizers, adhesion promoters, tackifiers, resins, flame retardants, colorants, and blowing agents. Optionally, rubber chemicals can include processing aids and activators. Alternatively, the one or more other rubber chemicals are selected from zinc oxide, fatty acids, zinc salts of fatty acids, waxes, accelerators, resins, and processing oils.
[0250] In a typical dry mixing process, one or more rubber chemicals (e.g., processing aids) are charged early in the mixing cycle to aid in the incorporation of the filler. Thus, while rubber chemicals can be essential, they can still interfere with the bonding or interaction between the filler and the surface of the elastomer and have a negative impact on the properties of the vulcanized rubber. It has been discovered that the use of a wetting filler allows the filler to be mixed into the solid elastomer in the absence or substantial absence of such rubber chemicals. While not wishing to be bound by any theory, it is believed that the presence of the wetting filler eliminates the need for rubber chemicals early in the mixing cycle, or at any point in the mixing cycle, because the liquid enables and improves the incorporation of the filler into the solid rubber.
[0251] Thus, optionally, the method includes charging a solid elastomer and a wet filler into a mixer, and mixing the solid elastomer and the wet filler in one or more mixing steps in the substantial absence of rubber chemicals at a mixer temperature controlled by at least one temperature control means to form a mixture. Optionally, the process further includes adding at least one additive selected from antidegradants and coupling agents during the charging or mixing, i.e., during the one or more mixing steps. Examples of such antidegradants (e.g., antioxidants) and coupling agents are described herein.
[0252] In this process option, during at least one of the mixing steps, and preferably during one mixing step, the mixer reaches a designated temperature of 120°C or higher, e.g., at least 125°C or higher, at least 130°C or higher, at least 135°C or higher, at least 140°C or higher, at least 145°C or higher, or at least 150°C or higher. This designated temperature can be measured by a temperature-measuring device within the mixing cavity. The designated temperature of the mixer can be the same as the maximum temperature of the mixture or composite reached during the mixing stage (which can be determined by removing the composite from the mixer and inserting a thermocouple or other temperature-measuring device into the composite), or can differ from the maximum temperature by no more than 30°C, or no more than 20°C, or no more than 10°C (or no more than 5°C, or no more than 3°C, or no more than 2°C). In this mixing method, optionally, one or more rubber chemicals can be added to the mixer once the mixer reaches a temperature of 120°C or higher. In other embodiments, the specified temperature can be in a range of 120°C to 190°C, 125°C to 190°C, 130°C to 190°C, 135°C to 190°C, 140°C to 190°C, 145°C to 190°C, 150°C to 190°C, 120°C to 180°C, 125°C to 180°C, 130°C to 180°C, 135°C to 180°C, 140°C to 180°C, 145°C to 180°C, 150°C to 180°C, 120°C to 170°C, 125°C to 170°C, 130°C to 170°C, 135°C to 170°C, 140°C to 170°C, 145°C to 170°C, 150°C to 170°C, etc. One or more rubber chemicals can be added at a specified temperature of 120°C or higher; at this point, the filler is distributed and kneaded into the elastomer, and the addition of the rubber chemicals is not expected to interfere with the interaction between the filler and the elastomer.
[0253] In this process option, the loading step and one or more mixing steps are carried out in the absence or substantial absence of one or more rubber chemicals before the mixer reaches the specified temperature. As defined herein, "substantially absent" refers to a process in which the loading step and one or more mixing steps can be carried out in the presence of one or more rubber chemicals in an amount of less than 10% by weight of the total amount of rubber chemicals ultimately provided by the composite, e.g., a vulcanized rubber prepared from the cured composite, or in which the loading step and one or more mixing steps can be carried out in an amount of less than 5% or less than 1% by weight of the total amount of rubber chemicals ultimately provided by the composite. Because the inclusion of rubber chemicals in the composite is optional, a suitable measure for determining the "substantial absence" of one or more rubber chemicals is to determine the targeted amount in the vulcanized rubber prepared from the composite, e.g., after curing the composite. Thus, a nominal amount of one or more rubber chemicals may be added during the loading or mixing step, but this is not an amount sufficient to interfere with filler-elastomer interaction. As a further example of "substantially absent," the charging and mixing may be carried out in the presence of one or more rubber chemicals in an amount or loading of 5 phr or less, 4 phr or less, 3 phr or less, 2 phr or less, 1 phr or less, or 0.5 phr or less, 0.2 phr or less, 0.1 phr or less, based on the resulting vulcanizate. Alternatively, the one or more rubber chemicals are absent (0 phr) in the composite material delivered in step (d).
[0254] The composite material as it leaves the mixer contains filler dispersed in the elastomer at a loading of at least 1 phr, e.g., at least 20 phr, with no more than a 10% filler yield loss. By this process, the composite material as it leaves the mixer is free or substantially free of one or more rubber chemicals, except for any stabilizing agents that may be present, for example, at the start of mixing. Alternatively, the composite material as it leaves the mixer can contain at least one additive selected from stabilizing agents and coupling agents, which can be added at any point during charging or mixing. Alternatively, the composite material as it leaves the mixer can contain or be substantially free of any rubber chemicals, for example, if one or more stabilizing agents are not added at the start of the mixing process. Alternatively, the mixture can alternatively consist essentially of or consist of the solid elastomer and the wet filler. Alternatively, the mixture can consist essentially of or consist of the solid elastomer, the wet filler, and at least one stabilizing agent. Alternatively, the mixture consists of or consists essentially of a solid elastomer, a wetting filler, at least one antidegradant, and a coupling agent.
[0255] In any of the embodiments disclosed herein, optionally, after initiating mixing of at least the solid elastomer and the wet filler and before the discharging step, the method can further include adding at least one stabilizing agent to the mixer so that the at least one stabilizing agent is mixed with the solid elastomer and the wet filler. The optional addition of the stabilizing agent(s) can occur at any time before the discharging step. For example, the addition of the stabilizing agent(s) can occur before the composite is formed and has a liquid content of 10 wt% or less, or 5 wt% or less. An example of an stabilizing agent that can be introduced is N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD), and others are described in other sections of this specification. The antidegradant can be incorporated in an amount ranging from 0% to 5%, 0.5% to 5%, 1% to 5%, 0% to 3%, 0.5% to 3%, 1% to 3%, 0% to 2%, 0.5% to 2%, or 1% to 2%, based on the weight of the composite being formed. Antidegradants added during the charging or mixing step may help prevent elastomer degradation during mixing; however, due to the presence of liquid in the mixture, the rate of elastomer degradation is slower compared to dry mixing processes, and the addition of the antidegradant can be delayed.
[0256] At least one additive can be included during the mixing method described herein or after the composite is formed. The at least one additive can include a curative package or at least one curative. To make a vulcanizable composite, the added curative package can include a crosslinker and optional activators and accelerators. When sulfur is used as the crosslinker, typical activators include zinc oxide and / or stearic acid, and typical accelerators include sulfenamides, such as N-tert-butyl-2-benzothiazole sulfenamide (TBBS) and N-cyclohexyl-2-benzothiazole sulfenamide (CBS). Other curatives used in rubber processing include peroxides, urethane crosslinkers, metal oxides, acetoxysilane compounds, phenolic resins, and the like. Additional suitable ingredients for sulfur-based systems and other crosslinking systems are well known to those skilled in the art.
[0257] Other rubber chemicals include antioxidants, processing aids, extender oils, waxes, various resins, coupling agents, and additional antidegradants. Antioxidants include N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD) and those listed in WO2012 / 037244, the disclosure of which is incorporated herein by reference.
[0258] Optionally, rubber chemicals can be combined with the composite in a mechanical mixer. Specifically, additives such as fillers (which may be the same or different from the fillers used in the mixer; exemplary fillers include silica, carbon black, and / or zinc oxide), other elastomers, other or additional masterbatches, anti-degradants (e.g., antioxidants), coupling agents, plasticizers, processing aids (e.g., stearic acid, which can also be used as curatives, liquid polymers, oils, waxes, etc.), resins, flame retardants, extender oils, and / or lubricants, and mixtures of any thereof, can be added in the mechanical mixer. Additional elastomers are combined with the composite to produce an elastomeric compound. Suitable elastomers include any of the elastomers utilized in the mixing processes previously described. Illustrative elastomers include, but are not limited to, rubber, 1,3-butadiene, styrene, isoprene, isobutylene, 2,3-dialkyl-1,3-butadiene (where alkyl is methyl, ethyl, propyl, etc.), acrylonitrile, polymers of ethylene, propylene (e.g., homopolymers, copolymers, and / or terpolymers), etc. The antidegradants (examples of antidegradants) can be amine-type antidegradants, phenol-type antidegradants, imidazole-type antidegradants, metal salts of carbamates, para-phenylenediamine(s) and / or dihydrotrimethylquinoline(s), polymerized quinine antidegradants, and / or other antidegradants used in wax and / or elastomer recipes.Specific examples include, but are not limited to, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6-PPD, e.g., ANTIGENE 6C available from Sumitomo Chemical Co., and NOCLAC 6C available from Ouchi Shinko Chemical Industrial Co.), "Ozonon" 6C from Seiko Chemical Co., polymerized 1,2-dihydro-2,2,4-trimethylquinoline (TMQ, e.g., Agerite Resin D available from RT Vanderbilt), 2,6-di-t-butyl-4-methylphenol (available as Vanox PC from Vanderbilt Chemicals LLC), butylhydroxytoluene (BHT), and butylhydroxyanisole (BHA). Other representative antidegradants may be, for example, diphenyl-p-phenylenediamine and others such as those disclosed in The Vanderbilt Rubber Handbook (1978), pp. 344-346.
[0259] mixer Specific types of internal mixers are Banbury mixers or Brabender mixers, either of which can be used in the methods of forming composite materials described herein. The internal mixer can be a tangential internal mixer. The internal mixer can be an intermeshing internal mixer. Other mixers include kneading-type internal mixers. Commercially available internal mixers from Farrel-Pomini, Harburg Freudenberger Maschinenbau GmbH (HF), Kobelco, or Pelmar Eng'r can be used. In addition to or instead of the option of using an internal circuit of steam, water, or other liquid in the rotor, the internal mixer can also have a cooling or heating jacket on one or more areas or parts of the mixing chamber to control the temperature of the ingredients being mixed therein. This can create one or more heating / cooling zones in the wall or part of the wall of the mixer. The mixer can be a single-stage mixer or a multi-stage mixer (e.g., two or more stages). Examples of mixers and designs that can be utilized are described in EP 2423253 B1 and US Pat. No. 7,556,419, the disclosures of which are incorporated herein by reference.
[0260] Alternatively, the mixer can be a continuous mixer. For example, the solid elastomer and wet filler may be mechanically worked by using one or more continuous internal mixers, twin-screw extruders, single-screw extruders, or roll mills, such as those described in U.S. Pat. No. 9,855,686 B2, the disclosure of which is incorporated herein by reference. Suitable kneading and mastication devices are well known and commercially available, including, for example, Unimix continuous mixers and MVX (Mixing, Venting, eXtruding) equipment from Farrel Pomini (Ansonia, Connecticut), FCM™ Farrel continuous mixers, long continuous mixers from Pomini, Pomini continuous mixers, twin-rotor co-rotating intermeshing extruders, twin-rotor counter-rotating non-intermeshing extruders, continuous compounding extruders, twin-screw kneading extruders manufactured by Kobe Steel, and Kobe continuous mixers. Alternative mastication equipment suitable for use in one or more embodiments disclosed herein will be familiar to those skilled in the art.
[0261] The mixing is carried out in a mixer(s) having at least one rotor, and the mixer can be one or more of the following: a kneader, a roll mill, a screw extruder, a twin-screw extruder, a multi-screw extruder, a continuous compounder, and / or a twin-screw extruder.
[0262] The mixing is carried out in a mixer(s) having at least one rotor, and the mixer can have a two-blade rotor, a four-blade rotor, a six-blade rotor, an eight-blade rotor, and / or one or more screw rotors.
[0263] Post-processing The output composite material can be subjected to one or more post-processing steps. Post-processing can be performed after any mixing step. For multi-stage mixing, post-processing can be performed after the first stage and / or after the second stage, etc. The composite material is post-processed to provide a composite material that is dried, homogenized, extruded, rolled, milled, etc. The one or more post-processing steps can shape or form or allow for improved handling, but preferably do not substantially disperse the filler. For example, the one or more post-processing steps can impart at most a small amount of energy, e.g., less than 300 kJ / kg composite, less than 200 kJ / kg composite, less than 100 kJ / kg composite, or less than 50 kJ / kg composite. For example, the one or more post-processing steps do not result in a significant temperature increase of the composite material (as a result of the low energy input).
[0264] Optionally, the liquid content of the delivered composite material can be 10 wt. % or less (e.g., 5 wt. % or less) as delivered, and this liquid content can be further reduced by one or more additional liquid (e.g., water) removal steps, such as further mixing step(s), blending step(s), application of heat, or use of a dryer or other means to remove moisture or liquid from the mixture, to achieve a desired liquid content of the composite material that is lower than the liquid content as delivered from the mixer. Generally, the post-treatment step can include compressing the composite material to remove from 1 wt. % to about 50 wt. %, e.g., 1 wt. % to about 10 wt. %, of the remaining liquid phase, based on the total weight of the composite material.
[0265] In any of the methods of making a composite material disclosed herein, the method may further include one or more of the following steps after forming the composite material: - 1 or more holding steps; - one or more drying steps which can be used to further dry the composite material to obtain a dried composite material; - one or more extrusion processes; - 1 or more rolling processes; - one or more grinding steps to obtain a ground composite material; - one or more granulation steps; - 1 or more cutting steps; - one or more bailment steps to obtain a bailed product or mixture; The scraped mixture or product may be broken up to form a granulated mixture; and / or - one or more mixing or blending steps; and / or -1 or more sheet ejection processes.
[0266] The one or more processing steps can be accomplished by one or more internal mixers, kneaders, roll mills, screw extruders, twin screw extruders, multi-screw extruders, continuous compounders, and / or twin screw delivery extruders fitted with roller dies (e.g., twin screw sheeters) or fixed blades.
[0267] By way of further example, after formation of the composite material, the following steps may be performed in the following order, each of which may be repeated any number of times (in the same or different circumstances): - one or more holding steps to develop further elasticity; - one or more cooling steps; - Further drying the composite material to obtain a further dried composite material; -mixing or blending the composite materials to obtain a blended mixture; - milling the compounded mixture (e.g. roll milling) to obtain a milled mixture; - granulating the milled mixture; Optionally scraping the mixture after granulation to obtain a scraped mixture; Optionally breaking up and mixing the scraped mixture.
[0268] Optionally, the composite material can be further processed in an open mill. The composite material can be discharged from the continuous compounder or extruder as a long extrudate and cut into shorter lengths before entering the open mill. Optionally, the composite material is fed to the open mill by a conveyor. The conveyor can be a conveyor belt, conduit, pipe, or other suitable means for transporting the composite material from the continuous compounder to the open mill. The open mill can be equipped with roller pairs, which can be optionally heated or cooled, to provide enhanced operation of the open mill. Other operating parameters of the open mill include the gap distance between the rolls, the bank height, i.e., the accumulation of material in the gap between the rolls and at their apexes, and the speed of each roll. The speed of each roll and the temperature of the liquid used to cool each roll can be controlled independently for each roll. The gap distance can be from about 3 mm to about 10 mm or from about 6 mm to about 8 mm. The roll speed can be from about 15 rpm to about 70 rpm, and the rollers can rotate toward each other relative to the inlet side of the mill. The friction ratio, which is the ratio of the speed of the collection roller, e.g., the roller on which the masticated product is collected, to the speed of the back roller, can be from about 0.9 to about 1.1. The liquid used to cool the rollers can be from about 35°C to about 90°C, e.g., from about 45°C to about 60°C, from about 55°C to about 75°C, or from about 70°C to about 80°C. In addition to controlling the operation of the open mill to provide the desired level of mastication and dry storage of the masticated product, it is desirable that the discharge of the open mill be collected as a smooth sheet on the collection roller. The residence time of the composite material in the mill can be determined in part by the roller speed, gap distance, and the desired amount of mastication and drying, and can be from about 10 minutes to about 20 minutes for already masticated material, for example, in a twin-rotor continuous mixer.
[0269] Those skilled in the art will recognize that various combinations of devices may be utilized. Depending on which devices are used, it may be desirable to operate them under conditions different from those described above in order to provide the material with a greater amount of work and / or additional dry storage. In addition, it may be desirable to utilize two or more of a particular type of device, such as an open mill or an internal mixer, in series, or to pass the masticated product through a given device more than once. For example, the composite material may be passed through two, three, or more open mills, or may be passed through two, three, or more open mills in series. In the latter case, it may be desirable to operate each open mill under different operating conditions, such as speed, temperature, different (e.g., higher) energy input, etc. After being mixed in the internal mixer, the composite material may be passed through one, two, or three open mills.
[0270] combination Additionally or alternatively, the composite material can be compounded with one or more stabilizing agents, rubber chemicals, and / or curatives and vulcanized to form a vulcanized rubber. Such vulcanized compounds can have one or more improved properties, such as, but not limited to, one or more improved rubber properties, such as, for example, improved hysteresis, abrasion resistance, and / or rolling resistance in tires, or improved mechanical strength and / or tensile strength, or improved tan δ and / or improved tensile stress ratio.
[0271] For example, in a compounding step (which can also be the initial mixing step), the components of the curative package, except for the sulfur or other crosslinking agent and accelerator, are combined with the neat composite in a mixing device (non-curatives, such as rubber chemicals and / or antidegradants, are often premixed and are collectively referred to as "smalls"). The most common mixing devices are internal mixers, such as Banbury or Brabender mixers, although other mixers, such as continuous mixers (e.g., extruders), may also be utilized. Subsequently, in a compounding step, the crosslinking agent, such as sulfur, and accelerators (if necessary) (collectively referred to as curatives) are added. This compounding step is often performed in the same type of equipment as the mixing step, but may be performed on a different type of mixer or extruder or roll mill. Those skilled in the art will recognize that once the curatives have been added, the vulcanization process begins once the appropriate activation conditions for the crosslinking agents have been achieved. Therefore, when sulfur is used, it is preferable to maintain the mixing temperature substantially below the curing temperature.
[0272] As an option, any method of preparing a composite material disclosed herein involves adding any rubber chemicals late in the composite formation process or avoiding adding rubber chemicals at any point in the composite formation process. Regarding the latter option, the rubber chemicals can be added to the composite material during the compounding stage. For example, the rubber chemicals can be added after the temperature of the composite material reaches 120°C or higher, e.g., 130°C or higher, or 140°C or higher. Alternatively, the rubber chemicals can be added during one or more compounding steps or after the composite material is discharged from the initial mixing step(s) that form the composite. Regarding this option, adding rubber chemicals too early in the initial mixing step(s) can interfere with the degree of contact between the rubber and the filler, which in turn can lead to overall poor filler dispersion and / or poor rubber-filler interaction in the composite material. For example, in some scenarios, adding rubber chemicals too early in the mixing process, compared to adding them after the composite temperature has reached 120°C or higher (e.g., 130°C or higher or 140°C or higher) or adding them during one or more compounding steps, can lead to a vulcanizate that exhibits lower tensile properties, such as a lower tensile stress ratio (M300 / M100), and poor filler dispersion. In certain cases, such undesirable effects of rubber chemicals when added too early can be observed when the elastomer is, for example, natural rubber or contains natural rubber.
[0273] Composition and vulcanization Traditionally, reinforcement (e.g., stiffness) in elastomer composites can be increased by increasing the loading, surface area, and structure of the filler material. The final mechanical properties of the composite can also be determined by how the particles are dispersed and positioned in the composite. In tests performed on composites prepared by this process and the resulting vulcanizates, it was discovered that certain dispersion conditions achieved the desired mechanical properties of the resulting vulcanizates.
[0274] The filler distribution and degree of dispersion ("state of dispersion" or "state of dispersion" or macrodispersion) in the elastomer network for both composites and vulcanized rubbers can be examined by optical microscopy in transmission mode on microtome sections of the composite (e.g., 2 μm or less in thickness, e.g., 0.5 μm to 2 μm, 0.5 μm to 1.5 μm, approximately 1 μm). Optical images of microtome sections (transmission mode) typically show a light background populated with dark objects, each of which is the result of a collection of carbon black agglomerates. Because the image is viewed in two-dimensional space, each dark object covers an area that can be likened to a type of "particle." (With respect to macrodispersions, the term "particle" is intended to represent the area coverage of the carbon black agglomerates and is to be distinguished from "primary particles" that form single carbon black agglomerates, which have dimensions on the order of 0.1 μm, which is below the resolution of optical microscopy.) This particle "diameter" is defined herein as the "area-equivalent diameter" of the filler and is typically in the micron size range. The dispersion state is therefore indicated by the shape of the particle size distribution, either in terms of particle area coverage or the number of particles per unit area of a particular size.
[0275] For composite materials, the state of filler distribution and dispersion in elastomers can also be assessed at the micron and sub-micron level ("microdispersion") and manifested by rheological properties, such as those measured by a rubber testing apparatus (RPA).
[0276] RPA is a tool for analyzing the rheological properties of elastomeric materials, such as the composite materials described herein, by subjecting the material to a strain sweep. Strain sweep testing subjects a material to a series of strain amplitudes and observes behavior known as the "Payne effect," which is thought to be a measure of microdispersion. One way to assess such an effect is to measure the dynamic storage modulus, G', at low and high strains, the ratio of which is defined as the "Payne ratio." The Payne effect can also be affected by rubber chemical loading and rubber molecular weight.
[0277] Composites prepared by the present process can be compared to composites prepared from a dry blending method (dry filler and dry elastomer). By doing so, distinct rheological behavior can be determined. At similar levels of reinforcement, any of the methods disclosed herein can achieve composites with a lower Payne effect, as determined by G' or G'(50%) measured at 50% strain amplitude, compared to a dry blending method or a comparative wet blending process (e.g., a comparative process combining a wet filler with a solid elastomer). A lower Payne effect has been found to indicate desirable properties in the final product, such as tire rolling resistance. Meanwhile, at similar levels of Payne effect, any of the methods disclosed herein can provide composites with higher reinforcement, G'(50%), than those achieved by a dry blending method or a comparative wet blending process in which a wet filler and a solid elastomer are combined.
[0278] It has been discovered that the composite materials prepared by this process achieve the following relationship or formula: Payne ratio≦0.1*G'@50%-y (where the Payne ratio is G'(0.1%) / G'(200%), G'(0.1%) is the dynamic storage modulus measured at 0.1% strain amplitude, G'(200%) is the dynamic storage modulus measured at 200% strain amplitude, and G'(50%) is the dynamic storage modulus measured at 50% strain amplitude, these dynamic storage moduli measured at 100°C and a frequency of 1 Hz, and y is a number in the range of 7 to 10.)
[0279] This relationship is not achieved by composites made by the dry blending method or the comparative wet blending process.
[0280] Additionally, composite macrodispersion can be assessed by optical microscopy of microtome sections, as discussed above. Indicators of macrodispersion, such as particle size distribution, weighted area, and area percentage of filler particles larger than 2 μm, can be obtained. By any of the methods disclosed herein, composites can be made in which there is a small number of large particles compared to the total area, which characterizes the distribution of fillers, such as carbon black, in the elastomer. Optionally, the dispersion can be assessed by measuring the "d" in the distribution. 90 Alternatively, the dispersion state can be measured by the "area contribution (%) of particles > 2 μm." The area contribution from particles can be reported in terms of image area. The total image area (μm 2 ) can be determined from the number of pixels and the image resolution. An image can have width and height dimensions, each reported in number of pixels, and the corresponding area is (pixels) 2 In terms of area, the resolution can be reported as (μm / pixel) 2 The image area can be reported as the product of: (area)*(resolution).
[0281] In certain embodiments, the filler has a state of dispersion in the elastomer according to the following formula: A≦1.25*B+x (In the formula: A is the area equivalent diameter (μm) of the filler particles in the composite material. 90 and B is [total area of particles with area equivalent diameter ≥ 2 μm] / [total image area] × 100% where B≧1%; A and B are determined by light microscopy in transmission mode on microtome sections, and (x is a number ranging from 15 to 20).
[0282] As mentioned elsewhere, 90% (d 90) can have an area-equivalent diameter of less than 1.25B+x. This relationship allows the composite to have a dispersion characterized by a reduced number of large particles compared to composites prepared by dry mix and comparative wet mix methods.
[0283] Certain embodiments provide composite materials having: (A) better microdispersion characteristics than composites made by prior methods combining dry filler and solid elastomer, and (b) macrodispersion characteristics that are distinctly different from liquid masterbatches and comparative wet mixing processes (combining wet filler and solid elastomer). As noted elsewhere, the combination of microdispersion and macrodispersion characteristics or signatures of at least some of the composite materials disclosed herein is unique and not found in prior composite materials.
[0284] Various composite materials can be produced from one or more of the methods disclosed herein. For example, a particular composite material disclosed herein contains an elastomer, which includes or can include at least 50% (by weight) natural rubber. The composite further includes a filler dispersed in the natural rubber (or dispersed in the elastomer). The filler can include or can include carbon black.
[0285] Thus, disclosed herein is a composite material having the following properties: (a) The filler is dispersed in natural rubber according to formula (1): A≦1.25*B+x (1) (In the formula: A is the area equivalent diameter (μm) of the filler particles in the composite material. 90 and B is [total area of particles with area equivalent diameter ≥ 2 μm] / [total image area] × 100% where B≧1%; A and B are determined by light microscopy of microtome sections, and x is a number ranging from 15 to 20; and (b) The composite material has properties according to equation (2): G'(0.1%) / G'(200%)≦0.1*G'(50%)-y (2) (where G'(0.1%) is the dynamic storage modulus measured at 0.1% strain amplitude, G'(200%) is the dynamic storage modulus measured at 200% strain amplitude, G'(50%) is the dynamic storage modulus measured at 50% strain amplitude, the dynamic storage moduli measured at a frequency of 1 Hz and 100°C, and y is a number in the range of 7 to 10).
[0286] The carbon black can be any carbon black previously described herein.
[0287] The variables x and y in the above formula can be integers or decimals (e.g., x can be 15, 16, 17, 18, 19, or 20, or 15.1, 15.2, 15.3, and the like for x, and / or y can be 7, 8, 9, or 10, or 7.1, 7.2, 7.3, and the like for y).
[0288] Optionally, the carbon black present in the composite material has a content of at least 60m 2 / g STSA, e.g. 60m 2 / g~210m 2 / g or 70m 2 / g~210m 2 / g, or 80m 2 / g~210m 2 / g, or 90m 2 / g~210m 2 / g, or 100m 2 / g~210m 2 / g, etc.
[0289] Alternatively, the carbon black present in the composite material can have a COAN of at least 75 mL / 100 g, for example, from 75 mL / 100 g to 150 mL / 100 g, from 85 mL / 100 g to 150 mL / 100 g, from 95 mL / 100 g to 150 mL / 100 g, or from 105 mL / 100 g to 150 mL / 100 g.
[0290] Alternatively, the composite material can have a carbon black loading of 60 phr or less, for example, 50 phr or less, or 40 phr or less, or 30 phr or less, or 20 phr or less, or 1 phr to 60 phr, or 5 phr to 60 phr, or 10 phr to 60 phr.
[0291] Alternatively, the carbon black present in the composite can have a BET / STSA ratio in the range of 1 to 1.2, such as a BET / STSA ratio of 1 to 1.15, 1 to 1.1, or 1 to 1.05.
[0292] Optionally, with respect to the total filler amount in the composite, the carbon black can be present in an amount of at least 50% by weight, based on the total weight of fillers, such as at least 60%, at least 70%, at least 80%, at least 90%, at least 99%, or 100% by weight, based on the total weight of fillers, for example, 50% to 100% or 60% to 95% by weight. The carbon black can be the sole filler or can be the predominant filler by weight.
[0293] Optionally, the filler is predominantly carbon black, but the composite can have silica present where the filler is comprised of a blend of carbon black and silica, e.g., a blend of 90 wt% or more carbon black and 10% or less silica.
[0294] Alternatively, the elastomer contains at least 50 wt% natural rubber, based on the total weight of the elastomer. This amount can be at least 75 wt%, at least 90 wt%, at least 95 wt%, or 100 wt% natural rubber. This alternative can be combined with carbon black, comprising at least 50 wt% carbon black, based on the total weight of the filler.
[0295] Also disclosed herein are vulcanized rubbers prepared from the composite materials disclosed herein. The vulcanized rubbers contain or can include a filler (as described herein) dispersed in an elastomer that is or includes natural rubber, such as a blend of natural rubber and polybutadiene rubber and / or styrene-butadiene rubber. The filler can contain or include or be carbon black. The carbon black can be the carbon black described herein above.
[0296] In vulcanized rubber composites containing carbon black, electrical resistivity measurements can be used to characterize the state of microdispersion. Electrical resistivity depends on, among other factors, the carbon black loading and its specific surface area and structure. To apply electrical resistivity to characterize carbon black microdispersions, it is normalized via the parameter δ, which takes into account the carbon black loading, particle size, and structure. This parameter represents the theoretical average spacing between agglomerates in a filled rubber system, assuming monodisperse particle size and perfect random particle dispersion (MJ. Wang, S. Wolff, and EH Tan, Rubber Chemistry and Technology, 1993, Vol. 66, p. 178).
[0297] For vulcanized rubber, a macrodispersion is defined as a dispersion of particles having an area-equivalent diameter of at least 4 μm, determined by optical microscopy on microtome sections, with a parameter ν of 1 mm 2The area measurement is determined by the number of hits. As discussed above, each "particle" is defined by the area coverage of the dark object as seen in the optical image. In vulcanized materials, the area measurement results can be distorted by a small number of very large non-carbon black entities, e.g., other compounding ingredients such as ZnO. Therefore, the approach here is the use of particle number (and removal of the contribution of a single large particle) rather than area to define the total undispersed area, which is actually believed to represent a characteristic attribute for the vulcanized material.
[0298] Certain embodiments provide vulcanized rubber that can have at least carbon black present as a filler, and the carbon black has a viscosity of at least 60 mPa.s. 2 / g STSA and a BET / STSA ratio in the range of 1 to 1.2; and the vulcanizate has resistivity and dispersivity properties that satisfy equation (3): [ln(R)-3.8] / [0.28*δ]≧0.0004*ν+0.9 (3) (In the formula: R is the resistivity (ohm·cm); δ=(6000·[0.806·φ -1 / 3 β -1 / 3 -1] / ρS)×β 1.43 where: φ = volume fraction of carbon black in the composite, S = BET surface area of carbon black (m 2 / g), ρ = carbon black density, 1.8 g / cm 3 It is estimated that β=φ eff / φ, φ eff is the effective volume fraction of carbon black, taking into account the occluded rubber, calculated from: φ eff = φ[1 + (0.0181 * COAN)] / 1.59, where COAN is the compression oil absorption of the carbon black determined by ASTM D3493; and ν≧65, where ν is the number of particles / mm with an area-equivalent diameter of at least 4 μm as determined by optical microscopy in transmission mode on microtome sections. 2 (The numerical value is .)
[0299] For this vulcanized rubber, carbon black is 60m 2 / g~210m 2 / g, or 60m 2 / g~190m 2 / g range.
[0300] For this vulcanizate, the carbon black may have a COAN of at least 75 mL / 100 g.
[0301] For this vulcanizate, the vulcanizate may have a carbon black loading of up to 60 phr.
[0302] For this vulcanizate, the filler may comprise or contain carbon black in an amount of at least 50% by weight based on the total weight of the fillers, or at least 90% by weight based on the total weight of the fillers, or at least 99% by weight based on the total weight of the fillers. The filler may be the only carbon black or may be the predominant filler by weight present.
[0303] For this vulcanizate, the filler may also include silica.
[0304] With respect to the vulcanized rubber, the vulcanized rubber can have one or more elastomeric properties. For example, the vulcanized rubber can have a tensile stress ratio M300 / M100 of at least 5.9, e.g., at least 6.0, at least 6.1, at least 6.2, when evaluated according to ASTM D412, where M100 and M300 refer to the tensile stress at 100% and 300% elongation, respectively.
[0305] Alternatively or additionally, the vulcanizate may have a maximum tan δ(60° C.) of not greater than 0.22, such as not greater than 0.21, or not greater than 0.2, not greater than 0.19, or not greater than 0.18.
[0306] Also disclosed herein is a method for making vulcanized rubber. The method can include at least curing the composite material in the presence of at least one curative. Curing can be accomplished by applying heat, pressure, or both, as known in the art.
[0307] Generally, the resistivity properties of vulcanized rubber containing at least 50% carbon black (e.g., at least 75% carbon black, or at least 90% carbon black) made with the present composites have been found to be higher than those of comparable vulcanized rubbers made by a dry-mix process (dry-mixed equivalents) for a given filler, loading (e.g., ±5 wt%, ±2 wt%), elastomer type, and compound recipe. Such resistivity properties are measured using the resistivity index ln(R) index The ln(R) value is expressed as the ratio of the ln(R) value of the vulcanized rubber prepared from the composite materials disclosed herein compared to the ln(R) value of its dry-mixed counterpart.
[0308] An index greater than 100 indicates that the vulcanizate has greater electrical resistivity than its dry-mixed counterpart of similar composition. For example, the vulcanizate may have a resistivity index of at least 105, at least 110, or at least 120, indicating an ln(R) greater than its dry-mixed counterpart by at least 5%, at least 10%, and at least 20%. Alternatively, the vulcanizate may have a resistivity index in the range of 105-170, 110-170, 120-170, or 130-170.
[0309] Another useful metric is the Payne difference, which is calculated from the difference between the dynamic storage modulus (G') at 0.1% strain and G' at 200% strain, i.e., G'(0.1%) - G'(200%).
[0310] The Payne Difference of the composite can be normalized to that of a corresponding composite made by a dry blending process. This result is called the Payne Diff Index. An index greater than 100 indicates that the composite has a lower Payne Difference value than the corresponding dry-blended equivalent composite, e.g., with the same filler type (e.g., carbon black, silica, etc.), filler loading (e.g., ±5 wt%, ±2 wt%), elastomer type, and compound recipe. Payne Difference is a measure of the state of the filler network in the elastomer. A lower Payne Difference Index indicates a better distributed and less connected network of filler particles. Such improved distribution is generally considered favorable for lower dynamic loss (e.g., tan δ) in the resulting rubber.
[0311] For example, the present composites, in which the filler contains at least 50 wt% silica, based on the total weight of the filler (e.g., the filler is at least 50 wt% silica, at least 75 wt% silica, or at least 90 wt% silica), can exhibit improved rheological properties compared to composites made with their dry-blended counterparts. Accordingly, composites, such as those prepared by the present methods, having a Payne Difference Index of at least 105, at least 110, at least 120, at least 130, at least 140, or at least 150 are disclosed herein. For example, a Payne Difference Index of at least 140 or at least 150 represents a Payne Difference value that is 40% lower or 50% lower than the corresponding composite prepared with its dry-blended counterpart (filler type, loading, elastomer type, and compound recipe). Alternatively, the composite material has a Payne Difference Index in the range of 105-180, 110-160, 120-160, or 130-160.
[0312] Payne Difference can also be a metric for composites containing carbon black and natural rubber prepared by the methods disclosed herein. For example, the following relationship is observed: Pain difference ≦ 13.5 * G' (50%) - s where Payne difference is G'(0.1%) - G'(200%), G'(0.1%) is the dynamic storage modulus measured at 0.1% strain amplitude, G'(200%) is the dynamic storage modulus measured at 200% strain amplitude, and G'(50%) is the dynamic storage modulus measured at 50% strain amplitude, these dynamic storage moduli measured at a frequency of 1 Hz and 100°C, and "s" is a number in the range of 1950 to 2100.
[0313] This relationship indicates an improvement in Payne difference over comparative wet and dry mix processes, which in turn may contribute to the improved hysteresis behavior of vulcanizates made from such composites.
[0314] Vulcanized rubbers prepared from the present composites (e.g., made by any of the disclosed processes between wet fillers and solid elastomers, whether single-stage or multi-stage, under the disclosed mixing conditions of Tz, loading, tip speed, continuity, and rubber chemical addition order selection) can exhibit improved properties. For example, vulcanized rubbers prepared from the present composites can have improved properties over vulcanized rubbers prepared from composites made by dry mixing of solid elastomers and non-wetting fillers ("dry-mix composites"), particularly those dry-mix composites having the same composition ("dry-mix equivalents"). Thus, this comparison is made between the dry-mix and present mixing processes, with equivalent fillers, elastomers, filler loadings (e.g., ±5 wt%, ±2 wt%), and compound recipes, and optionally, curative additives. Under these conditions, the vulcanized rubbers have tan δ values that are less than the tan δ values of vulcanized rubbers prepared from dry-mix composites having the same composition. Additionally or alternatively, the vulcanizate has a tensile stress ratio M300 / M100 that is greater than the tensile stress ratio of a vulcanizate prepared from a dry-mix composite material having the same composition, where M100 and M300 refer to the tensile stresses at 100% and 300% elongation, respectively.
[0315] In certain embodiments, vulcanized rubbers prepared from composites made by a multiple mixing step or multi-stage process have improved properties over vulcanized rubbers prepared from composites made by a single mixing step or single-stage process. As previously described, vulcanized rubbers prepared from the present composites by a single mixing step having a liquid content of 10% or less, or 5% or less, or other low levels as disclosed herein have improved properties over dry-mix composites. In certain cases, these properties can be further improved by one or more additional mixing steps or stages. For example, vulcanized rubbers prepared by a multi-stage (e.g., two-stage) or multi-step (e.g., two-stage) process have lower tan δ values than vulcanized rubbers prepared from composites made by a single-stage or single-stage process, such as the mixture delivered in step (c) disclosed herein. In another example, the vulcanizate prepared by a multi-stage (e.g., two-stage) or multi-step (e.g., two-mixing) process has a tensile stress ratio M300 / M100 greater than that of the vulcanizate prepared from the mixture delivered in step (c), where M100 and M300 refer to the tensile stresses at 100% and 300% elongation, respectively. If the filler is silica, in this particular case, the Payne Difference Index is lower for composites prepared by a multi-stage (e.g., two-stage) or multi-step (e.g., two-mixing) process compared to composites prepared by a single-stage or single-step process.
[0316] While any filler or combination of fillers is possible in any of the methods disclosed herein, certain beneficial properties (or rubber properties) can be achieved when the filler is or includes carbon black (e.g., reinforcing carbon black) or silicon-treated carbon black, for example, when carbon black is the only filler present or the primary filler used (e.g., when more than 50 wt%, e.g., more than 60 wt%, more than 70 wt%, more than 80 wt%, or more than 90 wt% of all fillers used is carbon black). For example, significant property improvements can be obtained for tan δ (e.g., tan δ 60°C) and / or tensile stress at 300% and 100% elongation (M300 and / or M100), and / or tensile stress ratio (M300 / M100).
[0317] Certain combinations of filler and elastomer are also effective in achieving improved properties. For example, the filler can be or contain carbon black, and the elastomer can be or contain natural rubber. By way of example, carbon black can be dispersed in natural rubber at loadings ranging from 40 phr to 65 phr, or other loadings described herein. Carbon black can be dispersed in natural rubber at 60 phr to 65 phr. 2 / g~170m 2 / g and / or COAN in the range of 70 mL / 100 g to 115 mL / 100 g. The filler may further comprise silica.
[0318] Another example of a specific combination of filler and elastomer is one in which the filler is or includes silica, and the elastomer is or includes natural rubber, or the elastomer is or includes styrene-butadiene rubber. The styrene-butadiene rubber can be or include oil-extended styrene-butadiene rubber. The silica can be dispersed in the natural rubber or styrene-butadiene rubber at a loading ranging from 40 phr to 75 phr, or other loadings described herein. The silica can be dispersed in the natural rubber or styrene-butadiene rubber at a loading ranging from 80 phr to 75 phr. 2 / g~250m 2 The polymer may have a BET surface area in the range of 1 / g.
[0319] Another example of a specific combination of filler and elastomer is one in which the filler is or includes silicon-treated carbon black and the elastomer is or includes natural rubber. By way of example, the silicon-treated carbon black is dispersed in natural rubber at a loading ranging from 40 phr to 65 phr, or other loadings described herein. The silicon-treated carbon black is dispersed in natural rubber at a loading ranging from 60 phr to 65 phr. 2 / g~170m 2 / g, e.g. 60m 2 / g~150m 2 / g and / or a COAN in the range of 70 mL / 100 g to 130 mL / 100 g, e.g., 70 mL / 100 g to 125 mL / 100 g, 70 mL / 100 g to 120 mL / 100 g, or 70 mL / 100 g to 115 mL / 100 g.
[0320] Also disclosed herein are articles of manufacture made from or including the composite materials or vulcanized rubbers disclosed herein.
[0321] The composite material may be used to make elastomer or rubber-containing products. Optionally, the elastomer composite material may be used in, for example, pneumatic tires as well as non-pneumatic or solid tires, e.g., Teki Tire treads, including caps and bases, undertreads, inner liners, tire sidewalls, tire carcasses, sidewall inserts, tire wire skims, and For retreaded tires Alternatively or additionally, the elastomeric composites (and subsequent vulcanizates) are used or manufactured for use in forming vulcanized rubbers that are compounded into various components of tires, including cushion gums, etc. Alternatively or additionally, the elastomeric composites (and subsequent vulcanized rubbers) are used in hoses, seals, gaskets, weatherstrips, wipers, auto parts, liners, pads, housings, wheel and track elements, pneumatic tires, and non-pneumatic or solid tires. ,Ta Tire sidewall inserts, tire wire skims, and For retreaded tires Alternatively or additionally, the elastomeric composite material (and subsequent vulcanization) may be used for cushion rubber. Alternatively or additionally, the elastomeric composite material (and subsequent vulcanization) may be used for hoses, seals, gaskets, vibration isolation products, track pads for trucks, truck-propeller equipment such as bulldozers, engine mounts, seismic stabilization equipment, mining equipment such as sieves, linings for mining equipment, conveyor belts, chute liners, slurry pump liners, mud pump parts such as impellers, valve seats, valve bodies, piston hubs, piston rods, plungers, slurry mixing impellers and slurry pump impellers, etc. The elastomer composites may be used in various applications, such as impellers for various applications, grinding mill liners, cyclones and hydrocyclones, expansion joints, marine equipment such as linings for pumps (e.g., dredge pumps and outboard motor pumps), hoses (e.g., dredge hoses and outboard motor hoses), and other marine equipment, shaft seals for marine, oil, aerospace, and other applications, propeller shafts, linings for piping, such as for transporting oil sands and / or tar sands, and other applications where wear resistance and / or enhanced dynamic properties are desirable. Furthermore, the vulcanized elastomer composites may be used in rollers, cams, shafts, pipes, bushings for vehicles, or other applications where wear resistance and / or enhanced dynamic properties are desirable.
[0322] Thus, the articles of manufacture include vehicle tire treads, including caps and bases, sidewalls, undertreads, inner liners, wire skim components, tire carcasses, engine mounts, bushings, conveyor belts, vibration isolation devices, weatherstrips, wipers, automotive parts, seals, gaskets, hoses, liners, pads, housings, and wheel or truck components.
[0323] With respect to the present disclosure, any "option" or "optional feature" can be combined with any other optional feature. It should be understood that the disclosure herein refers to certain illustrated examples, and that these examples are presented by way of example and not limitation. The intent of the foregoing detailed description is to discuss illustrative examples, but should be construed to cover all modifications, permutations, and equivalents of those examples that fall within the spirit and scope of the invention as defined by the additional disclosure.
[0324] The entire contents of all cited references in this disclosure are incorporated herein by reference to the extent not inconsistent with the present disclosure.
[0325] The present invention may include any combination of the various features of the above-described embodiments and / or the following claims, as set forth in sentences and / or paragraphs. Any combination of the features disclosed herein is considered part of the invention, and no limitation by features that can be combined is intended.
[0326] Other embodiments of the invention will be apparent to those skilled in the art from consideration of the specification and practice of the invention disclosed herein. It is intended that the specification and examples be considered as exemplary only, with a true scope and spirit of the invention being indicated by the following claims and equivalents thereof. [Example]
[0327] example These examples illustrate the preparation of elastomer composites and corresponding vulcanizates from various elastomers and fillers.
[0328] All mixing and compounding was performed in one of the following mixers: a BR-1600 Banbury® mixer (“BR1600”; manufacturer: Farrel), a BB2 tangential mixer (“BB2”; Kobelco Kobe Steel Group), a BB-16 tangential mixer (“BB-16”; Kobelco Kobe Steel Group), a BB-72 tangential mixer (“BB-72”; Kobelco Kobe Steel Group), and an FCM™-6 Farrel continuous mixer (“FCM”; Farrel-Pomini) equipped with #7 and #15 rotors. The BR1600 mixer was operated with two two-blade tangential rotors (2WL) providing a 1.6 L capacity. The BB2 mixer was operated with two four-blade tangential rotors providing a 1.5 L capacity. The BB-16 mixer was operated with two tangential rotors selected from the following types: 6WI6-blade ("6W"), 4WH4-blade ("4WH"), 4WN4-blade ("4WN"), and 2S2-blade ("2W"). These rotors provided the following mixer capacities, respectively: 14.4 L, 16.0 L, 16.2 L, and 17.7 L. The BB-72 mixer was operated with two 4WN rotors, providing a mixer capacity of 66.2 L. For batch mixers, ram pressure is defined as the pressure of the liquid supplying the force to the ram piston.
[0329] The moisture content of the delivered composite material was measured using a moisture balance (Model: HE53, Manufacturer: Mettler, Toledo, NA, OH). The composite material was sliced into small pieces (size: length, width, height <5 mm) and 2-2.5 g of material was placed on a disposable aluminum disc / plate, which was placed in the moisture balance. The weight loss was recorded for 30 minutes at 125°C. At the end of 30 minutes, the moisture content of the composite material was recorded as follows: Moisture content of composite = (initial weight - final weight) / initial weight * 100.
[0330] A small amount of organic volatile content (<0.1 wt%) may be included in this moisture test value.
[0331] The carbon black loading in the composites was determined by thermogravimetric analysis (Model Q500 unit, manufacturer: TA Instruments, DE). Approximately 15–20 mg of rubber sample was used. The sample was first heated under a nitrogen atmosphere from room temperature to 125°C at 30°C / min and isothermal for 30 minutes to remove moisture, then heated at 30°C / min up to 550°C and isothermal for 5 minutes to determine the organic content, which is primarily rubber content. After the atmosphere was replaced with air, the sample was then heated isothermal to 800°C at 30°C / min for 15 minutes to determine the carbon black content and other inorganic residues. The carbon black loading was then calculated based on the rubber and carbon black content data. For samples containing silica or silicon-treated carbon black, the remaining inorganic residue was attributed to that component as well as zinc oxide and was calculated based on the recipe.
[0332] The time-average water release rate for a particular mixing step was calculated from the amount of water lost per kg of composite material per unit time. Specifically, the time-average release rate was calculated as follows: Time-averaged release rate (kg / kg min) = total water removed / (release time × composite weight) (In the formula: Composite weights are determined on a dry weight basis; Total water removed (kg) = water in wet filler - water content in delivered composite; Delivery time = Ram stop time (min) - Rubber only mastication time (min).
[0333] Unless otherwise noted, mastication time for the gum only was 0.5 minutes.
[0334] Energy applied to the rotor (E R ) was calculated as follows: Energy efficiency = required heat / E R ×100%, (In the formula: - Heat requirement (kJ / kg) is the energy (kJ) required to remove water from 1 kg of composite (dry basis) with 100% efficiency, -The required heat is (heat of vaporization) + (sensible heat), - Heat of vaporization = liquid removed (kg) * latent heat of water vaporization (2260kJ / kg), -Sensible heat = water removed (kg) * specific heat capacity of water (4.1855 kJ / kg / K) * (100 - ambient temperature °C), - Amount of water removed (kg) = total water added to mixer (kg) - moisture content of delivered composite (kg).
[0335] Typically, the amount of moisture content at the time of loading can be determined from the amount of water in the wet filler.
[0336] Specific Energy (SE) is the energy applied to the rotor(s) between loading of solid elastomer and / or wet filler and delivery per kg of composite on a dry weight basis. Specific Energy is over the mixing time (ram stop time for single-stage and first-stage batch mixes).
[0337] The following tests were used to obtain performance data for each vulcanizate: The tensile stress at 100% elongation (M100) and 300% elongation (M300) were evaluated according to ASTM D412 (Test Method A, Die C) at 23°C, 50% relative humidity, and a crosshead speed of 500 mm / min. Tensile strain was measured using an extensometer. The ratio of M300 / M100 is referred to as the tensile stress ratio (or modulus ratio). Maximum tan δ was measured on an ARES-G2 rheometer (manufacturer: TA Instruments) using an 8 mm diameter parallel plate geometry in torsion mode. The vulcanized rubber specimen size was 8 mm in diameter and approximately 2 mm thick. The rheometer was operated at a constant temperature of 60°C and a constant frequency of 10 Hz. Strain sweeps were performed with strain amplitudes from 0.1 to 68%. Measurements were obtained at 10 points per decade, and the maximum measured tan δ ("max tan δ") was reported and referred to as "tan δ" unless otherwise specified.
[0338] Example I: Natural rubber / carbon black (volume 1.6L) This section describes the preparation of composites containing natural rubber (NR) and carbon black and the corresponding vulcanizates. The characteristics of the carbon black filler are shown in Table 1 below. ASTM Grade N134, available as VULCAN® 10HD carbon black ("V10HD"), ASTM Grade N234, available as VULCAN® 7H carbon black ("V7H"), VULCAN® 3 carbon black ("V3"), Propel® X25 carbon black ("X25"), Propel® X39 carbon black ("X39"), ASTM Grade N330, available as Propel® X22 carbon black ("X22"), ASTM Grade N772, available as Regal® SRF carbon black ("SRF"), ASTM Grade N550, available as Spheron® SOA carbon black ("SOA"), and ASTM Grade N375, available as Vulcan® J carbon black ("VJ"), were all obtained from Cabot Corporation. [Table 1]
[0339] This example illustrates the claimed and comparative blending processes. Three comparative blending processes were prepared:
[0340] 1. Dry Mix: Dry (non-wet) carbon black was prepared by mixing with solid natural rubber (samples Dry 1 to Dry 19).
[0341] 2. Comparative wet mix: Carbon black with a moisture content ranging from 10% to 50% was mixed with water by spraying or adding water onto the carbon black pellets in a container. This carbon black was then mixed with solid natural rubber (SMR20) and rubber chemicals (see Recipe 2 in Table 2 below) at a TCU temperature (TCU) of 60°C. z ) (Samples Comp1 to Comp10).
[0342] 3. Liquid Masterbatch ("LMB"): Prepared by mixing carbon black slurry with natural rubber latex. Table 2 lists the fillers and loadings used. [Table 2]
[0343] Preparation of the liquid masterbatch samples was based on the method described in Example 2 of U.S. Pat. No. 8,586,651, with the following exceptions: the latex elastomer (diluted and desludged MVL Field Latex) had a dry rubber content of 28%, and the filler slurry contained 13-14 wt. % carbon black. The flow rates were adjusted to achieve the desired production rate and the target final carbon black loadings listed in Table 2. The dewatered composite was masticated, mixed with 2 phr of antioxidant (6 PPD), dried in an FCM™ 6, and further masticated, cooled, and dried in an open mill.
[0344] For composites prepared according to the claimed invention, i.e., (Examples Ex1 through Ex28), wet carbon black was obtained either by mixing fluffy carbon black from the normal CB manufacturing process with water in a pin pelletizer at 60°C (never-dried carbon black) or by rewetting dried carbon black in a pelletizer (rewetted carbon black). Both methods provided pellets with water-in-filler concentrations ranging from 50% to 60%. For the rewetted carbon black, the carbon black samples were first milled in an 8" Model MicroJet Mill to produce fluffy carbon black particles with 99.5% particle size diameter less than 10 μm. This fluffy carbon black was then rewetted in a pin pelletizer to regenerate wet pellets.
[0345] All mixing and compounding was done in a BR1600 mixer at a ram pressure of 2.8 bar. The rubbers used were standard grades RSS1 and SMR20 natural rubber (Hokson Rubber, Malaysia). Technical descriptions of these natural rubbers are widely available, for example in Rubber World Magazine's Blue Book, published by Lippincott and Peto Co., Akron, OH, USA.
[0346] The mixing protocol for preparing this composite is outlined in Table 3. For all mixes, the total mastication time was 30 seconds. The time intervals listed in the mixing method below refer to the time period from the start of mixing, which is defined as "0 seconds." The term "smalls" refers to the combination of antioxidants and rubber chemicals. [Table 3]
[0347] In Table 3, the first occurrence of the mentioned temperature or time is the preferred option (e.g., 140°C or 180 s, whichever occurs first). For mixing method "1.6LC," mixing was carried out for 300 s, but the mixer rpm was reduced to ensure that the temperature did not exceed 160°C. For mixing method "1.6LH," the mixer was operated without cooling water.
[0348] After each mixing stage, the composite material was sheeted onto a two-roll mill operated at 50°C and approximately 37 rpm, followed by three or five passes through a nip gap of approximately 5 mm, with a rest time of at least 3 hours between mixing stages.
[0349] Table 4 lists the carbon black type, loading, mixing protocol, operating conditions, and resulting data for each sample. "FF" refers to loading fraction. "Specific Energy" refers to total specific energy. [Table 4-1] [Table 4-2] [Table 4-3]
[0350] For each of Ex. 1-28, the carbon black yield loss was less than 5 wt. % based on the total weight of the composite.
[0351] Vulcanizates were prepared by compounding Stage 1 or 2 composites with rubber chemicals, including various additives such as antioxidants, zinc oxide, and stearic acid ("smalls"), as well as curatives, followed by curing. The recipe is listed in Table 5. The wax beads were Akrowax™ 5031 wax beads, CBS (N-cyclohexyl-2-benzothiazole sulfenamide) was the accelerator CBTS, and TBBS (N-tert-butyl-2-benzothiazole sulfenamide) was the accelerator BBTS, all from Akrochem (Akron, OH). [Table 5]
[0352] The compounding protocol is shown in Table 6. For all smalls-containing composites, Stage 1 compounding was omitted, and the composites subjected only to the "1.6L Compound C" Stage 2 compounding procedure (referred to as "Stg2" in Table 8). [Table 6]
[0353] After each compounding stage, the compound was sheeted onto a two-roll mill operated at 50°C and approximately 37 rpm, followed by three passes through a nip gap of approximately 5 mm, with a rest time of at least 3 hours before the next mixing stage.
[0354] Curing of the samples was carried out in a heated press for a time determined by a conventional rubber rheometer, e.g., T90 + 10% of T90, where T90 is the time to achieve 90% vulcanization. The curing conditions are outlined in Table 7 below. [Table 7]
[0355] Table 8 shows the mixing conditions and properties for each sample. [Table 8-1] [Table 8-2]
[0356] Composites discharged from the wet-mix comparative process either exhibited high moisture content or high carbon black yield loss when the carbon black was wetted with more than 20% water, either of which produced composites with poorly dispersed filler. For example, comparative samples Comp1, Comp5, and Comp6 in Table 4 were discharged with a moisture content greater than 10%. Comparative samples Comp2 and Comp3 visibly exhibited loose carbon black on their surfaces, and carbon black yield loss was measured to be greater than 15%. It should be noted that the maximum tan δ values for comparative samples Comp2 and Comp3 are low, resulting from the high amount of carbon black yield loss of greater than 15% (see Table 14). For Comp4, mixing for 30 minutes resulted in a small temperature or torque increase after 30 minutes, and the suitable discharge temperature was not reached. To obtain a vulcanizable composite, Comp4 was mixed for an additional hour at 60°C. Comp5 had a yield loss of 3 phr and visible rough carbon black on its surface. Comp1 and Comp5 were subjected to additional vacuum drying to reduce the moisture content in the composites. For comparative wet-mixing processes with Tz below 65°C, it was found that composites with moisture content less than 10% could only be achieved by reducing the initial moisture content in the filler to 10%, as evidenced by comparatives Comp7 through Comp10. Comp6 was subjected to an additional mixing stage to reduce the moisture content as described in Example X, and the results of the second-stage composite are shown in Table 8. After the second stage of drying, the dried Comp6 composite, i.e., Comp6 SG2, showed no improvement in tan δ compared to Dry5, accompanied by poor mechanical properties as evidenced by a dramatic decrease in the M300 value. In contrast, Ex.4 showed improvements over Dry5 in both the tensile stress ratio (M300 / M100) and tan δ.
[0357] In contrast, the composites formed by the claimed process, i.e., Examples Ex. 1 through Ex. 28, all had moisture contents of less than 2% at delivery, even when at least 50% water was present in the filler. Such low moisture contents were achieved by the claimed mixing process alone, without additional steps such as additional vacuum drying (and with a total mixing time of no more than 35 minutes).
[0358] It can be seen that the rubber properties of the wet-mix comparative composites are not superior to those of the dry-mix comparative compositions. From the data in Table 8, it can be seen that the vulcanizates prepared from composites prepared by the claimed process exhibit: (a) at least one improvement in tan δ and tensile stress ratio (M300 / M100) compared to the dry-mix and wet-mix comparative samples, and (b) tan δ and tensile stress ratio properties similar to the composites made from the liquid masterbatch process (see LMB1 through LMB3). The liquid wetting the filler is believed to make the filler more easily dispersible in the solid elastomer. Wetting the filler allows for longer mixing times compared to dry-mixes, which provides more time to disperse the filler in the elastomer.
[0359] This example demonstrates that the claimed process, including the use of wet carbon black and application of certain input variables, such as a higher TCU temperature (Tz), provides optimal mixing conditions for improved filler dispersion and ultimately improved rubber properties. The comparative wet mix demonstrates that although the mixing time at a TCU temperature of 60°C is longer compared to the dry mix, the liquid is removed at a slower rate, resulting in composites with either high moisture content or long mixing times (greater than 1 hour) to achieve low moisture content.
[0360] Comparative samples Comp11, Comp12, and Comp13 were natural rubber wet carbon black blends performed without a TCU temperature setting, i.e., without controlling the mixer surface temperature. Comp11 and Comp12 had identical recipes and mixing methods. Due to the high 85% fill rate, ram deflection was very high. The resulting composite had significant moisture and unincorporated carbon black on the surface of the composite. Comp13 was prepared with a 75% fill rate. After 600 seconds of mixing, Comp13 still had significant moisture and unincorporated carbon black on the surface of the composite. Due to the poor properties of these composites, Comp11, 12, and 13 did not cure. Without controlled mixer surface temperature, the mixer conditions were constantly changed after each batch of mixing. The temperature of the mixer walls and rotors increased over time due to accumulated heat and lack of effective cooling. For example, for Comp11, the rubber was masticated to reach 91°C in 100 s; for Comp12, which was mixed after Comp11, the mastication reached 91°C in only 58 s. Without the use of cooling water, the mixer surface temperature was inconsistent, resulting in significant batch-to-batch variation.
[0361] This process generally resulted in a higher time-averaged release rate of liquid per unit of composite weight (ranging from 0.01 to 0.07 kg liquid / kg composite·min) compared to the comparative wet-mix samples run at 60 °C in TCU. Such higher liquid release rates resulted in a favorable reduction in moisture content over the optimal mixing time.
[0362] The claimed energy efficiency values reflected the increased energy input (contributing to the total specific energy) to the system driving the rotor to achieve a dry composite. Illustrative energy efficiencies ranged from 20% to 80%, which was generally higher than that of the comparative wet mixing process performed at 60°C in the TCU. Comp1, Comp5, and Comp6 provided energy efficiencies within the 20% to 80% range, but these comparative composites had moisture content values greater than 10 wt%.
[0363] Example II: Natural Rubber / Carbon Black (16L and 66L volumes) This example describes the preparation of composites and corresponding vulcanized rubbers, where composites were prepared according to the claimed process with various mixer types, rotor types, and other operating variables such as rotor speed, tip speed, and TCU temperature ("Tz"). The rubbers used were standard grade natural rubbers RSS1, RSS3, SMR5, and SMR20 natural rubber (Hokson Rubber, Malaysia). Technical descriptions of these natural rubbers are widely available, for example, in Rubber World Magazine's Blue Book, published by Lippincott and Peto Co., Akron, Ohio, USA.
[0364] Specifically, all samples were prepared by milling and rewetting V7H carbon black as described in Example I to provide wet carbon black pellets having a moisture content ranging from 55 to 60%. The composites in this example, i.e., Ex. 29-76, incorporated wet carbon black having a moisture content ranging from 55 to 60%. Dry mix samples were also prepared (Dry 20 to Dry 23). As demonstrated in Example I, the comparative mixes did not result in properly dried and / or dispersed composites, and comparative wet mix examples were not prepared due to handling and safety issues with large-scale mixing.
[0365] Mixing and blending were performed with BR1600, BB-16, and BB-72 mixers. In a specific case, blending was performed with a BB2 tangential mixer (Kobelco Kobe Steel Group) equipped with two four-blade tangential rotors providing a volume of 1.5 L. Table 9 shows the mixing protocol, where "Var" refers to the range of values identified in Table 10. [Table 9]
[0366] For mixing protocols 16L H and 16L I, the composites were roll milled in the same manner as described in Example I, but for five passes. For mixing protocols 16L J, 16L K, and 66L L, the discharged composites were passed through a TSR-125 twin-screw delivery extruder (Kobelco Kobe Steel Group) equipped with a roller head. The mixing conditions and properties are listed in Table 10. [Table 10-1] [Table 10-2]
[0367] For each of Ex. 29-76, the carbon black yield loss was less than 5 wt. % based on the total weight of the composite.
[0368] Vulcanizates were formed by compounding the composite materials with rubber chemicals. The rubber chemicals compounding table is shown in Table 11, and the compounding protocol is shown in Table 12. [Table 11] [Table 12]
[0369] Samples Dry 20 and Ex. 29 to Ex. 56 were compounded according to protocol 1.6 L Compound D. After each compounding stage, the compounds were sheeted on a two-roll mill operated at 50° C. and approximately 37 rpm, followed by six end-rolling passes with a nip gap of approximately 5 mm, with a rest time of at least 3 hours before the next mixing stage.
[0370] The formulations of Dry 21 to Dry 23 and Ex. 57 to Ex. 76 were carried out according to 1.5L Formulation E. After formulation, the compounds were sheeted to a thickness of 2.4 mm on a two-roll mill operated at 60°C. All samples were cured at a pressure of 100 kg / cm.2 The vulcanizate properties are listed in Table 13. [Table 13-1] [Table 13-2]
[0371] From Table 13, it can be seen that vulcanizates prepared from composites produced by the claimed process exhibit: (a) at least one improvement in tan δ and tensile stress ratio (M300 / M100) for composites such as Ex. 70 (51 phr), Ex. 73 (46 phr), and Ex. 64 (56 phr) compared to dry mix comparison samples of the same recipe, such as Dry 21 (51 phr), Dry 22 (46 phr), and Dry 23 (56 phr), and (b) properties similar to composites produced from a liquid masterbatch process (see Ex. 43 (50 phr) and Ex. 70 (51 phr) compared to liquid masterbatch LMB3 (50 phr)). These results, achieved with the larger mixer volumes of 16 L and 66 L, are similar to those demonstrated in Example 1, which was performed with a mixer volume of 1.6 L.
[0372] In general, the data in Examples 1 and 2 indicate that the additional energy input to the mixing process (as indicated by the resulting total specific energy) when compared to a comparative wet-mixing process enhanced the mixing of the wet filler and dry elastomer, allowing a sufficient amount of moisture to be removed in a shorter period of time while incorporating the filler into the elastomer. The data in Tables 4 and 10 indicate that the claimed process achieves higher specific energy and energy efficiency when compared to its comparative wet-mixing counterpart, resulting in composites with lower moisture contents, specifically 4% or less, and vulcanized rubbers with improved properties.
[0373] As shown by the comparative wet mixes, TCU temperatures not exceeding 65°C did not produce a sufficient temperature rise to release water. Comp1 through Comp6 (Comp7 through Comp10 had 10% water content in the carbon black). In contrast, at Tz temperatures above 65°C, the mixes experienced a temperature rise adequate for water removal. As the temperature increased, the temperature control acted as a coolant, allowing for longer mixing times. Finally, the temperature increased to a mixer temperature of at least 140°C to deliver the composite.
[0374] As in Example I, the energy efficiency ranged from 20% to 80%, and the average liquid release rate / kg composite was 0.01–0.07 kg liquid / kg composite·min. Such values were not obtained from a comparable wet-mixing process that produced composites with low moisture contents.
[0375] Increasing the tip speed can also increase the shear experienced by the mixture. Table 10 shows the increase in tip speed with increasing rotor speed and mixer chamber volume. Typically, such specific energy and tip speed are not optimal for dry mixes because high shear conditions can cause the elastomer to heat up rapidly and decompose before the filler can be properly dispersed in the elastomer. The use of a rotor with at least four blades allows for energy efficiency of at least 40%.
[0376] The data in Examples 1 and 2 also demonstrate that the presently claimed process allows for the preparation of composites without the presence of rubber chemicals. In the mixes of Ex. 53 and 54, the smalls were charged to the mixer simultaneously with the elastomer, where the smalls included the rubber chemicals. For Ex. 49 and 51, the smalls were added after the elastomer and filler charging was complete and the mixture reached a temperature of 140°C. Ex. 39, Ex. 52, Ex. 55, and Ex. 56 were mixed with only antioxidant present in the initial wet filler / elastomer mixture. All of these mixes were performed with the same carbon black type and loading, in the same mixer, and under essentially the same conditions. The data in Table 13 for Ex. 49, Ex. 51, Ex. 39, Ex. 52, Ex. 55, and Ex. 56 demonstrate that more optimal rubber properties were obtained for mixes without rubber chemicals present at the start of the mix.
[0377] It was discovered that in the wet mixing process, the mixture swells in the presence of water, and the swelling can interfere with the distribution of the carbon black. As shown in Table 14, it was discovered that reducing the loading reduces this swelling and surprisingly improves the rubber properties of the vulcanizate. [Table 14]
[0378] Previous data for the samples in Table 14 can be found in Tables 4, 8, 10, and 13, and some of the data is reproduced in Table 14. Additionally, Table 14 lists the carbon black yield loss and maximum ram deflection. The comparative wet mixing processes Comp1, Comp2, and Comp3 were run at loadings of 75% or 85%. The resulting maximum ram deflection values were high, greater than 30% of the rotor diameter. In contrast, the present wet mixing process was run at lower loadings ranging from 68% to 72%. As the loading decreased, the corresponding ram deflection decreased for the comparative wet mixing process. Furthermore, as the loading decreased from 72% to 68% for the present process, the ram deflection value decreased from 21% of the rotor diameter to less than 10%. At least one of the tensile stress ratio M300 / M100 and tan δ improved at lower loadings.
[0379] Example III: Natural Rubber / Silica This example describes the preparation of a natural rubber / silica composite and vulcanized rubber. The silica used was ZEOSIL® Z1165 MP precipitated silica from Solvay USA, Inc. (Cranberry, NJ). The coupling agent was Si-69 silane coupling agent ("Si69"; Evonik Industries). The silane coupling agent was added along with the first portion of silica.
[0380] Silica pellets, initially at 5-7% moisture content, were placed in a container and wetted by slowly incorporating additional water while stirring. The mixture was then further mixed overnight in a rotating drum. Composites of silica and natural rubber (RSS1) were prepared in a BR1600 mixer according to the protocol in Table 15 and under the conditions in Table 16. [Table 15] [Table 16]
[0381] The vulcanizates were compounded according to the recipe in Table 17 and the mixing protocol in Table 18. The vulcanizates were then cured at 150°C for 30 minutes. [Table 17] [Table 18]
[0382] The vulcanizate properties are shown in Table 19. [Table 19]
[0383] It can be seen that compared to dry mixing, natural rubber / silica composites prepared by the claimed process result in vulcanizates with reduced tan δ values and increased tensile stress ratios.
[0384] Example IV: Natural Rubber / Carbon Black-Silica This example describes the preparation and vulcanization of a composite containing a blend of natural rubber and silica and carbon black fillers. Two different filler ratios were used: carbon black / silica = 35:15 or 15:35. The silica used was ZEOSIL® Z1165 MP precipitated silica from Solvay USA, Inc. (Cranberry, NJ). The coupling agent was Si-69 silane coupling agent ("Si69"; Evonik Industries) and was added along with the first portion of silica. Propel® X25 carbon black, never dry, was used (see Table 1). Silica pellets were wetted as described for the natural rubber / silica composite in Example III.
[0385] Natural rubber (RSS1), carbon black, and wet silica were mixed in a BR1600 mixer according to the protocol in Table 20 and under the mixing conditions in Table 21. [Table 20] [Table 21]
[0386] The vulcanizates were prepared by compounding the formulations in Table 22 according to the protocol in Table 23, followed by curing at 150°C for 30 minutes. [Table 22] [Table 23]
[0387] The vulcanizate properties are shown in Table 24. [Table 24]
[0388] It can be seen that compared to the dry mix, composites made from wet carbon black / silica filler blends at two different filler ratios resulted in vulcanizates with reduced tan δ values and increased tensile stress ratios when compared to similar filler ratios.
[0389] Example V: Styrene-butadiene rubber / silica This example describes the preparation and vulcanization of a composite containing styrene butadiene rubber solution (BUNA® VSL 4526-0 HM S-SBR, Lanxess, Germany) and silica. The silica used was ZEOSIL® Z1165 MP precipitated silica from Solvay USA, Inc. (Cranberry, NJ). Silica pellets were wetted as described for the natural rubber / silica composite. Silane coupling agent X50S (Evonik Industries) was added along with the first portion of silica.
[0390] The SBR and silica were mixed in a BR1600 mixer according to the protocol in Table 25 and under the mixing conditions in Table 26. [Table 25] [Table 26]
[0391] The vulcanizates were compounded according to the protocol in Table 28 and the recipe in Table 27 for both samples, followed by curing at 150°C for 30 minutes. For Ex. 85, 6PPD was added only in Stage 1, and TMQ, ZnO, stearic acid, and wax were added in Stage 2, whereas for Dry 32, all the smalls, i.e., 6PPD, TMQ, ZnO, stearic acid, and wax, were added in Stage 1. N,N'-diphenylguanidine ("DPG" powder) is a vulcanization accelerator. [Table 27] [Table 28]
[0392] The vulcanizate properties are shown in Table 29. [Table 29]
[0393] It can be seen that compared to dry blending, composites made from wet silica result in vulcanizates with reduced tan δ values and increased tensile stress ratios.
[0394] Example VI: Natural Rubber:Butadiene Rubber (80:20) / Carbon Black This example describes the preparation and vulcanization of a composite containing an 80 / 20 blend of natural rubber (RSS1) and butadiene rubber (Buna® CB 22 butadiene rubber (Lanxess, Germany)) with carbon black filler. The carbon blacks used were never-dried VULCAN® 7H carbon black and Propel® X25 carbon black.
[0395] Natural rubber (NR), butadiene rubber (BR), and carbon black (50 phr for dry and wet CB) were individually charged and mixed in a BR1600 mixer according to the protocol in Table 30 and under the mixing conditions in Table 31. [Table 30] [Table 31]
[0396] The vulcanizates were compounded according to the protocol in Table 33 and the recipe in Table 32. The compounds were then cured at 150°C for 30 minutes. [Table 32] [Table 33]
[0397] The vulcanizate properties are shown in Table 34. [Table 34]
[0398] It can be seen that compared to composites prepared by dry blending of the same fillers, composites made from wet carbon black yield vulcanizates with reduced tan δ values and increased tensile stress ratios.
[0399] Example VII: Natural rubber / carbon black-reduced graphene oxide This example describes the preparation of composites containing natural rubber and a filler blend containing wet carbon black and reduced graphene oxide (rGO) and vulcanized rubber. Specifically, the reduced graphene oxide is a form of high-density reduced graphene oxide, which was prepared as disclosed in U.S. Provisional Patent Application No. 62 / 857,296, filed June 5, 2019, the disclosure of which is incorporated herein by reference. The high-density reduced graphene oxide contains water in a 1:4 mass ratio of rGO to water.
[0400] A reference mixture was prepared from a natural rubber (SMR20) / rGO masterbatch mixed with additional SMR20 rubber and dry Vulcan® J carbon black. The first example was prepared similarly to the reference, except that wet carbon black was incorporated. In the second example, the elastomer was directly compounded with wet carbon black (prepared by adding water to carbon black pellets in a container; 50 wt.% moisture) and rGO. The final compound recipe is provided in Table 35. The mixing protocol for the NR / rGO masterbatch is provided in Table 36, and the protocol for the NR / CB-rGO composite is found in Table 37. [Table 35] [Table 36] [Table 37]
[0401] After each mixing stage, the composite material was sheeted onto end rolls operated at 50°C and about 37 rpm, followed by six end rolls with a nip gap of about 5 mm, with a rest time of at least 3 hours before the next mixing stage.
[0402] The vulcanized rubber was compounded according to the method in Table 38. [Table 38]
[0403] The vulcanizate properties are shown in Table 39. [Table 39]
[0404] It can be seen that compared to the reference examples, the composites prepared from the wet fillers yield vulcanizates with lower tan δ values and higher tensile stress ratios.
[0405] Example VIII: Styrene-Butadiene Rubber / Silicon-Treated Carbon Black This example describes the preparation of a composite and vulcanizate containing a styrene butadiene rubber solution (BUNA® VSL 4526-0 HM S-SBR, Lanxess, Germany) and EcoBlack™ CRX4210 silicon-treated carbon black obtained from Cabot Corporation, prepared as described in U.S. Patent No. 6,028,137, which is incorporated herein by reference. This silicon-treated carbon black was prepared using STSA 119m 2 / g, 109 mL / 100 g of COAN, and a silicon content of 10.2%. The coupling agent was Si69, which was blended with V3 in a 1:1 weight ratio. The Si69 / V3 blend was added along with the first portion of the silicon-treated carbon black. The silicon-treated carbon black pellets were wetted as described for the natural rubber / silica composite in Example III.
[0406] The SBR and silicon-treated c...
Claims
1. 1. A composite material containing a filler dispersed in an elastomer, wherein the filler contains carbon black in an amount of at least 50% by weight based on the total weight of the filler, and the elastomer contains at least 50% by weight of natural rubber based on the total weight of the elastomer, and the composite material has the following properties: (a) The filler has a state of dispersion in the elastomer according to formula (1): A≦1.25*B+x (1) (In the formula: A is the area equivalent diameter (μm) of the filler particle in the composite material 90 and B is [total area of particles having an area-equivalent diameter ≧2 μm] / [total contrast area]×100% where B≧1%; A and B are determined by optical microscopy in transmission mode on microtome sections, and x is a number ranging from 15 to 20; and (b) The composite material has properties according to equation (2): G'(0.1%) / G'(200%)≦0.1*G'(50%)-y (2) wherein G'(0.1%) is the dynamic storage modulus measured at 0.1% strain amplitude, G'(200%) is the dynamic storage modulus measured at 200% strain amplitude, G'(50%) is the dynamic storage modulus measured at 50% strain amplitude, the dynamic storage modulus measured at a frequency of 1 Hz, 100°C, and y is a number in the range of 7 to 10.
2. 1. A vulcanizate containing a filler dispersed in an elastomer, wherein the filler comprises carbon black in an amount of at least 50% by weight based on the total weight of the filler, and the elastomer comprises natural rubber in an amount of at least 50% by weight based on the total weight of the elastomer, and wherein: Carbon black is at least 60m 2 / g STSA and a BET / STSA ratio in the range of 1 to 1.2; and The vulcanized rubber has resistivity and dispersion properties that satisfy equation (3): [ln(R)-3.8] / [0.28*δ]≧0.0004*ν+0.9 (3) (In the formula: R is the resistivity (ohm-cm); d=(6000・[0.806・φ) -1/3 b -1/3 -1] / ρS)×β 1.43 Where: φ = volume fraction of carbon black in the composite, S = BET surface area of carbon black (m 2 / g), ρ=carbon black density, 1.8 g / cm 3 It is estimated that β=φ eff / f, φ eff teeth, f eff =φ[1+(0.0181*COAN)] / 1.59 where COAN is the compression oil absorption of the carbon black as determined by ASTM D3493; and ν≧65, where ν is the number of particles having an area-equivalent diameter of at least 4 μm per mm, as determined by optical microscopy in transmission mode on microtome sections. 2 Vulcanized rubber having a viscosity of 100:1 (wherein m is the numerical value of the viscosity).
3. The composite material of claim 1, wherein the elastomer further contains at least one rubber selected from polybutadiene rubber and styrene-butadiene rubber.
4. The composite material of claim 1 or 3, wherein x=15.
5. The composite material of claim 1, 3 or 4, wherein y=10.
6. The composite material of any one of claims 1 or 3-5, wherein the carbon black has an STSA of at least 60 m 2 / g.
7. The composite material of claim 1, wherein the carbon black has a COAN of at least 75 mL / 100 g.
8. The composite material of claim 1, wherein the carbon black has a BET / STSA ratio in the range of 1 to 1.
2.
9. The composite material of claim 1, wherein the composite material has a carbon black loading of 60 phr or less.
10. The composite material of claim 1, wherein the filler further contains silica.
11. A vulcanized rubber prepared from the composite material according to any one of claims 1 or 3 to 10.
12. The vulcanized rubber of claim 2, wherein the elastomer further contains at least one rubber selected from polybutadiene rubber and styrene-butadiene rubber.
13. The vulcanized rubber of claim 2 or 12, wherein the carbon black has a COAN of at least 75 mL / 100 g.
14. The vulcanized rubber of claim 2, 12 or 13, wherein the filler further comprises silica.
15. The vulcanized rubber of claim 2 or any one of claims 12 to 14, wherein the vulcanized rubber has a tensile stress ratio M300 / M100 of at least 5.9, where M100 and M300 refer to the tensile stresses at 100% and 300% elongation, respectively.
16. 16. The vulcanizate of any one of claims 2 or 12-15, wherein the vulcanizate has a maximum tan δ(60°C) not exceeding 0.
22.
17. A treated tire comprising the vulcanized rubber of any one of claims 2 or 12-16.
18. A product containing the vulcanized rubber described in any one of claims 2 or 12 to 16.
19. The product of claim 18, wherein the product is incorporated into a pneumatic, non-pneumatic or solid tire.
20. The article of claim 18, wherein the article is selected from tire treads, undertreads, inner liners, sidewalls, sidewall inserts, wire skims, and cushion gums for retreaded tires.
21. The article of manufacture of claim 18, wherein the article is selected from hoses, linings, liners, seals, gaskets, vibration isolation products, trucks, track pads for truck-propeller vehicle equipment, engine mounts, seismic stabilization devices, sieves for mining equipment, linings for mining equipment, conveyor belts, chute liners, slurry pump liners, mud pump impellers, valve seats, valve bodies, piston hubs, piston rods, plungers, slurry mixing impellers and slurry pump impellers, grinding mill liners, cyclones and hydrocyclones, expansion joints, linings for dredge pumps and outboard pumps for marine equipment, marine shaft seals, and propeller shafts.
Citation Information
Patent Citations
Tire comprising rubber composition
JP2012062393A
Carbon black composition with sulfur doner
US20190002702A1